Transparent and mechanically robust fish gelatin hydrogels through covalent–noncovalent interfacial regulation by dialdehyde carboxymethyl chitin nanofibers - Yuan Duan; Kai Ma; Xiao Fu; Shaoxiong Li; Rongqiang Chen; Jirong Zhao; Xiaoyu Wang; Yong Hong Meng; Shuai Zhang; Yurong Guo (Food Hydrocolloids, 2027)

Degradation of mycotoxins in cow milk by dielectric barrier discharge cold plasma and its effect on milk quality - Yike Han; Shangchen Fu; Meng Li; Siqi Wang; Yijie Lu; Wupeng Ge; Chunfeng Guo; Yuan Zhou; Zhenpeng Gao (International Dairy Journal, 2026)

Decoding and exploiting intratumoral microbiota: from microenvironment modulation to clinical intervention - Hongyuan Zhang; Xuehua Zhang; Jianran Guo; Xuefang Huang; Meng An; Yongna Qiao; Song Wang; Bo Fu (Molecular Biology Reports, 2026)

Characteristics and mechanism of karst groundwater cycle evolution under large-scale exploitation: a case study of the Yanxi karst groundwater system - Yawei Feng; Fengxin Kang; Fengfeng Shi; Xuesen Wang; Xianzhou Meng; Yifu Fu; Aijun Li; Hao Chen; Qingcheng He (Carbonates and Evaporites, 2026)

Where sky meets sea: Integrated aerosol and ocean color retrieval from PACE SPEXone multi-angle polarimetry - Meng Gao; Kamal Aryal; Peng-Wang Zhai; Kirk Knobelspiesse; Bryan Franz; Brian Cairns; Ivona Cetinić; Guangliang Fu; Otto Hasekamp; Amir Ibrahim; Andrew M. Sayer; P. Jeremy Werdell (Remote Sensing of Environment, 2026)

A synergistic enzymatic strategy for comprehensive improvement of bread quality and digestibility using a novel maltohexaose-forming amylase and a 4,6-α-glucanotransferase - Yu-chuan Wang; Hong Liu; Li-xiao Fu; Meng-jun Han; Qiao-juan Yan; Zheng-qiang Jiang; Yan-xiao Li (Food Hydrocolloids, 2026)

Laser pyrolysis of poly(methyl methacrylate) to high-yield and high-purity methyl methacrylate monomer: A solvent- and catalyst-free strategy for chemical recycling - Xu-Zhen Zhu; Guang-Jian He; Meng-Meng Wang; Fu-Lu Chang; Zi-Yang Hua; Hao-Bo Wang; Xuan-Qi Wu; Lun Chen (Chemical Engineering Journal, 2026)

A novel bidentate coordination bis-thionocarbamate collector for copper-sulfur separation under low-alkalinity conditions: Synthesis and adsorption mechanism - Zekun Wang; Xiaokun Fu; Yan Jin; Yao Meng; Haoran Cheng; Louyan Shen; Ming Li; Xingrong Zhang (Chemical Engineering Journal, 2026)

Electrostatic-interaction-tailored PAM-PA-ChCl deep-eutectic gel electrolyte for high-performance zinc‑iodine batteries - Yixin Zhao; Ming Chen; Zhen Wang; Qitong Sun; Wei Fu; Fanlu Meng (Chemical Engineering Journal, 2026)

Constructing a “switch” for photo-thermal catalytic pathway: Directional regulation of NO reduction product distribution by the coordination mode at the La site over Pd–La/CeO2 - Jianfei Li; Boxiang Du; Qian Xia; Zhuoran Bi; Xiangyu Meng; Jinlin Long; Zizhong Zhang; Wenxin Dai; Xianzhi Fu (Chemical Engineering Journal, 2026)

Prediction of critical heat flux under non-uniform heating in a 3 × 3 rod bundle based on CMFD - Fu Shengwei; Jiang Jiacheng; Jiang Jiahang; Jiao Meng (Annals of Nuclear Energy, 2026)

Chitosan/montmorillonite aerogel with polypyrrole coating via bidirectional freeze-casting achieving absorption-dominated EMI shielding with ultra-low thermal conductivity - Qingpeng Chen; Qiyu Zhuang; Guanghuan Li; Xiangming Li; Quan Liu; Meng Fu (Applied Clay Science, 2026)

An automated High-Precision farm mapping pipeline using UAV point clouds - Yongchao Shan; Yanxin Yin; Hao Wang; Guangqiang Zhang; Xiangchen Cao; Yue Zhao; Weiqiang Fu; Zhijun Meng; Chunjiang Zhao (Computers and Electronics in Agriculture, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

A comprehensive review on PIM-1 membranes for enhanced CO2 separation: strategies for CO2 transport enhancement - Shaohan Lian; Jiangxue Fan; Xiangyun Meng; Boyuan Fu; Siqi Zhang; Jing Han; Tianyang Zhao; Yanan Guan; Erhong Duan; Chunfeng Song (Environmental Research, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Single-mode topological state laser based on cholesteric liquid crystal microcapsules for ultra-high sensitivity detection of trace silver ions - Zhi Sun; Yu Zhao; Xiaowei Yang; Tao Chen; Yiqian Fu; Siyi Meng; Xiang Liu; Xiuhong Wang (Chemical Engineering Journal, 2026)

Inorganic Ammonia carbon capture pilot testing and simulation research - Xia Zhonglin; Fan Shuaijun; Zuo Jiahai; Wang Xiaohua; Chen Wentong; Yang Fu; Jia Jun; Chen Luyao; Meng Weian; Zhao Zhenyang; Zhu Hongtao; Ma Xiaoying; et al. (Chemical Engineering Journal, 2026)

Two-pronged strategy of pore size sieving and recognition sites tailoring for perfluoropropylene-perfluoropropane separation - Zongzhen Han; Meiting Wang; Meng Gao; Kunhua Wang; Hao Yu; Zhiguo Bian; Ruitao Lv; Wei Chen; Liangmin Ning; Min Fu (Chemical Engineering Journal, 2026)

High-entropy (TiVCrMnFe)2AlC MAX phase: Synthesis and application in efficient electrooxidation 5-Hydroxymethylfurfural to 2, 5-Furandicarboxylic acid - Shunxin Shao; Liying Fu; Hao Feng; Guangbo Che; Yonghui Gao; Renquan Guan; Ayesha Sadiqa; Asif Khan; Weiwei Meng; Yasin Orooji; Chunbo Liu; Ehsan Ghasali (Chemical Engineering Journal, 2026)

Low-temperature thermochemical energy storage behavior of Zn-doped phosphogypsum-based calcium sulfate dihydrate: Correlating defect evolution with electronic structure - Fei Mu; Shuai Luo; Meng Fu; Yuanyuan Li; Xuyuan Tang; Yaoqi Huang; Xiaomin Cheng (Chemical Engineering Journal, 2026)

Unraveling the impacts of 2D/3D urban morphology on thermal discomfort: Bridging objective and subjective perspectives under the LCZ framework - Teng Zhang; Baolei Zhang; Yu Cheng; Pingjie Fu; Fei Meng (Building and Environment, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Quantifying responses of concurrent PM2.5-O3 pollution to their precursors in the Yangtze River Delta megacity Cluster of China - Mingliang Ma; Mengjiao Liu; Mengnan Liu; Yihong Jiao; Fei Meng; Pingjie Fu; Jingxue Bi; Tongshuai Rong; Yangyang Liu; Yuqiang Wang; Huaqiao Xing (Environment, Development and Sustainability, 2026)

Strigolactones constrain rice drought acclimation by suppressing ROS scavenging through the D53–OsWRKY31–ZFP36 module - Qianqian Li; Yi Wang; Jijun Yan; Liquan Kou; Hao Zhang; Jinhua Yang; Qingliang Hu; Yanshuo Guo; Xinwei Ban; Nan Luo; Peiyong Xin; Yanhui Jing; et al. (Molecular Plant, 2026)

Numerical simulation of the evolution of the temperature field of phase change temperature-regulating asphalt pavement under the urban heat island effect - Dingjie Xu; Jiasheng Dai; Feng Ma; Zhen Fu; Chen Li; Yanzhe Zou; Yingjie Hou; Xiaolong Yang; Zhe Li; Meng Jia (Sustainable Cities and Society, 2026)

Numerical investigation on hydrodynamic interference in parallel water entry of vehicles with deflection angles - Xiao-Qiang Chen; Jia-Jie Wang; Chang Liu; Meng-Chao Zhang; Fu-Ren Ming (Ocean Engineering, 2026)

Loading-rate sensitivity of damage mechanisms in marine sedimentary coral reef limestone - Kai Wu; Xianfeng Zhang; Qingshan Meng; Peishuai Chen; Shuaiyang Fu; Yu Zhong; Qian Li; Fuquan Ji (Ocean Engineering, 2026)

First early Toarcian B/Ga paleosalinity record from the eastern Tethyan Ocean: Implications for hydroclimate evolution - Ying Nie; Wei Wei; Yansheng Shan; Shengqiang Zeng; Shuai Zhang; Ahmed Mansour; Rui Wang; Jianguo Yin; Shouji Pang; Fanyang Meng; Shiming Dong; Weihong Pan; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Unraveling microbiome, metabolome and volatilome profiles of naturally fermented sauerkraut from six Chinese cabbage cultivars - Jiayi Cao; Yuanlong Chen; Shuang Zhou; Huan Meng; Yushuai Wei; Chuanzhen Ma; Jianan Du; Haiyan Fu; Chunguang Liu; Xinyu Song; Fengshan Yang (Food Research International, 2026)

Edible Medicinal Choerospondias axillaris Polysaccharides: A Review on Extraction, Structure–Activity Relationships and Encapsulation Properties - Caijiao Li; Huijie Zhang; Yan Gong; Lei Fu; Jin Ma; Meng Wang (Food Bioscience, 2026)

Bi-doped SnO2 porous nanospheres for trace formaldehyde sensing at room temperature - Dan Meng; Yihang Fu; Lijun Li; Lei Zhang; Zongsheng Xie; Jian Qi; Xiaoguang San (Chemical Engineering Journal, 2026)

Temperature-responsive carbon dots-spiropyran photochromic films for stepwise-decryption optical anti-counterfeiting with information self-destruction - Meichen Meng; Zhimeng Ma; Mingbo Yue; Chang Liu; Xiaoyu Xu; Qiang Fu (Chemical Engineering Journal, 2026)

Synergistic regulation of bimetallic d-band centers in NiM-NiMOx (M = Co/Cu) catalysts toward enhancing selective hydrogenation - Liangmin Ning; Jun Xie; Shiyan Sheng; Jiawen Wang; Tianyu Zhang; Shuai Li; Shuanglu Fu; Tianqi Xie; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Synergistic cooling effects of UV protective shading and PV-ESS powered ventilation on pedestrian-level microclimate and modelled physiological heat stress - Shisheng Chen; Weiwei Yang; Jiayan Fu; Zhongqi Yu; Yumeng Jin; Meng Zhen; Lei Xu; Ruohan Xu; Chao Cen (Building and Environment, 2026)

Integration of NIRS and GWAS identifies GhMYB86 as a potential regulator of cottonseed protein content with pleiotropic effects on fiber strength in upland cotton - Yiwen Huang; Xi Huang; Longyu Huang; Shouyang Fu; Yuzhen Wu; Dayun Zhou; Jun Peng; Yajun Liang; Meng Kuang (Theoretical and Applied Genetics, 2026)

Mapping Whole-Brain Nonlinear Structure-Function Dynamics in Aging via Neural Granger Causality - Meng Niu; Shanli Ren; Chen Lin; QingChen Wang; Yongzhi Yin; Hanning Guo; Yu Fu (Brain Topography, 2026)

Contrasting mineral–microbial pathways drive phosphorus bioavailability under moderate pH shifts in agricultural soils - Meng Qi; Rongyang Cui; Anqiang Chen; Xinmei Zhao; Ming Ni; Zhiwu Li; Hui Yan; Chi Wang; Bin Fu (Applied Soil Ecology, 2026)

A comprehensive review of Nostoc commune polysaccharides: Preparation methods, structural characteristics, health benefits, and applications - Xinrui Xu; Mengru Zhang; Deqiang Yang; Lei Fu; Lihong Wu; Meng Wang (Algal Research, 2026)

Actin polymerization drives endogenous MMP-9 upregulation and blood–brain barrier disruption in ischemic brain endothelial cells - Yiyin Zhao; Songbin He; Yiming Wang; Meng Jin; Yichao Fu; Xiaojing Zhou (Molecular and Cellular Biochemistry, 2026)

Multi-omics analysis of untargeted metabolomics and gut microbiota study on the mechanism of Astragalus-Safflower to coordinate the regulation of energy metabolism pathways and gut microbiota remodeling to improve ischemic stroke - Junmin Fu; Fuyu Liu; Yun Han; Yonggang Feng; Kaixin Shan; Mimi Wang; Xiang Meng; Haibo Zhang; Mingsan Miao; Suxiang Feng; Xiaoyan Fang (Metabolic Brain Disease, 2026)

A physics-informed data-driven approach for long-term settlement of embankment widening - Boyang Xia; Meng Wei; Gang Zheng; Haizuo Zhou; Weichao Liu; Yongfeng Deng; Jun Xiong; Wei Zeng; Ziying Fu (Transportation Geotechnics, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

A pulsar escaping an ancient open cluster via tidal stripping - Lei Zhang; Xiaoting Fu; Di Li; Emma Carli; Long Wang; Jiaqi Zhao; Craig O. Heinke; Emanuele Dalessandro; Yang Chen; Angela Bragaglia; Duncan R. Lorimer; Ewan D. Barr; et al. (Science Bulletin, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Numerical investigation of dynamic response of HDPE raft-cage aquaculture systems under combined wave-current conditions: Multi-System coupling analysis - Fei Fu; Xiaoying Zhang; Zhanbin Meng; Di Ren; Xiangxi Han; Jianxing Yu; Zhe Hu (Ocean Engineering, 2026)

Quantitative criteria and deformation-dependent model for passive soil arching in compacted clay - Xiao-Hu Zhang; Han-Lin Wang; Xiang-Shen Fu; Cheng-Shuang Yin; Meng-Cheng Long (Computers and Geotechnics, 2026)

Dual-driven interfacial synthesis of PB/PmPD mixed matrix membranes via soft spraying for water treatment - Xiaotong Lu; Xiaojiao Hou; Peining Han; Yuhang Li; Zhicheng Pan; Tieqiang Wang; Fanbao Meng; Yu Fu (Chemical Engineering Journal, 2026)

Enhancing low-temperature NH3-SCR performance with hollow structure Cu/SAPO-34 catalysts - Xuejie Sui; Zhaoke Meng; Zehui Ma; Weiwei Zheng; Jingrui Yuan; Xuchao Geng; Fei Wang; Yuchao Lyu; Jianye Fu; Lishuang Ma; Xinmei Liu (Chemical Engineering Journal, 2026)

Temporal evolution of nocturnal thermal comfort for healthcare workers based on field evidence - Xin Wu; Yu Fu; Weijie Xia; Shilong Yuan; Meng Zhen; Fan Xu; Jing Li (Building and Environment, 2026)

Fat on Fire: Disrupted Microglial Lipid Metabolism as a Driver of Anesthetic Neurotoxicity - Yu-Jie Mou; Hai-Yue Tu; Yi-Chan Wang; Shao-Yong Song; Hua-Yue Liu; Dong Wang; Jun-Chao Wu; Xiao-Wen Meng; Zheng-Hong Qin; Fu-Hai Ji (Neuroscience Bulletin, 2026)

Refractory Dermatophytosis Caused by Trichophyton indotineae: A Case Series Highlighting Antifungal Resistance and Management Challenges - Yubo Ma; Rong Yan; Yakun Shao; Chunying Xiao; Tianshuo Zhao; Xingyu Li; Gang Wang; Chunying Li; Yinggai Song; Meng Fu; Yanyang Guo (Mycopathologia, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

Failure characteristics and development mechanism of time-delayed rockburst in a tunnel excavated via the drilling and blasting method: A case study - Lei Hu; Wen-Fei Chang; Ben-Guo He; Wei Zhang; Jun Zhao; Zhi-Bin Yao; Meng-Fei Jiang; Hong-Pu Li; Lian-Jie Fu (Tunnelling and Underground Space Technology, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Identification and knockout of SlHDZIV14 reveals fruit trichome-associated control of postharvest water loss in tomato - Ying Fu; Meng Li; Li Huang; Iben Sørensen; Xueting Liu; Chenhuan Fei; Wenran Song; Sen Zhang; Wei Zhang; Kexuan Tang; Jocelyn K.C. Rose; Qian Shen (Postharvest Biology and Technology, 2026)

Microbial adaptation and environmental co-selection drive antimicrobial resistance risk in agricultural ditches, evidence from the multilevel ditch-river continuum - Xiangyao Wu; Yulin Qi; Lingchen Meng; Keyan Li; Chao Ma; Dietrich A. Volmer; Chunmei Chen; Peizhe Sun; Pingqing Fu; Zhifeng Yan (Journal of Hazardous Materials, 2026)

Dependencies of ecological drought on climatic drivers in diverse ecosystems: Implications for water resources management - Zhiwen You; Leying Fu; Huaiwei Sun; Xuan Ban; Yubo Li; Pengsheng Li; Qiming Zheng; Changqing Meng; Jie Xue; Hui Qin (Journal of Environmental Management, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Systematic profiling of aroma and quality in UV-B treated grapes across fruit development stages - Lu Bian; Xiaoqiao Zhou; Jie Wang; Jiahao Fu; Xiaoxuan Jia; Yifei Zhang; Zhixin Zhang; Hamza Ali; Yanchun Fan; Xinyi Hao; Jiangfei Meng; Yan Xu; et al. (Food Research International, 2026)

Cannabidiol alleviates D-galactose-induced muscle tissue aging in mice by modulating oxidative stress and is associated with alterations in gut microbiota - RuiXue Lv; Song Liu; Lili Liu; Li Yang; Meng Zhang; Shuai Li; Tianfei Yu; Ming Zhao; Xuepeng Fu; WeiWei Zhang (Food Bioscience, 2026)

Thermo-mechanically coupled damage constitutive model and cross-scale fracturing mechanisms in argillaceous sandstone - Jie Fu; Wensong Xu; Guangming Zhao; Yian Chen; Xiangrui Meng (Bulletin of Engineering Geology and the Environment, 2026)

Visualization on deformation characteristics of passive soil arching effect in unsaturated compacted clay under plane-strain condition - Xiao-Hu Zhang; Han-Lin Wang; Meng-Cheng Long; Zhen-Nan Tian; Xiang-Shen Fu; Cheng-Shuang Yin (Bulletin of Engineering Geology and the Environment, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Selective oxidation of aqueous ammonium to nitrogen by photocatalytic optical fibers modified with Z-scheme Ag3PO4/MnO2 composites - Jiarun Meng; Yijun Wu; Heyun Fu; Shourong Zheng; Yi Tan; Xiaolei Qu (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Degradation of bisphenol A using a three-dimensional electrochemical reactor: Synergistic effects of H2O2 and mechanistic insights - Xu Ren; Lin Chen; Haifeng Fu; Meng Shen; Kai Song; Qiang Ma; Xin Peng (Process Safety and Environmental Protection, 2026)

Genome-wide analysis of the papaya bZIP gene family identifies CpbZIP52 as a key regulator of fruit postharvest ripening - Meiling Ding; Shanni Cao; Meng Zeng; Min Zhang; Hongya Tang; Xiaochun Chen; Xianqi Fu; Sicheng Bai; Min Yang; Kaidong Liu (Plant Science, 2026)

Multi-Sea-State Joint Frequency-Domain Identification of hydrodynamic parameters for float-over vessels - Rongze Wang; Meng Yuan; Mingyuan Sun; Liancai Cai; Yutu Ye; Xu Song; Shaohong Fu; Xin Li; Xinliang Tian (Ocean Engineering, 2026)

A coordinated control framework for maneuvering and power management in autonomous all-electric ships - Tiewei Song; Lijun Fu; Linlin Zhong; Yaxiang Fan; Meng Zhang (Ocean Engineering, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Source apportionment and health risk prioritization of groundwater contamination in a coal-mining area: An integrated SOM-PMF-Monte Carlo framework - Zheng Yin; Shiqi Zhang; Xiao Fu; Ran Sun; Ran Lv; Meng Yuan; Ziyuan Gao; Gang Wu (Journal of Environmental Management, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

Spatial–spectral feature guidance network for fine-grained object detection and recognition on complex-valued SAR images - Yuxi Suo; Youming Wu; Wenhui Diao; Qingbiao Meng; Xian Sun; Kun Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Revealing the activation mechanism of periodate by groundwater treatment plant waste iron-containing sludge for sulfadiazine removal: the key activation role of transition metal Mn - Yong Chen; Huiping Zeng; Jiaxin Xu; Sibo Fu; Yuliang Zhu; Fanxu Zeng; Luyao Teng; Jiahao Wu; Fanhao Meng; Dong Li; Jie Zhang (Environmental Research, 2026)

Self-sustaining singlet oxygen Fenton-like catalysis for scalable water remediation - Fu-Qiao Yang; Chang-Wei Bai; Jing Wang; Xin-Jia Chen; Pi-Jun Duan; Zhi-Quan Zhang; Ying Shao; Meng Zhang; Fei Chen (Chemical Engineering Journal, 2026)

Targeted lithium extraction from spent nickel-rich cathodes driven by a hydrogen-induced interfacial “push-pull” mechanism - DeHao Fu; Shan Jin; ChaoHui Chen; YingXiang Zhong; HaoFeng Tan; JunXia Meng; QuanXin Ma (Chemical Engineering Journal, 2026)

Association of plasma n-3 polyunsaturated fatty acid with gut mycobiome and implications for glucose homeostasis - Congmei Xiao; Yue Xi; Xinyu Wang; Chang Gao; Ruiqi Shi; Zelei Miao; Yuhui Liang; Wanglong Gou; Ke Zhang; Chun Wang; Xinxiu Liang; Meng Ye; et al. (Science China Life Sciences, 2026)

Effects of different photoperiods on growth performance and body coloration of largemouth bass (Micropterus salmoides) in recirculating aquaculture system - Jiahao Wei; Yiying Fu; Lenan Wang; Zhicheng Pan; Huifen Liu; Xiao Ma; Xi Shi; Xue Tian; Xiaolin Meng (Aquacultural Engineering, 2026)

Novel microfluidic gelatin-paper-based chip for sensitive colorimetric detection of urine albumin - Chien-Hsuan Ko; Chin-Chung Tseng; Hsing-Meng Wang; Chia-Chun Lee; Cheng-Xue Yu; Lung-Ming Fu (Analytica Chimica Acta, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Vincristine induces sperm malformation and motility dysfunction in mice by downregulating Tssk4 and Ccdc159 - Chaoming Zhou; Suyun Chen; Meng Fu; Yahui Hu; Hua Cao; Xu Cui (Reproductive Toxicology, 2026)

Iridal-type triterpenoids and stilbenes with anti-inflammatory activities from the rhizomes of Iris domestica - Kai-Dong Liu; Jiao-Jiao Zhou; Jiang Fu; Teng-Teng Meng; Jing Qu (Phytochemistry, 2026)

Imbalance of the AKT/MAPK signaling axis mediates the exacerbation of Alzheimer's disease pathology by simulated particulate air pollution from Shihezi in APP/PS1 mice - Xuening Li; Linglong Meng; Qiang Niu; Runjiang Ma; Yuhan Li; Hailing Zhou; Xiaoya Fu; Wenjie Chen; Juan Tang; Shangzhi Xu (NeuroToxicology, 2026)

Natural and anthropogenic controls on rare earth elements in groundwater: Indicative significance for distinguishing agricultural and urban-industrial impacts - Hang Meng; Guangcai Wang; Fu Liao; Hairu Mao; Bo Li; Fengxia Liu; Xianglong Chen; Hongyu Zhang; Zhiyuan Qiao (Journal of Hazardous Materials, 2026)

Establishing PdHg dual-atom sites on defective nitrogen-doped framework activated carbon for effective electrochemical CO2 reduction - Yanlong Gong; Fanfang Meng; Xiaoli Ran; Shixian Xiong; Jiangcheng Li; Xiaohong Yang; Haitao Fu; Xizhong An (Fuel, 2026)

Integrating ZSM-5 catalyst with controllable crystal size on macroporous biomass platform for benzene methylation with CO2/H2 - Weichao Qin; Caiyan Li; Tingjun Fu; Ruiwen Cao; Xueqing Wu; Yuyu Liu; Fanhui Meng; Guowu Zhan; Zhong Li (Fuel, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Source-oriented probabilistic human health risk assessments and priority heavy metal pollution control areas identification in the Laoguan river basin - Xinxin Long; Changyv Zhou; Hui Fu; Shaokang Meng; Yuan Wei (Environmental Pollution, 2026)

High-concentration polyethylene and polystyrene microplastics co-exposure shorten insect lifespan and impose ecological risk: Multi-omics evidence from Drosophila melanogaster - Yingyu Liu; Cheng Wang; Caixia Wang; Longhuan Fu; Yunbo Zhang; Zhuo Gao; Zhugen Yang; Fanyu Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Calcium selenide as a sacrificial electron donor boosting iron redox cycling for organic pollutant removal via transformation into elemental selenium - Haigang Fu; Shuang Meng; Jingyu Nie; Xinyun Zhang; Zihao Zhang; Yongjian Wang; Jing Zhang; Chuanshu He; Peng Zhou; Bo Lai (Chemical Engineering Journal, 2026)

Enhanced acetate tolerance and resource recovery via adaptive evolution of Chlorella vulgaris for sustainable upcycling of organic wastewater - Weizhao Meng; Enhui Liu; Jiahao Ma; Yixi Su; Jingyan Hu; Xiaomin Liang; Weiqi Fu (Bioresource Technology, 2026)

Variations of equivalent surface albedo and its influence on the photolysis rates of NO2 in a typical urbanized area of Shanghai - Yusen Duan; Kun Zhang; Qian Wang; Linhong Xiao; Yu Xiao; Juntao Huo; Zongjiang Gao; Chen Meng; Fan Yang; Qingyan Fu; Guangli Xiu (Atmospheric Environment, 2026)

A win–win strategy for balancing yield and CO2 emissions via shifts from r- to K-strategists in a mulched bamboo plantation - Tingting Cao; Quan Li; Meng Lei; Jiahui Zeng; Jiarui Fu; Simin Wang; Man Shi; Zhikang Wang; Xinzhang Song (Applied Soil Ecology, 2026)

Non‐Correlated Variation of Leaf and Fine Root Traits in Subtropical Forest Plants - Yuzhi Zhu; Meng Li; Junyong Zheng; Yongqiang Wang; Yanghang Ren; Han Zhang; Zeyu Feng; Sandy P. Harrison; I. Colin Prentice; Yue Zhang; Lewei Jin; Shuang Sun; et al. (Ecology Letters, 2026)
Plants employ multiple strategies to adapt to their growth environment. Characterizing key dimensions in plant trait space is important for understanding functional diversity within ecosystems. Leaf and root functional traits have been studied in the context of resource economics, but whether they covary, and through which mechanisms, is still debated. We investigated this in subtropical forests by sampling root and leaf traits on individuals of co‐existing species in two communities with different resource availability. We found largely non‐correlated variation between leaf and fine root traits both across and within communities, and a clear decoupling between leaf economic spectrum and root economic space, independent of evolutionary history. Our results suggest that leaf‐root trait relationships are shaped by an interplay between microenvironmental heterogeneity that drives decoupling and shared selection pressures promoting covariation. The interplay explains the weak observed coordination and highlights the importance of environmental context in predicting above‐ and below‐ground plant functions.

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Spatiotemporal variation of net anthropogenic phosphorus input and its delayed effect on lake phosphorus in a plateau lake of southwestern China - Huanyao Liu; Cen Meng; Shuaibing Wang; Yuyuan Li; Hui Fu; Wei Ouyang (Journal of Hydrology, 2026)

Synergistic enhancement of electrochemical performances via PDA/Fe3O4 modified anodes and amino acid-mediated bioelectrocatalysis of biomineralization in marine sediment microbial fuel cells - Lin-Meng Wang; Li-Ze Huangfu; Yi Yang; Yan Chen; Yu-Bin Fu (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Improving the flavor of black tea with treatment of cherry blossom and tannase: based on molecular sensory science and chemometrics - Xin Meng; Yijun Wang; Lianyao Cai; Huan Sun; Yiran Song; Wei Tao; Ying Gao; Chaohong Fu; Yong-quan Xu (Food Research International, 2026)

Mechanical summer pruning of ‘Syrah’ grapes in arid and semi-arid regions: the impact of canopy thickness on grapes and wine phenolic compounds - Lu Bian; Xince Yu; Zhixin Zhang; Yi Tong; Liang Zhang; Qian Xu; Jiahao Fu; Qiqi Wang; Wen Zhao; Jie Wang; Hongmei Chen; Jiangfei Meng; et al. (Food Chemistry, 2026)

A comprehensive review on wine authentication and traceability: Current issues, solutions and future perspectives - Hai-Qing Qiang; Hui-Wen Gu; Xiao-Li Yin; Zhan Meng; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Novel dual-phase porous Mn2O3/(Co,Mn)(Co,Mn)2O4 composite cathode material with enhanced interfacial stability for ultra-long cycle life in zinc ion batteries - Haoran Wang; Zhaoxia Hou; Hui Zhang; Wensheng Zong; Shuting Yin; Haibo Long; Zhongchao Fu; Nan Wu; Zihui Zhai; Depeng Zhang; Fanshun Meng; Dan Zhou (Chemical Engineering Journal, 2026)

Design and synthesis of novel fucosylated chondroitin sulfate derivatives as intrinsic FXase inhibitors and evaluation of their antithrombotic activities - Dongliang Xu; Xi Gong; Lisha Lin; Hang Dong; Yijian Wen; Yingnian Li; Gang Fu; Yuanhang Ma; Weicheng Xiong; Tianyu Guan; Ao Sun; Xiangbao Meng; et al. (Carbohydrate Polymers, 2026)

Deciphering acetate stress responses in methanogen using D2O-Labeled Single-Cell Raman spectroscopy - Min Li; Xiuxia Meng; Erqi Nie; Dongxue Lu; Rongbo Guo; Shanfei Fu; Jianhua Guo (Bioresource Technology, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Differential microbial communities and metabolite profiles in the rhizosphere and bulk soils of rubber tree (Hevea brasiliensis) infected with red root rot disease - Xiangjia Meng; Haibin Cai; Yongwei Fu; Keyu Bai; Lifang Zou; Cuicui Wang; Yi Zhou; Min Tu (Plant and Soil, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Quantitative scattering analysis of rough surface based on the boundary scattering matrix - Yang-pu Chen; Li-Yun Fu; Qing-qing Li; Hong-en Li; Qing-he Meng (Applied Geophysics, 2026)

RCDA-Net: a residual contextual dual attention network for wildfire spread region prediction - Xiaoxuan Huang; Qingxiang Meng; Jianhong Fu; Qin Zou (International Journal of Remote Sensing, 2026)

Organic material application holds great potential for alleviating soil nitrogen loss from cropland caused by shallow groundwater table fluctuations but increases N2O emissions - Rongyang Cui; Meng Qi; Bin Fu; Xinmei Zhao; Hui Yan; Zhiwu Li; Wanli Hu; Anqiang Chen (Water Research, 2026)

Dynamic frame rate recognition for vision-based deployment and recovery of USVs - Shengxuan Meng; Minlong Fu; Changbin Wang; Xiaonan Li; Dalei Song; Qianli Jiang (Ocean Engineering, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

UAV-based aboveground biomass estimation via trait-mediated pathways in a cultivated Leymus chinensis grassland - Lidong Cao; Yu Fu; Tianhang Zhao; Dekun Meng; Xiaoting Pan; Wei Sun (Journal of Environmental Management, 2026)

Consequence of microwave pretreatment on the fibrillization mechanism of whey protein: Aggregation kinetics, structural characterization, hypoglycemic and antioxidant activities - Yifei Meng; Xin Wen; Han Wang; Zhanmei Jiang; Hongyan Fu (Food Hydrocolloids, 2026)

Long-term evidence that controlled-release urea enhances yield and soil fertility while mitigating environmental impacts in double-season rice - Yifan Fu; Wei Yang; Meng Zhang; Xiangning Wu; Guodong Yang; Hongshun Xiang; Chanchan Du; Jinjuan Zhu; Chen Yang; Yunfan Wan; Shaobing Peng; Yu’e Li; et al. (Field Crops Research, 2026)

MOF-derived AgCl/ZnO heterojunction photocatalysts: Enhanced degradation of tetracycline via promoted charge carrier separation - Kailai Zhang; Ao Feng; Chuwen Ou; Qinwu Wu; Zhen Meng; Hang Chen; Shurui Xu; Xiaobo Fu; Wenbo Liao; Baizeng Fang; Guoyu Zhong (Environmental Research, 2026)

Breaking the vicious cycle in urethral repair: A Janus hydrogel scaffold with integrated active regulation and passive protection - Yangwang Jin; Fei Qin; Wenzhuo Fang; Meng Liu; Qiang Fu; Ming Yang; Jianguo Ma; Ranxing Yang (Chemical Engineering Journal, 2026)

Modulating d-band center to construct Ptδ–Cuδ+ pairs for selective hydrogenation of renewable furfural - Liangmin Ning; Shuai Li; Shiyan Sheng; Jiuheng Ma; Jiawen Wang; Tianyu Zhang; Shun Wang; Jingyi Han; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Gut microbiota-cognitive function interactions in patients with comorbid insomnia and sleep apnea (COMISA): a study on brain dynamic specificity - Huiyu Chen; Hui Li; Jiawei Guo; Liping Pan; Shishun Fu; Guihua Jiang; Meng Li (Brain Imaging and Behavior, 2026)

Antifouling compounds from marine fungus Aspergillus iizukae GXIMD 00548 - Chun-Qing Fu; Meng-Fan Qi; Chun-Xiao Chen; Hua-Qing Huang; Xiao-Wei Luo; Cheng-Hai Gao; Yong-Hong Liu; Xin-Ya Xu (Biofouling, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Golden coloration of Ginkgo biloba can be driven by fine-tuning of pigment, flavonoid, and terpene metabolism - Yibin Lu; Guolin Wang; Dong Yang; Cuiping Zhang; Guo He; Xiao Zhou; Yu Liu; Weiqi Li; Chunxiang Fu; Mengzhu Lu; Gongke Zhou; Jie Meng (Journal of Plant Physiology, 2026)

Impacts of the mega cascade reservoirs on riverine hydrothermal regimes based on deep learning - Meixiu Yu; Jinjie Guan; Jianyun Zhang; Junliang Jin; Qingshe Meng; Hanlin Song; Zixuan Xu; Xiaolong Liu; Jiayi He; Ting Fu (Journal of Hydrology, 2026)

A hydrolase with synergistic dual-cavity remodeling for high-efficiency degradation of PET waste - Qisheng Fu; Zhisheng Wei; Zewei Zhang; Lingqia Su; Zhengfei Yan; Meng Xu; Sunan Zhu; Guiyuan Zheng; Demin Kong; Shiheng Chen; Xiaoya Chen; Canzhao Li; et al. (Journal of Hazardous Materials, 2026)

Ammonia-hydrogen blends combustion in turbulent high temperature co-flow - Meng Ji; Zhijun Wu; Oscar Vento; Quanbo Shang; Chaoqun Hu; Alessandro Ferrari; Lezhong Fu; Jun Deng; Liguang Li (Fuel, 2026)

Bioinspired iron porphyrin covalent organic framework nanozyme with peroxidase-like activity for ratiometric colorimetric and portable swab-assisted detection of nitrite in food samples - Jin Liu; Qiuyu Chen; Xiaoyan Meng; Cong Hu; Fengfu Fu; Zian Lin (Food Chemistry, 2026)

Occurrence, drivers, and risk assessment of non-antibiotic pharmaceuticals in urban sewer systems - Fan Meng; Shaojing Sun; Jialu Cheng; Ziyi Wang; Changshun Wang; Jinpan Jiang; Lu Lu; Jingchao Li; Yajie Tian; Lixin Ma; Bo Li; Xiaoyu Feng; et al. (Environmental Pollution, 2026)

Impact of carboxymethyl cellulose on the gelation and digestive characteristics of myofibrillar protein and its application for encapsulation of puerarin - Qiao-bo Zhang; Shi-Meng Liang; Yan-wei Yuan; Xue-xing Yin; Jing-jing Fu; Yue-wen Chen; Wen-qiang Cai (Carbohydrate Polymers, 2026)

Tracing fertilizer transformation and leaching in karst soils via soil column experiments and nitrogen isotopes - Ping Zhang; Yi-Meng Ren; Xiao-Dan Wang; Fu-Jun Yue (CATENA, 2026)

A synthetic biocontrol consortium of Streptomyces salinarius and Bacillus halotolerans exhibits superior protection against Fusarium oxysporum infection in Pinus via synergistic interactions - Haixia Wang; Lin Fu; Chunli Li; Xuanyi Meng; Siyang Wang; Xinlu Zhang; Xinyu Zhou; Xiangna Wang; Fangliang Zheng; Chunyu Zhu (Plant and Soil, 2026)

Risk factors for Poor Response to Itraconazole in Onychomycosis Patients: A Prospective, Observational Study in China - Chang Miao; Yubo Ma; Xingyu Li; Tianshuo Zhao; Haijun Miao; Dong Yan; Luming Hai; Gang Wang; Yanyang Guo; Meng Fu (Mycopathologia, 2026)

Low-dose chlorine disinfection poses a greater potential risk of antibiotic resistance genes and their pathogenic hosts - Qiyue Meng; Jia Wang; Kun Li; Yibo Zhang; Ziyu Hu; Feng Wang; Fei Pan; Jie Fu; Chenyuan Dang (Water Research, 2026)

Catalytic ozonation of cyanide in gold leaching efluent by EDTA-Coir/copper slag: Efficacy and mechanisms - Wanzhen Zhong; Gang Meng; Jiacheng Cui; Xinshenghui Zhu; Siyi Luo; Weiqiang Tan; Zongliang Zuo; Weizhang Fu; Dongdong Ren (Process Safety and Environmental Protection, 2026)

Carbon isotope stratigraphy of the Doushantuo Formation in basinal facies of South China: Constraints on the Shuram excursion in a deep ocean environment - Rui Fu; Chaochao Xing; Lei Zhang; Meng Ning; Fangbing Li; Xianguo Lang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Monoculm1 confers cold tolerance at the seedling stage in rice - Ruiqing Li; Chenfan Zheng; Binqiang Wang; Shang Dai; Yue Song; Huali Zhang; Zhiguo E; Bo Liu; Jiale Chen; Can Zhang; Haowei Fu; Ning Xu; et al. (Molecular Plant, 2026)

On-demand thermal regulation and water harvesting via liquid metal-infused bio-inspired microchannel architectures - Chenfei Zhou; Yuanbo Sun; Yu Cheng; Chenyang Cai; Meng Zhang; Wang Zhang; Yu Fu (Journal of Cleaner Production, 2026)

Electrochemical aptasensor based on Zr-MOF@Ag nanocomposite for the rapid detection of chloramphenicol in honey, milk and lake water - Zhaoyuan He; Chengxiang Fu; Shuling Meng; Jiaqi Luo; Jieke Qiu; Jianing Huang; Xiaoge Duan; Jiakang He; Jinzi Wang; Hailan Chen (Food Chemistry, 2026)

Fabrication of Prussian blue mixed matrix membranes based on the synchronous growth for water treatment - Xiaotong Lu; Xing Gao; Xiaojiao Hou; Bingbing Chen; Peining Han; Tieqiang Wang; Fanbao Meng; Yu Fu (Chemical Engineering Journal, 2026)

Iono non-hydrothermal (INH) method for synthesis of highly ordered mesoporous silica materials - Hosein Ghaedi; Jiawen Fu; Xin Meng; Yang Liu; Yeshui Zhang; Shakil Ahmed Jiskani; Abdul Raheem; Ming Zhao; Paul S. Fennell; Edward J. Anthony (Chemical Engineering Journal, 2026)

Anammox community characteristics and stable relationships centered on anammox bacteria - Yi-Cheng Wang; Hui-Min Fu; Hong-Yuan Liu; Han Wu; Zi-Han Zeng; Jian-Hong He; Meng-Jiao Gao; Peng Yan; Liang Zhang; You-Peng Chen (Chemical Engineering Journal, 2026)

Atomically dispersed Pd on WO3/WS2 nanoflowers for fast hydrogen detection - Jingyun Li; Fanfang Meng; Mei Zhu; Hao Lv; Yanlong Gong; Xiaohong Yang; Jiangcheng Li; Shixian Xiong; Haitao Fu; Xizhong An (Chemical Engineering Journal, 2026)

Hydrophobic association-reinforced polymerizable deep eutectic ionic gels for next-generation wearable electronics: Multilevel dynamic network construction and multifunctional integration - Qiuyan Luo; Jia Jiang; Yuhang Lin; Hucheng Fu; Zewen Wu; Meng Wang; Yiting Xu; Xinyu Liu; Birong Zeng; Lizong Dai (Chemical Engineering Journal, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Removal of Mo(VI) by Iron-Modified Biochar Based on a Bilayer Permeable Reactive Barrier - Mengru Li; Meng Tan; Sujing Fu; Peng Liu; Kunpeng Zhou (Water, Air, & Soil Pollution, 2026)

Traditional Chinese medicine and natural small molecules for pain treatment via voltage-gated sodium channels: a review - Zhen Zhang; Fu-Yu Xie; Yue Zhang; Meng-Xia Wu; John N. Wood; Chao-Mei Fu; Ahmed M. M. Mahmoud (Phytochemistry Reviews, 2026)

Research on Risk Evaluation of Tunnel Water Inrush Based on Multi-source Geophysical Exploration Data Fusion of MLP-Transformer Model - Guang Huo; Huai-bing Wang; Jin-gang Zhang; Yi-guo Xue; Bo-yin Fu; Fan-meng Kong; Zongwei Yan (Applied Geophysics, 2025)

Numerical investigation of dynamic response in HDPE floating raft array for aquaculture: Coupled system analysis and sea trial evidence - Fei Fu; Zhe Hu; Xiaoying Zhang; Zhanbin Meng; Jianxing Yu (Ocean Engineering, 2025)

Donor-acceptor structured boron-doped g-C3N4 photocatalysts for enhanced tetracycline degradation and H2O2 production - Xiangdong Chen; Meng Wang; Zhonghui Fu; Yiping Deng (Journal of Cleaner Production, 2025)

The embodied agricultural NH3 emissions in China's inter-provincial trade and the implied environmental inequities - Lu Lu; Zebin Zhao; Jinpan Jiang; Fan Meng; Ziyi Wang; Changshun Wang; Jingchao Li; Hong Qi; Donglei Fu (Journal of Cleaner Production, 2025)

New insights into the distribution and risk of antibiotics: From point to non-point source in a rapidly urbanizing watershed — A case study of the Wenyu River, Beijing - Lei Chen; Xinyi Meng; Xuehui Zhou; Jingyu Wang; Yijia Fu; Shuai Wang; Yukun Ma; Zhenyao Shen (Journal of Cleaner Production, 2025)

Machine learning-based prediction of PAHs thermal desorption efficiency: Model optimization, boundary correction, and mechanistic insights - Pengcheng Fu; Meng Qi; Chunshuang Liu; Cheng Zhang; Yuhao Zhao; Zhibao Liu; Hao Wang; Dongfeng Zhao (Journal of Environmental Management, 2025)

Simultaneous quantification of fructose and sucrose in beverages using microfluidic paper chip and colorimetric pixel-area analysis method - Chan-Chiung Liu; To-Lin Chen; Hsing-Meng Wang; Kuan-Hsun Huang; Lung-Ming Fu (Food Chemistry, 2025)

High entropy metal organic framework nanozyme with cocktail effect for efficient extraction and colorimetric detection of tetracycline in food and water environment - Lupeng Dou; Sitong Huang; Zhimei Huang; Zhen Liu; Ke Xiao; Leixia Meng; Yamin Fu (Food Chemistry, 2025)

Atmospheric microplastic emissions from organic waste composting: Field-based assessment and exposure implications - JiaJia Zhang; ChenLu Fu; GuoYuan Zou; Meng Zhao; Meng Mao; YanHua Chen (Environmental Research, 2025)

Nucleoside-modified mRNA-engineered myogenic-induced stem cell sheet propels urethral sphincter rejuvenation and reverses stress urinary incontinence - Meng Liu; Yuhui Wang; Ranxing Yang; Kaile Zhang; Ming Yang; Wenzhuo Fang; Yangwang Jin; Wei Fu; Ying Wang; Qiang Fu (Chemical Engineering Journal, 2025)

Low-molecular-weight dextran sulfate sodium as novel heparanase inhibitor preventing breast cancer metastasis in mice by inhibiting migration and angiogenesis - Yidian Mo; Guohao Song; Linbo Fu; Yuchao Wang; Tongtong Geng; Ao Sun; Baodi Gou; Xiangbao Meng; Liangren Zhang; Heng Wang; Zhongjun Li; Zhongtang Li (Carbohydrate Polymers, 2025)

Spatial heterogeneity in biomass yield and quality driving regional strategies for enhanced rice straw bioeconomic potential: a case study in Hunan, China - Congyu He; Zhiwei Li; Yi Xu; Meng Li; Tongcheng Fu; Zili Yi; Shuai Xue (Bioresource Technology, 2025)

Transcriptome and physiological analysis revealed core genes that promote glutathione metabolism in blue honeysuckle in response to freezing stress - Yuxin Fan; Dandan Zang; Tianyi Wang; Zhihua Song; Na Li; Hongyan Cao; Tingting Du; Meng Qi; Yujie Fu; Qing Yang; Biying Dong; Dong Meng (Tree Genetics & Genomes, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Genome-wide association studies in forestry - Xiangrun Meng; Yinyin Fu; Yanran Qi; Zhuoying Jin; Peng Li; Yalin Sang (Molecular Biology Reports, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

The whole genome sequence of Cordyceps cicadae — an edible and potential medicinal fungus - Yuwei Liu; Xueqian Li; Yiqi Meng; Yifan Wu; Yuting Jin; Xiaotong Ma; Wei Zhou; Yuchong Tan; Fu-Cheng Lin; Hongkai Wang (Molecular Genetics and Genomics, 2025)

Quantitative estimation of the spatiotemporal responses of PM2.5 and O3 synergistic pollution to precursors in the Chengdu-Chongqing City Group of China - Mingliang Ma; Yihong Jiao; Mengjiao Liu; Mengnan Liu; Fei Meng; Huaqiao Xing; Jingxue Bi; Yuqiang Wang; Tongwen Liu; Pingjie Fu (Air Quality, Atmosphere & Health, 2025)

Sample Size and Optimal Timing for Urine Collection Based on Diurnal Variability of Urinary Iodine/Creatinine Ratio in Pregnant Women - Qi Meng; Min Fu; Rui Yang; Fei Li; Junjing Li; Meina Ji; Qi Jin; Mengxin Liu; Hexi Zhang; Wenxing Guo; Wanqi Zhang (Biological Trace Element Research, 2025)

Depth-dependent velocity changes in the 2018 Kilauea eruption: insights into magma behavior - Cong Zhou; Lei Fu; Xiangzhi Zeng; Meng Zhang; Pei Zhang; Kexu Shi; Lingyun Ji; Qingliang Wang (Bulletin of Volcanology, 2025)

Dexmedetomidine alleviates ferroptosis caused by traumatic brain injury via the NRF2/HO-1/GPX4 pathway - Jin-Jing Hao; Xue-lian Fang; Yi-Yang Chen; Zi-jun Meng; Fu-xing Dong; Xiao-fang Yang; Zheng Chu; Jin-xia Kuai; Haijun Bao (Metabolic Brain Disease, 2025)

Applying natural product repurposing strategy to identify baicalein as novel caseinolytic protease P inhibitor and its application in the treatment of rice bacterial diseases - Zhaoju Sun; Teng Yang; Zhouqing Long; Xichun Fu; Jiao Meng; Xiang Zhou; Cai-Guang Yang; Song Yang (Pesticide Biochemistry and Physiology, 2025)

ARR1/12-ETP1/2 model negatively regulates submergence-induced hypoxia response in A. thaliana - Meng Liu; Xuerui Li; Zeyu Cheng; Yuhang Wu; Wensen Fu; Yongqi Hu; Jin Yan; Songfeng He; Wenli Chang; Ruijia Zhang; Yingying Qian; Jianquan Liu; et al. (Journal of Plant Physiology, 2025)

Explore the relationship between Bowen ratio and evapotranspiration in wetlands using the maximum entropy production model - Huaiwei Sun; Leying Fu; Weiguang Wang; Jie Xue; Jing Wang; Weihong Liao; Haicheng Li; Xunlai Sun; Yong Yang; Jingfeng Wang; Hong Zhang; Fulong Chen; et al. (Journal of Hydrology, 2025)

Resorcinol-formaldehyde resin as co-catalyst in Fenton-like reaction: Synergistic enhancement of Fe3+/Fe2+ cycling via phenolic hydroxyl redox and conjugated-structure mediated electron transfer - Qingnan Meng; Rui Fu; Linzhi Huang; Zhangwen Xie; Yufei Tang; Kang Zhao (Journal of Cleaner Production, 2025)

Effect of desalination-related pH shift on whey protein structure and digestion: Insights from spectroscopy, molecular dynamics simulation, and peptidomics - Meng-Qi Liu; Yun Chen; Hong-Fu Zhao; Ying-Chao Qiu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Effects of fermentation by different strains on the Physico- chemical properties, quality, and metabolic profile of Rice noodles - Yuanyuan Ren; Yuhang Li; Rui He; Yingjie Lei; Yi Zhao; Zikuan Meng; Ding Ma; Jin Fu; Geng Zhong (Food Chemistry, 2025)

Identification of natural food-derived emulsifiers using QSAR and machine learning: Application in dairy emulsions - Meng-Qi Liu; Zai-Xi Zhou; Hong-Fu Zhao; Ying-Hua Zhang (Food Chemistry, 2025)

Evolution of immunoglobulin M (IgM) structure and function in vertebrates: A comprehensive review - Shun Yang; Lu-Chuan Zhao; Fu-Zhen Guo; Hong-Sen Xu; Meng-Meng Huang; Hui Fei (Fish & Shellfish Immunology, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Optimization of conductivity and stability on inverse spinel CoFe2O4 for alkaline oxygen evolution reaction - Fu-Yu Guo; Jian Luan; Xian-Chen Meng; Peng Zheng; Wen-Long Duan; Wen-Ze Li (Chemical Engineering Journal, 2025)

Associations of long-term exposure to ambient PM2.5 and its constituents with risk of incident hypertension in rural China - Donghui Yang; Xia Meng; Yun Chen; Xiaolian Dong; Haidong Kan; Chaowei Fu (Atmospheric Pollution Research, 2025)

Uptake of inorganic nitrogen between understory shrubs and replanted broadleaved trees in a subtropical plantation - Qianyuan Liu; Liang Kou; Shengwang Meng; Fengting Yang; Xiaoli Fu; Huimin Wang (Plant and Soil, 2025)

Research on rock breaking mechanism of laser-assisted TBM cutter based on continuous-discrete coupling method - Yukun Chen; Zhiqiang Huang; Kai Fu; Meng Yin; Long Li (Tunnelling and Underground Space Technology, 2025)

An integrated framework for assessing solar photovoltaic potential of building surfaces at city scale using parametric simulation and optimized machine learning models - Fuming Lei; Zengfeng Yan; Pingan Ni; Yingjun Yue; Shanshan Yao; Jingpeng Fu; Liuhui Meng; Guojin Qin (Sustainable Cities and Society, 2025)

Citizen preferences for supporting farmers in sustainable rural management: An analysis of five biogeographically differentiated European countries - Rao Fu; Meng Yue; Shan Jin; Lynn J. Frewer (Journal of Rural Studies, 2025)

Changes in the effectiveness of low impact development practices and their role in optimal design - Shuai Wang; Guowangchen Liu; Xiaoyue Zhang; Yiji Fu; Jingyu Wang; Xinyi Meng; Shenghan Gao; Yukun Ma; Zhenyao Shen; Lei Chen (Journal of Hydrology, 2025)

How does the coupled action of freeze-thaw and acidification affect the release of toxic elements from indigenous Zn smelting slags? - Damao Xu; Caihong Gao; Baihong An; Tianpeng Hu; Lai Zhou; Xueqiang Zhu; Qingjun Meng; Rongbing Fu (Journal of Environmental Sciences, 2025)

Oil-based micro-sized extraction system designed from O/W Pickering emulsion template for highly efficient nanoplastics removal in the gastrointestinal tract - Xiao Fu; Chi Zhang; Xiao Tong Lu; Fang Xiao Guo; Xu Zhang; Huixia Zhou; Xin-Ai Guo; Xiaoyu Wang; Ching Yuan Hu; Shuai Zhang; Yong Hong Meng (Food Hydrocolloids, 2025)

Fractal analysis of residential air conditioning energy consumption: Identifying usage patterns and temporal complexity - Chenghao Fu; Ziqiao Li; Longkang Dai; Zhilong Liu; Meng Liu (Energy and Buildings, 2025)

Spatio-temporal neural operator on complex geometries - Xiaoyang Fu; Gengxiang Chen; Yingguang Li; Xu Liu; Lu Chen; Qinglu Meng; Changqing Liu; Xiaozhong Hao (Computer Physics Communications, 2025)

Sponge-like PNIPAM/Fe3O4/PPy composite hydrogel actuator with rapid response, self-sensing and multiple manipulating manners for complex application scenarios - Xingchen Cui; Bing Zhang; Pingzhi Shao; Linlin Li; Shunsheng Ye; Fuqiang Fan; Yu Fu; Fanbao Meng; Tieqiang Wang (Chemical Engineering Journal, 2025)

Engineered IGF-1-expressing adipose-derived stem cell sheet fragments promote urethral sphincter tissue regeneration - Ying Wang; Guo Gao; Meng Liu; Ming Yang; Yuhui Wang; Wenzhuo Fang; Yangwang Jin; Wei Fu; Qiang Fu (Chemical Engineering Journal, 2025)

Concurrent incorporation of Fe doping and construction of Pd-O-Fe interface for Pd/CeO2 photo-assisted thermocatalytic NO reduction into ammonia - Aoqiang Li; Jianfei Li; Chaowei Liang; Xiangyu Meng; Xianzhi Fu; Wenxin Dai (Chemical Engineering Journal, 2025)

Selectively extracting lithium from single and mixed cathode materials - Zifei Meng; Jiahui Hou; Zexin Wang; Xiaotu Ma; Panya Thanwisai; Jinzhao Fu; Zeyi Yao; Wenting Jin; Hao Zhou; Zhenzhen Yang; Yan Wang (Chemical Engineering Journal, 2025)

Sunlight-driven hydrogen peroxide activation via copper hydroxyphosphate with broad spectrum response for imidacloprid degradation: Mechanism insight and DFT calculation - Haoran Zhang; Jiang Li; Yujiao Liu; Sihao Fu; Tianjie Su; Lingyu Meng; Yunfei Wang; Nian Ma; Guocheng Liu; Qinghua Yan; Yanjun Xin; Shuaishuai Xin (Chemical Engineering Journal, 2025)

Molecular epidemiology and phylogenetic analysis of Echinococcus spp. in the Qinghai-Tibetan Plateau: unraveling genetic evolution in a high-risk region for echinococcosis - Guoyan Zhou; Zhi Li; Xueyong Zhang; Ru Meng; Xiuying Shen; Zhen Zhang; Fuyun Chen; Hong Duo; Yong Fu (Veterinary Research Communications, 2025)

Formation and enrichment mechanisms of precious gas in sedimentary basins - Quanyou Liu; Yongbo Wei; Dongya Zhu; Xiaoqi Wu; Qingqiang Meng; Pengpeng Li; Yin Fu; Di Zhu; Wang Zhang; Zhijun Jin (Science China Earth Sciences, 2025)

Sublethal deltamethrin induces transgenerational fitness costs in Neoseiulus agrestis (Karg) (Acari: Phytoseiidae): impaired parental reproduction and offspring development - Jing Chang; Shu-Lei Zhang; Cheng Wang; Xiao-Tong Fu; Zhi-Jia Huo; Rui-Xia Meng (Experimental and Applied Acarology, 2025)

Exploring the Impact of Selenium Supplementation on Nutritional, Inflammatory, and Cardiac Function in Chronic Heart Failure Patients: A Novel Approach to Managing Deficiency - Ladi Kou; Fandong Meng; Guotao Fu; Rongqiang Zhang (Cardiovascular Toxicology, 2025)

What Controls the Distribution of Ore Veins in Quartz Vein-Type Tungsten Deposits: Constrains from Fan-Shaped Mineralization in SE China - Gui-Cong Fang; Deng-Hong Wang; Fu-Qiang Yang; Zhan-Xu Ni; Chang-Shuai Huang; Ping Wang; Meng Feng; Zuo-Hai Feng (Journal of Earth Science, 2025)

Impact of SNP Variants in PON-1 or UGT1A1 on Iron Chelation Therapy Outcomes and Zinc Status in Thalassemia Major Patients - Meng-Yao Lu; Wan-Fu Tsai; Chang-Shiann Wu; Chien-Sheng Wang; Nailis Syifa; Mong-Liang Lu; Jiahn-Haur Liao; Wei J. Chen; Kai-Hsin Lin; Tzu-Hua Wu (Biological Trace Element Research, 2025)

Regional airflow velocity control to meet the diverse requirements of unevenly distributed maize threshing mixtures - Meng Zhang; Chao Cheng; Jun Fu; Zhi Chen; Luquan Ren (Biosystems Engineering, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Overcoming microbial antagonism: strategic enhancements for dibenzofuran bioremediation - Yanan Wu; Changai Fu; Yan Chen; Xu Wang; Wenhui Zhao; Meng Chen; Li Li (Journal of Environmental Management, 2025)

Mechanisms of microbial inhibition of freeze-thaw hydraulic alternating erosion in cold black soil region: Reconstructing soil structure with indigenous bacteria - Tianxiao Li; Zhaoxing Xiao; Qiang Fu; Fanxiang Meng; Renjie Hou; Shunli Zheng; Mo Li; Dong Liu; Fanying Kong (Journal of Environmental Management, 2025)

The autoignition characteristics of oxygen-in-ammonia blending fuel turbulent jet flame into high temperature co-flow - Meng Ji; Zhijun Wu; Zhe Kang; Quanbo Shang; Guanyu Zhang; Chaoqun Hu; Lezhong Fu; Yang Yu; Jun Deng; Liguang Li (Fuel, 2025)

Design of protein-based carriers for curcumin with tailored particle properties: Stability and mechanistic insights - Wenting Huang; Zhiping Hong; Zhijie Fu; Chun Meng; Yuhong Mao (Food Chemistry, 2025)

Characterization of key aroma compounds in Maillard reaction products of Agrocybe aegerita enzymatic hydrolysates by GC×GC-O-MS - Hongyang Meng; Fan Yang; Shaobo Zhen; Anzhen Fu; Shuang Bi; Ye Liu (Food Bioscience, 2025)

Paeoniae Radix alba polysaccharide modulates gut microbiota to restore metabolites and promote the enteric nervous system development in colitis mice - Chao-Wen Zhang; Si-Zhe Shui; Shuang Liao; Yu-Chao Kuang; Dai-Zheng Yin; Yi Gu; Banaz Jalil; Michael Heinrich; Xing-Fu Chen; Zhong-Qiong Yin; Chun Wu; Xu Song; et al. (Food Bioscience, 2025)

Structural optimization of CdTe photovoltaic window based on climate adaptability - Sifan Huang; Meng Wang; Bin Zou; Shuhao Wang; Yin Xiong; Ganhua Fu; Qinghua Sun; Shuang Dou; Jinqing Peng (Energy and Buildings, 2025)

Triple-network conductive hydrogel with high strength and toughness for visual flexible strain sensor - Meng Meng; Renli Fu; Tiange Xue; Xingyu Liu; Jun Jiang; Xuhai Liu (Chemical Engineering Journal, 2025)

Ordered porous polylactic acid membrane as mask layer for high voltage aluminum anode foils electrolytic capacitors - Hongliang Fu; Hongliang Bao; Yue Lian; Zhengshan Qiao; Shuan Zhang; Xianfu Meng; Kunsong Ma; Deqiu Zhu; Jing Zhao; Huaihao Zhang (Chemical Engineering Journal, 2025)

An integrated machine learning-based indoor thermal health model using a multidimensional database of thermal environments, physiological, and psychological indices - Yingxian Zhai; Meng Liu; Chandra Sekhar; Kailai Sun; Wanting Xia; Qisheng Li; Chenghao Fu; Lumeng Liu; Huan Liu; Ziqiao Li (Building and Environment, 2025)

Nitrogen addition simplifies micro-food webs in leaf litter habitats at humus-near stage of decomposition in a subtropical plantation - Wei Fu; Chen Liang; Guofei Shang; Shengwang Meng; Tongchuan Li (Plant and Soil, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Asymmetric C2-functionalization of indoles via visible-light-promoted three-component reaction - Han-Peng Pan; Xiao-Ying Hu; Jun-Hui Luo; Zhao-Jie Fu; Xin-Yi Yao; Meng-Yan Ran; Fang-Xin Wang; Xiang-Zhi Zhang (Molecular Diversity, 2025)

Genomic selection for hard-to-measure traits in aquaculture: Challenges in balancing genetic gain and diversity - Ziyi Kang; Jie Kong; Qi Li; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Zhaoxin Wang; et al. (Aquaculture, 2025)

New perspectives on bacterial chlorine resistance: Phages encoding chlorine resistance genes improve bacterial adaptation - Jia Wang; Yibo Zhang; Qiyue Meng; Ziyu Hu; Jie Fu; Chenyuan Dang (Water Research, 2025)

Scandium and gallium in weathered basalts as unconventional resources - Mei-Fu Zhou; Wen Winston Zhao; Zhenchao Wang; Min Wang; Shengbiao Yang; Lei Meng; Liang Qi; Guangfu Xing; Xiang Li; Dai Zhou (Journal of Asian Earth Sciences, 2025)

The spoilage characteristics and key metabolites of Lactobacillus brevis and Lactobacillus plantarum in ready-to-eat chicken feet - Xin Jia; Peng Gao; Ailian Meng; Yi Fu; Hao Chen; Min Huang (Food Research International, 2025)

Preparation, identification and potential mechanism of novel urate-lowering active peptide from hemp protein: From animal model to computer simulation - Meng-Qi Liu; Hong-Fu Zhao; Zi-Ying Zhao; Ying-Hua Zhang; Yan Dong (Food Research International, 2025)

Hybrid DNA nanomaterial and three-directional hybridization chain reaction enable electrochemical diagnosing metastatic lymph nodes of breast cancer by one-step exosome sensing - Zhihao Zhang; Ronghao Hu; Di Fu; Weijing Liu; Jie Qu; Yue Wang; Xianghu Zeng; Xin Zhao; Xiangyue Meng; Binxu Qiu; Xin Jiang; Bofu Liu; et al. (Chemical Engineering Journal, 2025)

Nutrient enrichment weakens the positive feedback of soil organic carbon decomposition to short-term warming in subtropical forests - Ming-Hui Meng; Chao Liang; Jin He; Zi-Yi Shi; Fu-Sheng Chen; Fang-Chao Wang; Xue-Li Jiang; Xiang-Min Fang (Plant and Soil, 2025)

Research on the Influence of Hydrofoil Propulsive Parameters on Propulsion Efficiency - Meng Cui; Zhihao Liu; Fei Lu; Jiaye Gong; Zheng Fu (Journal of Marine Science and Engineering, 2025)
Oscillating hydrofoils can be used to simplify the study of the swinging caudal fin propulsive mode of fish, where the motion parameters have a direct impact on the hydrodynamic performance and propulsive efficiency. In this study, numerical calculations were carried out on two-dimensional hydrofoils for sinusoidal and non-sinusoidal heave oscillation, and the numerical results of sinusoidal hydrofoils were compared with the experimental values, which were in good agreement. An analysis of how different motion parameters of the sinusoidal hydrofoil affect the hydrodynamic performance was conducted, and the recommended operating condition range was given in combination with the flow field analysis. A unique non-sinusoidal curve was defined, which can enable the motion to enter the crest and trough earlier or later. The parameters for controlling the degree of non-sinusoidal were also defined. A detailed discussion was carried out on how the non-sinusoidal parameters affect the hydrodynamic performance and the change in the flow field. The corresponding recommended working conditions and application scope were given. Further studies can reveal the propulsive mechanism of the swinging caudal fin and provide a reference for the engineering and design of the next generation of bionic fish.

Quantitative analysis of anthocyanins and flavonoids in purple and green leaves of Eleutherococcus senticosus by UPLC-MS/MS techniques - Mei Hua; Meng Meng; Yu-pin Fu; Yun-qin Li (Natural Product Research, 2025)

Controlled synthesis of metal-based Janus nanostructures for tandem electrocatalytic carbon dioxide reduction - Yangbo Ma; Mingzheng Shao; Guozhi Wang; Liang Guo; Yunhao Wang; Fengkun Hao; Fu Liu; Xiang Meng; Chaohui Wang; Yuecheng Xiong; Zhanxi Fan (Science Bulletin, 2025)

Feature transfer projection with low-rank and dual graph embedding for multimode process monitoring - Xue Xu; Chaogang Yang; Xianglei Meng; Yuanjian Fu; Chaomin Luo; Chengyi Xia (Process Safety and Environmental Protection, 2025)

Performance and mechanism analysis of a novel conjunctival composite dust suppressant for metal mines - Zhian Huang; Keying Meng; Jiaze Ren; Rongxia Yu; Mingming Fu; Gaowen Wang; Yinghua Zhang; Hongsheng Wang; Jinyang Li; Ye Xu; Md Yasin; Asim Farooq (Process Safety and Environmental Protection, 2025)

Micro- and nanoplastics differ in particle-mucus interactions: The sight on rheological properties, barrier dysfunction and microbiota dysbiosis - Xuemei Meng; Xue Zheng; Wenting Mai; Jianying Gao; Yanli Fan; Jing Fu; Junnan Xu (Journal of Hazardous Materials, 2025)

Mass spectrometry-based lipidomics combined with flavoromics reveal the mechanism of characteristic flavor formation in Chelidonichthys kumu bone soup treated with different edible oils by frying - Zixi Li; Meng Dong; Libo Qi; Shan Shang; Yan Guo; Lei Qin; Baoshang Fu (Food Bioscience, 2025)

Mechanism of microparticulated whey protein replacing milk fat during the production stages of renneted casein gel - Ran Meng; Ran Feng; Runhao Fu; Zihan Wang; Bao Zhang (Food Hydrocolloids, 2025)

A hydrophobic cathode design towards high-stability Zn-air batteries: Coupling FeTAP molecules with self-supporting edge-rich graphene membrane - Jiachen Meng; Yulei Zhang; Xuemin Yin; Yanqin Fu; Dan Wen; Qiang Song; Hejun Li (Chemical Engineering Journal, 2025)

Enhanced photosynthetic CO2 fixation in mutualistic Chlorella sp. and Mesorhizobium loti co-cultures - Dandan Yao; Yunhui Li; Kun Tian; Meng Wang; Ding Tan; Xingjia Fu; Yonghong Wu; Yun Liu; Hui Wang (Chemical Engineering Journal, 2025)

A ratiometric fluorescence sensor based on Eu3+ doped LDH@CMCh gel for visual detection and effective adsorption of tetracycline antibiotics - Xiaoli Guo; Jiaxiao Niu; Yixin Meng; Yongpeng Ma; Ruiyu Fu; Jiawei Liu; Xiaoqin Hai; Hongbo Li; Yanhui Zhang; Xin Di (Carbohydrate Polymers, 2025)

Two nuclear loci Rf-m1 and Rf-m2 interplay to determine the fertility restoring efficacy of ZD-type CMS soybean - Xiaoxia Yu; Yupeng Feng; Lulu Zhou; Hongye Gao; Hongbin Wang; Yaru Chen; Jiamai Liang; Tianyu Meng; Meng Li; Yihan Yuan; Junping Yu; Hao Liu; et al. (Theoretical and Applied Genetics, 2025)

Apolipoprotein E ε4-Specific Relationship Between Serum Olfactomedin 4 and Alzheimer’s Disease - Chunxiao Wei; Guimei Zhang; Xiaoshu Fu; Meng Zhao; Weijie Zhai; Yanxin Shen; Li Sun (Molecular Neurobiology, 2025)

Adaptation and synthetic biology of the model cyanobacterium Synechococcus elongatus for sustainable development: a review - Weizhao Meng; Mengsheng Xia; Jingyan Hu; Chao Wang; Cheng Qian; Mingmin Zhang; Weiqi Fu (Frontiers in Marine Science, 2025)
Synechococcus elongatus is a model cyanobacterium with remarkable adaptability to diverse environmental stresses, making it a promising candidate for the photoautotrophic conversion of carbon dioxide into valuable chemicals. This review explores the adaptive mechanisms that allow S. elongatus to survive under various abiotic stresses, such as changes in CO 2 levels, heavy metals, and light conditions. We also highlight recent advancements in synthetic biology that have enabled the engineering of S. elongatus to produce biofuels and other value-added compounds, including fatty acids, alcohols, and carotenoids. Additionally, we discuss the applications of modern omics techniques to elucidate the genetic basis of stress tolerance and metabolic regulation. Despite the promising potential of S. elongatus for industrial applications, challenges remain in scaling up production, enhancing genetic stability, and optimizing bioreactor systems. Finally, we provide insights into future directions, including the integration of genome engineering, system-level modeling, and co-culture strategies, to improve the efficiency of cyanobacterial cell factories for sustainable biotechnology applications.

Recruiting high-efficiency denitrifying consortia using Pseudomonas aeruginosa - Jiajie Wu; Xiaolong Wang; Yue Fu; Zhong Yu; Fangang Meng (Water Research, 2025)

Adsorption kinetics and mechanisms of carbohydrate/UiO-66 composites for cationic/anionic dye removal - Shuang Xu; Liqin Wang; Feng Wang; Shangjun Fu; Wei Meng; Guowen He; Wenxiu Cao; Wei Zhang (Journal of Water Process Engineering, 2025)

Occurrence, spatial-seasonal variation and air-soil exchange of traditional and novel organochlorine pesticides across 30° latitude in Eastern China: Old tales and new realities - Liang Wang; Wan-Li Ma; Pu-Fei Yang; Chun-Yan Huo; Peng-Tuan Hu; Wen-Long Li; Meng-Qi Fu (Journal of Hazardous Materials, 2025)

Simultaneous and instrument-free detection of quinine and crystal violet based on a dual-emissive Eu3+-functionalized metal-organic framework - Hou-Qun Yuan; Yuan Yuan; Si-Yi Liu; Jia-Hao Fu; Yi-Fan Xia; Wei Li; Meng-Yuan Pan; Lirong Jiang; Peiyao Chen; Guang-Ming Bao (Journal of Hazardous Materials, 2025)

Co-deposition of CuxFey on nickel foam promotes NH3 desorption to enhance nitrate reduction activity and ammonia selectivity - Guangyuan Meng; Xinwan Zhang; Wenzhao Fu; Yannan Qiu; Di Yin; Peng Chen; Daqing Jia; Zhihao Lu; Lehua Zhang (Journal of Environmental Chemical Engineering, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Cobalt phthalocyanine modified holey Graphene/Cobalt phosphide for supercapacitor electrodes - Wei Chen; Min Fu; Siyuan Yang; Liangmin Ning; Hao Yu; Meng Gao; Kunhua Wang; Meili Guan; Ruitao Lv; Nan Li; Jianming Pan (Chemical Engineering Journal, 2025)

A biphasic nanoplatform with switchable biochemical programs for combined organelle-specific cancer therapy - Wanting Hao; Meng Zhang; Ruokun Li; Zi Fu; Xinyuan Cui; Zeyang Liu; Hongjing Jiang; Dalong Ni; Fuhua Yan (Chemical Engineering Journal, 2025)

Benzalkonium chloride assisted quenching-free fabrication of nonalloyed FAPbI3 perovskite films and solar cells - Tian Hou; Xiaoran Sun; Zhipeng Fu; Zhicheng Wang; Linhu Xiang; Yuelong Huang; Xiaojing Hao; Meng Zhang (Chemical Engineering Journal, 2025)

Investigation of frozen rock behavior: mechanical properties, pore structure, and strength under confining pressures - Kun Wang; Jian-xin Fu; Meng Zhaobo; Zhang Bangyi (Cold Regions Science and Technology, 2025)

Evaluation and selection of superior Fraxinus mandshurica families for genetic improvement using growth traits, morphological characteristics, and wood properties - Meng Fu; Ronghua Liang; Pengfei Wang; Qiang Feng; Chaoqun Li; Ying Xin; Yaguang Zhan; Fansuo Zeng (Euphytica, 2025)

Nutrient additions have minor impact on microbial carbon use efficiency - Qunou Jiang; Lingyuan Yan; Huimin Wang; Xiaoqin Dai; Shengwang Meng; Xiaoli Fu; Fengting Yang; Zeqing Ma; Wenjiao Shi; Wenjun Lv; Yuxin Wang; Decai Gao (Agriculture, Ecosystems & Environment, 2025)

Bayesian-based analysis of sequence activity characteristics in the Bohai Rim region - Jin-Meng Bi; Cheng Song; Fu-Yang Cao (Applied Geophysics, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

New Colorimetric Chemosensor for Rapid Naked-Eye Detection of Cu2+ and Its Application in Gas-Generating Agents - Xiaohong Cheng; Jun You; Shaoyong Meng; Wenjie Shen; Tao Du; Wenbin Fu; Yunqiang Luo; Song Wang (Journal of Fluorescence, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Synergistic effects of bio-organic fertilizer and different soil amendments on salt reduction, soil fertility, and yield enhancement in salt-affected coastal soils - Meng Xiao; Shengguo Jiang; Jinbiao Li; Wenping Li; Pengxiao Fu; Guangming Liu; Jinlin Chen (Soil and Tillage Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Causal relationship analysis and risk assessment of contributing factors in coal mine ordinary accidents: A case study (2002–2023) - Chenhui Yuan; Gui Fu; Jiangshi Zhang; Yongtun Li; Meng Han; Yuxuan Lu; Jinkun Zhao; Zhirong Wu (Process Safety and Environmental Protection, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

Catalysis and absorption behaviors of the shelled-hollow CaO-MgO microspheres on product distributions and desulfurization during waste tire fast pyrolysis - Boyu Qu; Ye Shui Zhang; Tian Wang; Yutao Zhang; Zegang Fu; Yucen Meng; Aimin Li; Guozhao Ji (Fuel, 2025)

Manganese vacancy and shell protection as two-pronged strategies for boosting capacitive deionization of manganese-based prussian blue analog electrodes - Guoxiang Liu; Wei Chen; Liangmin Ning; Hao Yu; Meng Gao; Linzheng Ma; Ruitao Lv; Jianming Pan; Min Fu (Desalination, 2025)

Mechanochemical treatment boosted microwave-assisted sulfonation of softwood lignin for the fabrication of dye dispersant - Xu Fu; Ling-Ping Xiao; Bo-Wen Meng; Wen-Jie Li; Run-Cang Sun (Chemical Engineering Journal, 2025)

A dual-modification strategy for both the Quinone-based cathode and Zn anode electrodes of the aqueous zinc-ion battery - Mengyao Zhang; Jiahao Fu; Na Xu; Lei Meng (Chemical Engineering Journal, 2025)

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

Increased expression of an isoform of the long non-coding RNA, lnc37707, is associated with malathion resistance in Bactrocera dorsalis - Li-Wei Meng; Zong-Yu Luo; Fu-Qiang Zhang; Yi-Xuan Dong; Chao Ye; Wei Zhang; Jin-Jun Wang (Pesticide Biochemistry and Physiology, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Comprehensive characterization of micro-pore structures in different lithologies of the lacustrine fine-grained mixed sedimentary reservoir of the Shahejie Formation in the Jiyang Depression - Wenneng Zhao; Mingshi Feng; Yanyu Gao; Ying Fu; Wanbin Meng; Siyuan Fan; Yi Lan; Bing Zhang (Ore and Energy Resource Geology, 2025)

Remediation effectiveness and mechanism on surfactant-enhanced remediation of low-permeability petroleum hydrocarbon contaminated soil under fracturing conditions - Shi-Jin Feng; Jiu-Ge Niu; Fu-Jiang Shi; Qi-Teng Zheng; Meng-Wen Gao (Journal of Hydrology, 2025)

The cation/H+ exchanger OsCAX2 is involved in cadmium uptake and contributes to differential grain cadmium accumulation between Indica and Japonica rice - Xiang-Qian Liu; Huan Liu; Meng-Jie Fu; Li-Wen Zhang; Si-Fan Yin; Zhong Tang; Fang-Jie Zhao; Xin-Yuan Huang (Journal of Hazardous Materials, 2025)

Integrated ecological-health risk assessment of ofloxacin - Jingyu Wang; Yukun Ma; Xuehui Zhou; Shuai Wang; Yijia Fu; Shenghan Gao; Xinyi Meng; Zhenyao Shen; Lei Chen (Journal of Hazardous Materials, 2025)

Sustainable ammonia leaching for efficient nickel and cobalt recovery from mixed hydroxide precipitate - Yu Wang; Yanjuan Zhang; Caixia Lv; Guangye Wei; Long Meng; Jiajie Fu; Zhihui Yu; Jingkui Qu (Journal of Environmental Chemical Engineering, 2025)

Experimental study of the effects of engine oil on gaseous and particulate emissions during gasoline/ethanol combustion - Zichao Meng; Feng Zhou; Xiongbo Duan; Jianqin Fu; Jingping Liu; Banglin Deng (Fuel, 2025)

Study of thickened CO2 flooding for enhancing oil recovery in Low-Permeability sandstone reservoirs - Guojun Li; Meilong Fu; Jiani Hu; Shoufei Lu; Fankun Meng (Fuel, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

Coordinated transcriptional regulation of carbohydrate-related pathways contributes to the difference of starch accumulation between starchy cassava and sugary cassava - Zehong Ding; Lili Fu; Ganlu Chen; Yan Yan; Weiwei Tie; Xianwei Meng; Jinghao Yang; Xianjin Qiu; Jiaming Zhang; Wei Hu (Carbohydrate Polymers, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

Flexible surface acoustic wave technology for enhancing transdermal drug delivery - Jikai Zhang; Duygu Bahar; Hui Ling Ong; Peter Arnold; Meng Zhang; Yunhong Jiang; Ran Tao; Luke Haworth; Xin Yang; Chelsea Brain; Mohammad Rahmati; Hamdi Torun; et al. (Drug Delivery and Translational Research, 2025)
Transdermal drug delivery provides therapeutic benefits over enteric or injection delivery because its transdermal routes provide more consistent concentrations of drug and avoid issues of drugs affecting kidneys and liver functions. Many technologies have been evaluated to enhance drug delivery through the relatively impervious epidermal layer of the skin. However, precise delivery of large hydrophilic molecules is still a great challenge even though microneedles or other energized (such as electrical, thermal, or ultrasonic) patches have been used, which are often difficult to be integrated into small wearable devices. This study developed a flexible surface acoustic wave (SAW) patch platform to facilitate transdermal delivery of macromolecules with fluorescein isothiocyanates up to 2000 kDa. Two surrogates of human skin were used to evaluate SAW based energized devices, i.e., delivering dextran through agarose gels and across stratum corneum of pig skin into the epidermis. Results showed that the 2000 kDa fluorescent molecules have been delivered up to 1.1 mm in agarose gel, and the fluorescent molecules from 4 to 2000 kDa have been delivered up to 100 µm and 25 µm in porcine skin tissue, respectively. Mechanical agitation, localised streaming, and acousto-thermal effect generated on the skin surface were identified as the main mechanisms for promoting drug transdermal transportation, although micro/nanoscale acoustic cavitation induced by SAWs could also have its contribution. SAW enhanced transdermal drug delivery is dependent on the combined effects of wave frequency and intensity, duration of applied acoustic waves, temperature, and drug molecules molecular weights. Graphical Abstract Graphical Abstract: Flexible surface acoustic wave technology for enhancing transdermal drug delivery

Dietary supplementation of Litsea cubeba oil promotes growth and intestinal immunity in GIFT tilapia - Fu-Yan Chen; Ying Bai; Gan Yang; Han-Jing Yan; Liu-Yang Li; Zhi-Mou Liu; Ju-Ping Wen; Zhen-Bin Wang; Jun-Hong Xia; Meng-Ling He (Aquaculture, 2025)

Mechanism study of the effect of a surface liquid film on the collision adhesion behaviour of rice stalks - Jun Fu; Meng Zhang; Chao Cheng; Haiming Zhao; Luquan Ren (Biosystems Engineering, 2025)

Selective production of olefins from methanol over a heteroatomic SAPO-34 zeolite - Zhaodong Zhu; Mengtian Fan; Meng He; Bing An; Yinlin Chen; Shaojun Xu; Tianze Zhou; Alena M. Sheveleva; Meredydd Kippax-Jones; Lutong Shan; Yongqiang Cheng; Hamish Cavaye; et al. (Science Bulletin, 2025)

Prenatal high-sucrose diet affects pulmonary artery contractile functions via MT receptors - Xueqin Feng; Hongwei Fu; Xiao Sun; Hua Shu; Yongning Zhu; Yanyan Bai; Qinggui Ren; Xinying Liu; Meng Liu; Fanyong Zhang; Yanping Wang (Reproductive Toxicology, 2025)

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

Photocatalytic degradation of xanthate by S–scheme CeO2/g–C3N4 heterojunction and its DFT calculation - Deqin Meng; Li Wang; Cheng Zhong; Jiani Fu; Xiaolong Hu; Dengzheng Gao; Qingbin Guo; Jinbo Hou; Hang Zhao (Journal of Water Process Engineering, 2025)

β-cyclodextrin polymers as a new sorbent for solid-phase extraction of xenobiotics in Urine - Yuan Meng; Minqi Liu; Yicheng Liao; Junhuai Luo; Xiaoli Fu; Peizhe Sun (Journal of Hazardous Materials, 2025)

Nutrient enrichment shapes litter micro-food webs in a subtropical plantation - Hui Shao; Huimin Wang; Manuel Delgado-Baquerizo; Xiaoqin Dai; Shengwang Meng; Paul Kardol; Yuxin Wang; Fusheng Chen; Liang Kou; Decai Gao; Xiaoli Fu (Forest Ecology and Management, 2025)

Potential effects of pH changes in the micro-environment during desalination on infant powder: The perspective of pH shift affecting whey protein molecular structure and function - Meng-Qi Liu; Wen-Xiu Zhi; Hong-Fu Zhao; Ying-Chao Qiu; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Hydrocolloids, 2025)

Frabrication of carboxymethylchitin nanofibers and fish gelatin hybrid gels with robust gel performance - Rongqiang Chen; Shuai Zhang; Jiao Jiao Sun; Lijuan Xu; Yuan Duan; Fengchen Li; Yanhui Han; Xiao Fu; Meng Wang; Yong Hong Meng; Yurong Guo (Food Hydrocolloids, 2025)

Olanzapine exposure disordered lipid metabolism, gut microbiota and behavior in zebrafish (Danio rerio) - Yawei Wang; Fu You; Zhenyi Huang; Yuan Liu; Boya Yang; Xulu Chang; Guokun Yang; Xue Tian; Shikun Feng; Xiaolin Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Tuning photoluminescence and electroluminescence of multi-resonance thermally activated delayed fluorescence emitters through peripheral donor modification for highly efficient deep-blue OLEDs - Chen-Lu Hou; Sai Guo; Yu-Fu Sun; Jia-Xuan Hu; Hong-Jin Liao; Xiao Li; Fu-Lin Lin; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Deciphering direct and indirect factors contributing to airborne microbes in university dormitories - Lumeng Liu; Di Huang; Shuwan Wang; Qisheng Li; Ting Fu; Qiujia Lai; Chi Feng; Meng Liu; Huan Liu (Building and Environment, 2025)

Electroacupuncture Promotes the Generation of Intestinal Treg Cells After Ischemic Stroke by Foxp3 Acetylation Regulation - Yonglin Chen; Ling Ouyang; Xinyi Yang; Bufan Wu; Lingling Meng; Jialin Gu; Yaling Wang; Juan Li; Jingjing Zhang; Xinyue Jing; Shengfeng Lu; Lanying Liu; et al. (Molecular Neurobiology, 2025)

Integrated multi-omic high-throughput strategies across-species identified potential key diagnostic, prognostic, and therapeutic targets for atherosclerosis under high glucose conditions - Zhida Shen; Meng Zhao; Jiangting Lu; Huanhuan Chen; Yicheng Zhang; Songzan Chen; Zhaojing Wang; Meihui Wang; Xianglan Liu; Guosheng Fu; He Huang (Molecular and Cellular Biochemistry, 2025)

Sublethal effects of lambda-cyhalothrin on the biological characteristics, detoxification enzymes, and genes of the papaya mealybug, Paracoccus marginatus - Jian-Yu Li; Yan-Ting Chen; Yan Chen; Jian-Wei Zhao; Jian-Wei Fu; Meng-Zhu Shi (Journal of Pest Science, 2025)

Research on Optimization Method for Irregular Seismic Acquisition in Curved Wave Domain Based on Simulated Annealing - Hu Zhao; Meng-yang Chen; Yu-dong Ni; Rong-rong Zhao; Fu-hao Jiang; Wei Chen; Jing-yun Dai (Applied Geophysics, 2025)

Freeze-thaw cycles affect hydrothermal and heavy metal transport mechanisms in porous media: Closed and transient flooded system conditions - Tianxiao Li; Chengye Zhao; Qiang Fu; Fanxiang Meng; Dong Liu; Mo Li (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Facile access to spirobifluorene-fused chiral multi-resonance materials with ultra-narrowband blue emission - Hu Cheng; Chen-Hao Guo; Meng Li; Yusong Guo; Zhangyi Fu; Junjie Liu; Yudong Yang; Jingbo Lan; Zhengyang Bin (Science Bulletin, 2025)

Behavioural loyalty analysis of bus passengers using multi-source data fusion - Yu Fu; Xiang Wang; Fanrui Meng; Sihan Wang; Yangchen Song; Yutong Wang (Journal of Transport Geography, 2025)

Effects of dissolved oxygen on the anaerobic/oxic/anoxic simultaneous nitrification, denitrification and phosphorus removal (AOA-SNDPR) process for advanced wastewater treatment and in situ sludge reduction - Baokun Xu; Liang Liu; Meng Wang; Zhidong Fu; Peng Xu; Jingwei Ma; Qiulai He (Journal of Environmental Chemical Engineering, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)

Nondestructive three-dimensional structure and growth characteristics of anammox granular sludge - Meng-Wen Peng; Ya-Song Chen; You-Peng Chen; Wan Sun; Meng-Meng Liu; Xun Weng; Shuai Wang; Yu Shen; Hui-Min Fu (International Biodeterioration & Biodegradation, 2025)

Microbial and chemical diversity analysis reveals greater heterogeneity of Liubao tea than ripen Pu-erh tea - Hao-Yi Yan; Meng-Fu Chen; Yi-Chen Hu; Ya-Shuai Kong; Tie-Jun Ling (Food Research International, 2025)

Hotspots of nitrogen losses from anthropogenic sources in the Huang-Huai-Hai Basin, China - Shuyu Fu; Fanlei Meng; Sijie Feng; Chenxi Yao; Jiajie Liu; Xuejun Liu; Wen Xu (Environmental Pollution, 2025)

Ecological effect of seasonally changing temperature on the life cycle of Aurelia aurita - Da Song; Wentao Fu; Meng Fan; Kun Li (Ecological Modelling, 2025)

Mechanisms of hydraulic erosion control in different microrelief patterns of loess sloped farmland under continuous rainfall - Xinkai Zhao; Xiaoyu Song; Danyang Wang; Lanjun Li; Pengfei Meng; Chong Fu; Long Wang; Wanyin Wei; Yu Liu; Huaiyou Li (CATENA, 2025)

Construction of polylactic acid plastisphere microbiota for enhancing nitrate reduction in denitrification biofilters - Yanxi Chen; Mengzhen Huang; Yue Fu; Tianyu Gao; Zhihao Gan; Fangang Meng (Bioresource Technology, 2025)

Fitness and adaptive evolution of a Rhodococcus sp. harboring dioxin-catabolic plasmids - Xu Wang; Changai Fu; Meng Chen; Yanan Wu; Yu Chen; Yan Chen; Li Li (World Journal of Microbiology and Biotechnology, 2025)

Evaluating overhanging slope failure mechanisms and rockfall trajectories through integrated UAV imagery and discrete element modeling - Meng-Chia Weng; Geng-Man Zhang; Yu-Yao Fu; Hoang-Khanh Le; Yu-Hui Kao (Landslides, 2025)
To evaluate the threat of rockfall from an overhanging slope above a bridge, this study proposes a comprehensive analysis procedure to assess the failure mechanisms of the slope and the associated rockfall trajectories. The analysis utilizes high-resolution point cloud data obtained through integrated UAV-based imagery technology, enabling a detailed evaluation of joint configurations and slope stability. The geometric reconstruction of unstable rock blocks, combined with stereographic projections, provides an in-depth analysis of potential failure modes. Discrete element modeling (DEM) is employed to simulate the failure processes and predict rockfall trajectories, with particular emphasis on the potential risks to the underlying bridge. The results indicate that rockfall events near the bridge are primarily driven by wedge-shaped failures, a finding confirmed by both the proposed inverted three-dimensional projection method and DEM simulations. The analysis identifies critical rock blocks near the bridge, underscoring the need for targeted mitigation strategies. This case study demonstrates the effectiveness of integrating UAV-derived data with DEM for assessing overhanging slope failures and managing rockfall risks in similar geological settings.

Influence of Rhamnolipids Biosurfactant on the Anodic Electrochemical Performance in Marine Sediment Microbial Fuel Cell and the Acceleration Degradation of Crude Petroleum - Luyao Hou; Xuerong Zai; Yao Meng; Shengkang Liang; Yali Cao; Yan Chen; Huaijing Zhang; Xiang Huang; Yubin Fu (Journal of Ocean University of China, 2025)

Evolutionary Analysis of Hypoderma Pantholopsum in Tibetan Antelopes on the Qinghai–Tibetan Plateau - Fan Zhang; Haining Zhang; Zhi Li; Ru Meng; Peiling Ye; Yong Fu (Acta Parasitologica, 2025)

The Seasonal Correlation Between El Niño and Southern Oscillation Events and Sea Surface Temperature Anomalies in the South China Sea from 1958 to 2024 - Jun Song; Lingxiang Yao; Junru Guo; Yanzhao Fu; Yu Cai; Meng Wang (Journal of Marine Science and Engineering, 2025)
This study utilizes high-resolution sea surface temperature (SST) reanalysis data (0.25° × 0.25°) to investigate the relationship between SST anomalies in the South China Sea and ENSO events. The main findings are as follows: First, there is a delayed correlation between ENSO and SST anomalies in the South China Sea, with the correlation being stronger during El Niño years than during La Niña years. Second, the correlation with the peak values of the Oceanic Niño Index (ONI) is strongest for El Niño events with a 9-month lead, while for La Niña events, it is strongest with a 2-month lead. Seasonally, during El Niño events, the strongest correlations are observed in summer with a 3-month lead and in winter with a 1-month lag. For La Niña events, the strongest correlations are seen in summer with an 8-month lag and in winter with a 9-month lag. Finally, an analysis of atmospheric anomalies and shear kinetic energy anomalies relative to SST anomalies reveals a significant seasonal SST response, particularly during the summer of El Niño years and the winter of La Niña years. Overall, these results enhance our understanding of ENSO’s influence on the South China Sea and provide valuable insights for climate prediction and ecosystem protection in the region.

Structure and function of rhizosphere and nonrhizosphere bacterial communities of Ziziphus jujuba var. spinosa (Bunge) Hu ex H. F. Chow in the southern Taihang Mountains, China - Xiangrui Fu; Xin Meng; Donglai Ma; Yuguang Zheng; Jianming Jiang; Yuping Yan; Xian Gu (Biologia, 2025)

Dynamic gaming strategies about fuel consumption reduction and mileage range between two heterogeneous automotive supply chains - Yongxi Yi; Ao Fu; Meng Zhang; Yuqiong Li (Environment, Development and Sustainability, 2025)

Exploring the spatial heterogeneity of soil organic carbon and the influence of coastal factors: A case study in the Yellow River Delta, China - Youxiao Wang; Yingjun Sun; Qi Wang; Pingjie Fu; Yaohui Liu; Fang Wang; Fei Meng (Science of The Total Environment, 2025)

Virulence phenotype alteration impacts nosocomial pathogen persistence on inanimate surfaces in hospital settings - Meng Zhang; Lizhang Liu; Xiaoqiang Yang; Yanhua Kang; Qiuying Qin; Yingying Fu; Lin Zhu; Yongchang Xu (Science of The Total Environment, 2025)

Application of multi-angle spaceborne observations in characterizing the long-term particulate organic carbon pollution in China - Yun Hang; Qiang Pu; Qiao Zhu; Xia Meng; Zhihao Jin; Fengchao Liang; Hezhong Tian; Tiantian Li; Tijian Wang; Junji Cao; Qingyan Fu; Sagnik Dey; et al. (Science of The Total Environment, 2025)

An enhancer–promoter-transcription factor module orchestrates plant immune homeostasis by constraining camalexin biosynthesis - Ying Zhang; Meng Tang; Yi Zhang; Qinglin Cheng; Lijiang Liu; Wei Chen; Jiatao Xie; Jiasen Cheng; Yanping Fu; Bo Li; Daohong Jiang; Xiao Yu (Molecular Plant, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Unraveling the resistance mechanism of anammox granular sludge to iron nanoparticles - Xun Weng; Meng-Jiao Gao; Zheng Mao; Hui-Min Fu; Shi-Jun Li; Peng Yan; You-Peng Chen (Journal of Environmental Management, 2025)

Metagenomic perspectives on antibiotic resistance genes in tap water: The environmental characteristic, potential mobility and health threat - Qiyue Meng; Yibo Zhang; Da He; Yu Xia; Jie Fu; Chenyuan Dang (Journal of Environmental Sciences, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Induced electric field as alternative pasteurization to improve microbiological safety and quality of bayberry juice - Liping Xue; Zitao Zheng; Yuhang Wu; Lingtao Zhang; Huang Zhang; Na Yang; Xueming Xu; Yamei Jin; Man Meng; Fu Wang (Food Chemistry, 2025)

Enhancing CO2-reduction methanogenesis in microbial electrosynthesis: Role of oxygen-containing groups on carbon-based cathodes - Xuejiao Qi; Xuan Jia; Mingxiao Li; Meiying Ye; Yufang Wei; Fanhua Meng; Shanfei Fu; Beidou Xi (Bioresource Technology, 2025)

Thickness monitoring of threshing mixture on the oscillating plate of corn grain harvester - Jun Fu; Meng Zhang; Chao Cheng; Haiming Zhao; Luquan Ren (Computers and Electronics in Agriculture, 2024)

Whole-genome mutagenesis of whiteleg shrimp (Litopenaeus vannamei) by ARTP and analysis of its mutational characteristics - Qiang Fu; Jingxin Zhou; Sheng Luan; Kun Luo; Baolong Chen; Jiawang Cao; Xupeng Li; Qun Xing; Jie Kong; Xianhong Meng (Aquaculture, 2024)

Manganese(III) dominants the mobilization of phosphorus in reducing sediments: Evidence from Aha reservoir, Southwest China - Quan Chen; Jing-fu Wang; Meng-qiang Zhu; Hai-bo Qin; Peng Liao; Zhi-tong Lu; Peng-cheng Ju; Jing-an Chen (Science of The Total Environment, 2024)

Increased global warming potential during freeze-thaw cycle is primarily due to the contribution of N2O rather than CO2 - Chunhong Zhao; Ziping Liu; Huimin Wang; Xiaoqin Dai; Shengwang Meng; Xiaoli Fu; Qunou Jiang; Wenjun Lv; Jiancheng Chen; Decai Gao (Science of The Total Environment, 2024)

Evaluating long-term reductions in trace metal emissions from shipping in Shanghai - Meng Wang; Yusen Duan; Juntao Huo; Jia Chen; Yanfen Lin; Qingyan Fu; Tao Wang; Yu Huang; Junji Cao; Shun-cheng Lee (Journal of Hazardous Materials, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Mechanisms of radical regulation during carbamazepine degradation by UV-LED/chlorine process with different wavelengths in water - Qi Fu; Zhi Zhang; Yi-Li Lin; Tian-Yang Zhang; Yun-Lu Zhang; Renjie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Jian Lu; Zheng-Ning Luo; Chao Zeng; Huan He; et al. (Journal of Environmental Chemical Engineering, 2024)

Bifunctional reduced graphene oxide/polyelectrolytes/MoS2-AuNPs hybrids with Vis/NIR photocatalytic and photothermal activities for biosafe and efficient antibacterial applications - Meng Fu; Chang Luo; Qi Yuan; Zequn Ma; Quansheng Long; Baihui Liu; Dang Wu; Jingshui Xu; Xiangming Li (Journal of Environmental Chemical Engineering, 2024)

Electrodeposition of dense spherical Ni3P on nickel foam cathode enhance nitrate electrochemical reduction via promoting nitrate adsorption - Wenzhao Fu; Guangyuan Meng; Di Yin; Xinwan Zhang; Yaqi Shi; Zhengwu Yang; Dingming Chang; Peng Chen; Lehua Zhang (Journal of Environmental Chemical Engineering, 2024)

Notch signaling regulates limb regeneration through Hes1 and HeyL in the Chinese mitten crab - Ju Li; Xiaoyan Lv; Xin Zhang; Xiumei Zhao; Yuxuan Meng; Sidi Liu; Simiao Fu; Jinsheng Sun (Insect Biochemistry and Molecular Biology, 2024)

CFD-DEM study on the raceway transport phenomena and thermo-chemical behaviors in a three-dimensional blast furnace: Effects of process parameters - Meng Li; Zhong Li; Chao Li; Guanyin Wu; Xizhong An; Hao Zhang; Haitao Fu; Xiaohong Yang; Qingchuan Zou (Fuel, 2024)

L-lysine enhances pork color through antioxidant activity and myoglobin conformational changes - Xiuyun Guo; Shuangyi Xu; Peiqi Jiang; Chao Fu; Jipan Wang; Xiangren Meng (Food Research International, 2024)

Effect of different food matrices on the bioaccessibility of vitamin D3 in beverage systems: Comparison between juice and liquid milk - Shaojie Fu; Jinfeng Bi; Xiyu Jiang; Meng Liu; Xuan Liu (Food Chemistry, 2024)

Effects of deep, air and vacuum frying on oyster quality and protein-mediated mechanism analysis via TMT quantitative proteomics - Junbo Chu; Songyi Lin; Baoshang Fu; Xiangning Meng; Jiaxin Qiang; Simin Zhang (Food Chemistry, 2024)

Structural properties and antioxidant capacity of different aminated starch-phenolic acid conjugates - Feng-Kun An; Meng-Yun Li; Hai-Lu Luo; Xing-Long Liu; Zhen Fu; Min-Hong Ren (Food Chemistry, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

Functional characterization of Arabidopsis hydroxynitrile lyase in response to abiotic stress and the regulation of flowering time - Lei Xue; Duo Bu; Jiangyan Fu; Zhe Zhou; Meng Gao; Ren Wang; Sheng Xu (Molecular Biology Reports, 2024)

Linkage of Mineral Inclusions and Zoning of Magnetite with Fluid Evolution of Hydrothermal Systems: A Case Study of the Fenghuangshan Cu-Fe-Au Skarn Deposit, Eastern China - Xiao-Wen Huang; Yiping Yang; Mei-Fu Zhou; Yu-Miao Meng; Jian-Feng Gao; Liang Qi (Journal of Earth Science, 2024)

Thalassospira aquimaris sp. nov. and Winogradskyella marincola sp. nov. two marine bacteria isolated from an agar-degrading co-culture - Zi-Yue Fu; Dao-Feng Zhang; Meng-Han Huang; Hong-Chuan Wang; Xiao-Ye Chen; Yu-Fang Yao; Yang Yuan; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Exploring the glycoprotein washing fluid-assisted cleanup for the restoration of oil-contaminated shorelines with environmental integrity - Jiyao Sui; Rengyu Yue; Huifang Bi; Haiyan Fu; Aili Yang; Meng Wang; Chunjiang An (Science of The Total Environment, 2024)

TBiSeg: A transformer-based network with bi-level routing attention for inland waterway segmentation - Chuanmao Fu; Meng Li; Bo Zhang; Hongbo Wang (Ocean Engineering, 2024)

Active methane release from the early Cambrian seafloor? Clues from Ba isotopes - Meng Cheng (程猛); Wei Wei; Xinyang Chen; Haiyang Wang; Lianjun Feng; Zhenbing She; Yong Fu; Thomas J. Algeo; Fang Huang; Chao Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Supplementation with Akkermansia muciniphila improved intestinal barrier and immunity in zebrafish (Danio rerio) - Yawei Wang; Zhenyi Huang; Zewei Gui; Boya Yang; Fu You; Guokun Yang; Xindang Zhang; Xulu Chang; Xiaolin Meng (Fish & Shellfish Immunology, 2024)

Contrasting dynamics of marine bacterial-algal communities between the two main pulses of the Late Ordovician Mass Extinction - Yu Liang; Zerui Ray Liu; Thomas J. Algeo; Lei Meng; Chengdong Ming; Jun Wang; Bowen Song; Zhonghui Liu; Mei-Fu Zhou (Earth and Planetary Science Letters, 2024)

Charge transfer complex induced confinement effect between organic semiconductor and polymer chains for enhancing high-temperature capacitive energy storage - Tan Zeng; Chao Yuan; Qiao Li; Zhaoyu Ran; Li Meng; Jing Fu; Dongduan Liu; Jinliang He; Qi Li (Chemical Engineering Journal, 2024)

Fabrication of hydrogen-bonded crosslinked hydrogel vitrimer with enhanced self-healing and printability via K+ induced low methyl apple pectin - Tianya Hu; Shuai Zhang; Huan Zhang; Xiao Fu; Shuai Luo; Shuaida Wang; Pengtao Zhao; Xiaoyu Wang; Yong Hong Meng; Yurong Guo (Carbohydrate Polymers, 2024)

Tunicate cellulose nanocrystals strengthened injectable stretchable hydrogel as multi-responsive enhanced antibacterial wound dressing for promoting diabetic wound healing - Shengming Hua; Yujie Zhang; Yifei Zhu; Xin Fu; Lingtao Meng; Lihua Zhao; Lingming Kong; Shihui Pan; Yuju Che (Carbohydrate Polymers, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

On theoretical and practical analyses of BDS-3/Galileo/GPS all-in-view and PPP time transfer with the consideration of satellite clock biases - Dong Zhang; Fu Zheng; Meng Wang; Yuanhui Lin; Liangcheng Deng; Zhen Wang; Chuang Shi (Journal of Geodesy, 2024)

Hohaiivirga grylli gen. nov., sp. nov., a New Member of the Family Methylobacteriaceae, Isolated from Cricket (Gryllus chinensis) - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wei He; Lu Wang; Zi-Yue Fu; Wen-Jun Li; Ai Hua Zhang; Dao-Feng Zhang (Current Microbiology, 2024)

High resolution (1-km) surface soil moisture generation from SMAP SSM by considering its difference between freezing and thawing periods in the source region of the Yellow River - Xiaolei Fu; Yuchen Zhang; Luofujie Guo; Haishen Lü; Yongjian Ding; Xianhong Meng; Yu Qin; Yueyang Wang; Bin Xi; Shiqin Xu; Pengcheng Xu; Gengxi Zhang; et al. (Agricultural and Forest Meteorology, 2024)

Genomic characteristics of human respiratory syncytial virus from children in China during 2017-2020 - Fei Li; Yun Zhu; Qiuping Li; Xiaolei Guan; Hailin Zhang; Changchong Li; Meng Zhang; Lei Li; Yiliang Fu; Yali Duan; Luci Huang; Zhengde Xie; et al. (Archives of Virology, 2024)

Effect of Osteogenic Metabolic Differentiation of Silver Nanoparticles-based Periodontal Ligament Fibroblasts on Orthodontic Tooth Movement - Juan Fu; Kun Meng; Qingmin Yuan (Cell Biochemistry and Biophysics, 2024)

Parameter optimization and experiment of air-fed rubber tree pesticide application device based on CFD-DEM coupling method - Meng Fu; Huiming Zhang; Yong Wang; Wei Fu; Bin Zhang; Yuxing Fu; Tiwei Zeng (Computers and Electronics in Agriculture, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A new split-ring protoilludane-type sesquiterpenoid and prenylated aromatic compounds from Coriolopsis trogii - Xin-Meng Zhai; Lu-Lu Wang; Ning Li; Fu-Cai Ren (Phytochemistry Letters, 2024)

The JA-to-ABA signaling relay promotes lignin deposition for wound healing in Arabidopsis - Huimin Xu; Chaoqun Dong; Ying Wu; Shasha Fu; Arfa Tauqeer; Xinyun Gu; Qianfang Li; Xufang Niu; Peng Liu; Xiaoyue Zhang; Chuanyou Li; Meng Li; et al. (Molecular Plant, 2024)

Quantification of factors affecting fault sealing by using machine learning: Shuangtaizi fault anticline, southern margin of the Liaohe Western Depression, Northeastern China - Xiaofei Fu; Mingming Jiang; Zhiming Hu; Yejun Jin; Lingdong Meng; Ruishan Du; Qi Liu (Marine and Petroleum Geology, 2024)

Quantification- and structural-taste intensity of umami peptides from Agrocybe aegerita through quantitative structure-activity relationship - Fan Yang; Hongyan Meng; Anzhen Fu; Ye Liu; Shuang Bi (Food Chemistry, 2024)

Self-standing COF-MOF composite sandwich membranes with high permeability for dye separation - Bingbing Chen; Xing Gao; Xiaojiao Hou; Yuanlin Fu; Yuhang Li; Fuqiang Fan; Tieqiang Wang; Fanbao Meng; Yu Fu; Junchao Ma (Desalination, 2024)

Surface-controlled oxygen vacancy-rich Bi/BiVO4 Schottky junction for highly selective and active photocatalytic nitrogen fixation - Guanghua Xia; Yue Meng; Qiang Fu; Zhiling Huang; Bo Xie; Zheming Ni; Shengjie Xia (Chemical Engineering Journal, 2024)

Effect of micro-diamond and nano-polycrystalline diamond interfacial microstructure on OLC phase transition - Lifeng Dai; Yanguo Li; Wenqi Luo; He Jia; Yongan Luo; Yanping Yang; Yufei Meng; Xin Han; Wantang Fu; Qin Zou; Yingwei Fei (Chemical Engineering Journal, 2024)

Enhancing safe and effective treatment of carbapenem-resistant Klebsiella pneumoniae with polymyxin B-loaded dendritic nanoparticles - Wen Zhong; Yuyin Fu; Xukun Liao; Na Xu; Lingyi Shen; Jinglin Wu; Dan Zheng; Yadi Zhou; Lin Tan; Binyi Xia; Xinghua Fan; Meng Zhou; et al. (Chemical Engineering Journal, 2024)

Performance and mechanism investigation of Cu loading and S vacancy synergistic promotion of MoS2 catalyzed low-temperature water gas shift reaction: Experimental and theoretical calculations - Qiang Fu; Zhiling Huang; Yue Meng; Bo Xie; Zheming Ni; Shengjie Xia (Chemical Engineering Journal, 2024)

Multifunctional and immunoregulatory microenvironment-responsive hydrogel for whole course management of infected diabetic wounds - Zhenyu Luo; Xiaoxue Fu; Hua Jiang; Weikun Meng; Shue Jin; Yongrui Cai; Ze Du; Ping Song; Anjing Chen; Li Li; Peifang Li; Jiali Chen; et al. (Chemical Engineering Journal, 2024)

A pair of cadinane-type sesquiterpene enantiomers and other chemical constituents from the whole plants of Chloranthus henryi - Meng-Li He; Lian-Lian Xu; Shi-Qin Fu; Yang Liu; Yong-Ming Luo; Fang-You Chen (Biochemical Systematics and Ecology, 2024)

Fine-mapping of a major QTL controlling plant height by BSA-seq and transcriptome sequencing in cotton - Chao Li; Longyu Huang; Yiwen Huang; Meng Kuang; Yuzhen Wu; Zhiying Ma; Xiaoqiong Fu (Theoretical and Applied Genetics, 2024)

Identification and Activity Study of an Impurity Band Observed in the nrSDS-PAGE of Aflibercept - Meng Li; Weiyu Li; Xin Wang; Gang Wu; Jialiang Du; Gangling Xu; Maoqin Duan; Xiaojuan Yu; Chunbo Cui; Chunyu Liu; Zhihao Fu; Chuanfei Yu; et al. (Pharmaceutical Research, 2024)

Prevalence of antibiotic resistance genes, heavy metal, and bacterial community composition in sea sediments influenced by Eriocheir sinensis breeding aquaculture - Hui Fu; Wei Sun; Yawei Cao; Qing Li; Xiaotong Wang; Zijie Zhou; Qian Meng; Tingyi Luo; Wei Gu; Qingguo Meng (Environmental Science and Pollution Research, 2024)

Quantitative estimation of the effective elastic thickness around the Burma Plate and correlation analysis of its influencing factors - Yawen She; Qian Zhao; Guangyu Fu; Guojie Meng; Layue Li; Myo Thant (Tectonophysics, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Acesulfame potassium triggers inflammatory bowel disease via the inhibition of focal adhesion pathway - Zhaodong Zhai; Yibo Zhang; Xujing Liang; Jingsheng Li; Zhiqi Chen; Jianbin Zhang; WeiCai Li; Teng Wang; Qianyi He; Fu Li; Qilin Meng; Jieqiong Cao; et al. (Journal of Hazardous Materials, 2024)

Experimental investigation on the turbulence flame autoignition characteristics of ammonia in a high-temperature co-flow - Meng Ji; Zhijun Wu; Alessandro Ferrari; Oscar Vento; Quanbo Shang; Guanyu Zhang; Lezhong Fu; Jun Deng; Liguang Li (Fuel, 2024)

A preliminary investigation of the effectiveness of feedback messaging on household room air conditioning usage in summer - Meng Liu; Mengshu Liang; Bingjie Huang; Zhilong Liu; Chenghao Fu; Ziqiao Li (Energy and Buildings, 2024)

The co-assembly of spike silica nanoparticles with high affinity to nucleic acid for airborne virus detection - Xue Zhang; Yamin Yu; Kaixin Du; Wenwei Han; Jie Xue; Shanshan Li; Shangyou Lv; Jianye Fu; Xin Wang; Meng Qiu (Chemical Engineering Journal, 2024)

The synergistic effect of hole co-doping on carrier transports and phonon tuning in Sb2Te3 flexible thermoelectric thin film - Meng Wei; Haobin Li; Mohammad Nisar; Zilong Zhang; Fu Li; Guangxing Liang; Jingting Luo; Zhi Zheng; Yuexing Chen; Zhuanghao Zheng (Chemical Engineering Journal, 2024)

Triggering Receptor Expressed on Myeloid Cells 2 Alleviated Sevoflurane-Induced Developmental Neurotoxicity via Microglial Pruning of Dendritic Spines in the CA1 Region of the Hippocampus - Li Deng; Shao-Yong Song; Wei-Ming Zhao; Xiao-Wen Meng; Hong Liu; Qing Zheng; Ke Peng; Fu-Hai Ji (Neuroscience Bulletin, 2024)

Dissolved Organic Matters, an Intermediary of the Microbial Community and Potassium Fertilizers in A. carmichaeli rhizosphere Soil - Fei Xia; Meng Fu; Chen Liu; Yulong Li; Yi Qiang; Ding He; Guoyan Zhang; Langjun Cui (Journal of Soil Science and Plant Nutrition, 2024)

miR-7160 inhibits gastric cancer cell proliferation and metastasis by silencing SIX1 - Meng Meng; Guoxin Guan; Xingming Liu; Wei Sun; Xinye Cui; Saiya Fu; Fuwen Luo (Journal of Genetics, 2024)

Sodium nitroprusside (SNP) generated nitric oxide delays senescence of cowpea (Vigna unguiculata (L.) Walp) - Chunmei Bai; Fan Zhang; Demei Meng; Christopher B. Watkins; Lili Ma; Anzhen Fu; Zhaoze Sang; Susu Guo; Hongwei Wang; Qing Wang; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Electroosmosis of gold tailings under multiple electrokinetic geosynthetics electrodes - Changbo Du; Ben Niu; Fu Yi; Meng Wang; Xinqi Jiang (Geotextiles and Geomembranes, 2024)

ZSM-5@Zn/ZSM-5 core@shell nanocrystals as integrated catalysts for efficient methanol conversion into aromatics - Zhuo Wang; Huiling Zheng; Fanhui Meng; Tingjun Fu; Zhong Li (Fuel, 2024)

In situ formation of solidified supramolecular solvent based dispersive liquid-liquid microextraction for the enrichment of phenylurea herbicides in water, fruit juice, and milk - Shurong Chen; Yuhao Jiang; Junxian Li; Meng You; Rongxu Zhang; Jilong Li; Zhuang Fu; Jiahan Xie; Zhibing Wang (Food Chemistry, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Upward soil arching effect under unloading: mechanism, theory and engineering application - Ren-Peng Chen; Han-Lin Wang; Xiang-Shen Fu; Fanyan Meng; Qi-Wei Liu; Xing-Tao Lin (Transportation Geotechnics, 2024)

New insights into the influences of firework combustion on molecular composition and formation of sulfur- and halogen-containing organic compounds - Caiqing Yan; Haibiao Chen; Fei Xu; Qinglong Fu; Ying Zhou; Ruizhi Zhou; Ruiyu Li; Mei Zheng; Mingjie Xie; Bin Jiang; Zhisheng Zhang; He Meng; et al. (Science of The Total Environment, 2024)

Studies of the diluent, temperature and pressure effect on the lower and upper flammability limits of ammonia in air - Wen Fu; Yulong Zhou; Jiangtao Wu; Ke Zhang; Xianyang Meng (Process Safety and Environmental Protection, 2024)

PagPXYs improve drought tolerance by regulating reactive oxygen species homeostasis in the cambium of Populus alba × P. glandulosa - Cheng Jiang; Jiawei Wang; Xinyue Fu; Chunyan Zhao; Weilin Zhang; Hesheng Gao; Chenhao Zhu; Xueqin Song; Yanqiu Zhao; Yi An; Lichao Huang; Ningning Chen; et al. (Plant Science, 2024)

Effect of polyethylene microplastics on antibiotic resistance genes: A comparison based on different soil types and plant types - Yi Li; Xinwei Shi; Meng Zeng; Peiqing Qin; Mingyue Fu; Shiyu Luo; Chijian Tang; Cuiju Mo; Fangming Yu (Journal of Hazardous Materials, 2024)

Benzo[a]pyrene evokes epithelial-mesenchymal transition and pulmonary fibrosis through AhR-mediated Nrf2-p62 signaling - Meng-Die Li; Li-Hong Chen; Hui-Xian Xiang; Ya-Lin Jiang; Bian-Bian Lv; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

The construction of Cs3MoxSbyBr9/BiVO4 S-scheme heterojunction photocatalyst for efficient photocatalytic N2 fixation - Zhao-Lei Liu; Han-Ying Luo; Meng-Ran Zhang; Yan-Fei Mu; Fu-Quan Bai; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2024)

Molecular composition and sources of free amino acids in atmospheric aerosols from Mt. Tai and a nearby city - Qingzi Zhao; Libin Wu; Xiaoli Fu; Wei Hu; Yajie Wang; Yuantao Wang; Ke Xin; Jingjing Meng; Siyao Yue; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2024)

Distribution and dynamics of niche and interspecific association of dominant phytoplankton species in the Feiyun River basin, Zhejiang, China - Shengnan Zhu; Zengchuan Dong; Guobin Fu; Shujun Wu; Jinyu Meng; Weilin Liu; Yupeng Liu; Xun Cui; Yuejiao Zhou (Journal of Oceanology and Limnology, 2024)

Reversal of gentamicin sulfate resistance in avian pathogenic Escherichia coli by matrine combined with berberine hydrochloride - Jinwu Meng; Jinxue Ding; Weiran Wang; Bolin Gu; Fanting Zhou; Desheng Wu; Xiang Fu; Jiaguo Liu (Archives of Microbiology, 2024)

Particulate matter pollution, polygenic risk score and mosaic loss of chromosome Y in middle-aged and older men from the Dongfeng-Tongji cohort study - Xin Guan; Xia Meng; Guorong Zhong; Zirui Zhang; Chenming Wang; Yang Xiao; Ming Fu; Hui Zhao; Yuhan Zhou; Shiru Hong; Xuedan Xu; Yansen Bai; et al. (Journal of Hazardous Materials, 2024)

Using Hg isotopes and trace elements to constrain the origin of the Ordovician Xiangquan Tl deposit, South China - Lei Meng; Mei-Fu Zhou; Wei Terry Chen (Journal of Asian Earth Sciences, 2024)

A geometric variation method to extract rock strength parameters via uniaxial compression testing - Zhe Li; Zhen-Qi Yang; Meng Fu; Gao-Feng Zhao (International Journal of Rock Mechanics and Mining Sciences, 2024)

Evolution of pore structure and reactive transport parameters during acid leaching of sandstone uranium ore - Shuai Wang; Meng Lian; Dexin Ding; Guicheng He; Haiying Fu (Hydrometallurgy, 2024)

The interaction effects of zinc and polygenic risk score with benzo[a]pyrene exposure on lung cancer risk: A prospective case-cohort study among Chinese populations - Ming Fu; Hua Meng; Minghui Jiang; Ziwei Zhu; Xin Guan; Yansen Bai; Chenming Wang; Yuhan Zhou; Shiru Hong; Yang Xiao; Meian He; Xiaomin Zhang; et al. (Environmental Research, 2024)

Insights into synergetic modulation of nickel sites over graphene by introducing tungsten and light for efficient methanol electrooxidation - He Xiao; Wenxiang Wang; Man Zhao; Zimei Fu; Meng Bai; Li Zhang; Junming Zhang; Ergui Luo; Jian Zhang; Haishun Wu; Jianfeng Jia (Chemical Engineering Journal, 2024)

Advances in understanding the regulation effect of carbon dots on intrinsic activity of metal and metal-free catalysts for electrocatalysis reaction - Meng Bai; Zimei Fu; Chunmei Liu; Peipei Zhao; Jiamin Ma; Wenxiang Wang; He Xiao; Junwei Wu; Man Zhao; Jianfeng Jia (Chemical Engineering Journal, 2024)

Development of a novel membrane-based quorum-quenching microbial isolator for biofouling control: Process performance and microbial mechanism - Yue Fu; Jiajie Wu; Yingxin Wu; Boyi Yang; Xiaolong Wang; Ronghua Xu; Fangang Meng (Bioresource Technology, 2024)

Recognition of mango and location of picking point on stem based on a multi-task CNN model named YOLOMS - Bin Zhang; Yuyang Xia; Rongrong Wang; Yong Wang; Chenghai Yin; Meng Fu; Wei Fu (Precision Agriculture, 2024)

Functional responses of two species of predatory mites (Acari: Phytoseiidae) to eggs and first-instar nymphs of Bactericera Gobica Logniova (Homoptera: Psyllidae) - XiaoTong Fu; YuanZhi Cao; XinTong Dong; Jing Chang; ZhiJia Huo; RuiXia Meng (Experimental and Applied Acarology, 2024)

Mycorrhizal associations relate to stable convergence in plant–microbial competition for nitrogen absorption under high nitrogen conditions - Zhenggang Du; Lingyan Zhou; Madhav P. Thakur; Guiyao Zhou; Yuling Fu; Nan Li; Ruiqiang Liu; Yanghui He; Hongyang Chen; Jie Li; Huimin Zhou; Ming Li; et al. (Global Change Biology, 2024)
Nitrogen (N) immobilization (Nim, including microbial N assimilation) and plant N uptake (PNU) are the two most important pathways of N retention in soils. The ratio of Nim to PNU (hereafter Nim:PNU ratio) generally reflects the degree of N limitation for plant growth in terrestrial ecosystems. However, the key factors driving the pattern of Nim:PNU ratio across global ecosystems remain unclear. Here, using a global data set of 1018 observations from 184 studies, we examined the relative importance of mycorrhizal associations, climate, plant, and soil properties on the Nim:PNU ratio across terrestrial ecosystems. Our results show that mycorrhizal fungi type (arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi) in combination with soil inorganic N mainly explain the global variation in the Nim:PNU ratio in terrestrial ecosystems. In AM fungi‐associated ecosystems, the relationship between Nim and PNU displays a weaker negative correlation ( r = −.06, p r = .25, p

Law of respirable dust pollution induced by cutting-advancing support in a fully mechanized mining face and spatial stereoscopic dust control and removal technology - Shuzheng Song; Gang Zhou; Biao Sun; Genru Zhou; Honglei Wei; Yunna Wang; Zhenkun Fu; Zhen Liu; Long Meng (Environment, Development and Sustainability, 2024)

Identification of SNPs and candidate genes associated with growth using GWAS and transcriptome analysis in Coilia nasus - Yue Yu; Shi-Ming Wan; Shuang-Meng Zhang; Jun-Qi Liu; Ai-Li Sun; Yao Wang; Yong-Fu Zhu; Shu-Xin Gu; Ze-Xia Gao (Aquaculture, 2024)

Optimal open nucleus breeding system for long-term genetic gain in the Pacific white shrimp using genomic selection - Ziyi Kang; Jie Kong; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Junyu Liu; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Qi Li; et al. (Aquaculture, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Anthropogenic-induced ecological risks on marine ecosystems indicated by characterizing emerging pollutants in Pearl River Estuary, China - He Liu; Bo Zhao; Meng Jin; Rui Wang; Zirong Ding; Xiong Wang; Wenjie Xu; Qianghua Chen; Rizhu Tao; Jianping Fu; Danping Xie (Science of The Total Environment, 2024)

Length-controlled hydrophobic CF3-COF as a highly efficient absorbent coating for dual-mode solid-phase microextraction of sixteen polycyclic aromatic hydrocarbons in water samples - Zirong Lan; Jin Huang; Shanliang Fu; Youwei Chen; Taoyu Meng; Wenli Zhou; Zhou Xu; Maolong Chen; Li Wen; Yunhui Cheng; Li Ding (Science of The Total Environment, 2024)

Mechanism of zinc stress on magnesium deficiency in rice plants (Oryza sativa L.): Insights from magnesium isotopes - Yucong Fu; Ting Gao; Qiqi Wu; Meng Qi; Zhengrong Wang; Chengshuai Liu (Science of The Total Environment, 2024)

Mechanical energy triggered piezo-catalyzation of Bi2WO6 nanoplates on ferrate (Fe(VI)) oxidation in alkaline media: Performance and mechanism - Jinzhe Li; Chuyun Fu; Meng Zhu; Xinwen Huang; Shuang Song; Feilong Dong (Environmental Pollution, 2024)

Probing into the radiative mechanisms and drivers influencing urban heat-cold islands and urban pollution islands during heavy-haze events in a cold megacity of Northeast China - Stephen Dauda Yabo; Lu Lu; Lixin Ma; Bo Li; Donglei Fu; Fan Meng; Jinpan Jiang; Xie Shengjin; Wei Zhang; Hong Qi (Atmospheric Research, 2024)

Assessing the Performance of a Dynamical Downscaling Simulation Driven by a Bias-Corrected CMIP6 Dataset for Asian Climate - Zhongfeng Xu; Ying Han; Meng-Zhuo Zhang; Chi-Yung Tam; Zong-Liang Yang; Ahmed M. El Kenawy; Congbin Fu (Advances in Atmospheric Sciences, 2024)

Numerical modeling of gas injection induced cracking with unsaturated hydromechanical process in the context of radioactive waste disposal - Zhan Yu; Jian-Fu Shao; Gilles Duveau; Meng Wang; Minh-ngoc Vu; Carlos Plua (Tunnelling and Underground Space Technology, 2024)

Cevanine-type alkaloids from the bulbs of Fritillaria unibracteata var. wabuensis and their antifibrotic activities in vitro - Lu Fu; Wenyue Tian; Meng-Yu Bao; Zhiyan Liu; Wen-Jing Ren; Jiazheng Liu; Wei Zhang; Zhifeng Zhang; Jin Gao; Li-Ping Bai; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Analysis of novel In2S3/polyimide Z-scheme heterojunctions with enhanced photocatalytic target compound degradation efficiency - Min Fu; Mei Yang; Jinwu Bai; Yi Li; Meng Fang; Peng Lu; Xue Kuang (Journal of Environmental Chemical Engineering, 2024)

The initial magma–fluid evolution of the Laochang porphyry molybdenum deposit in Lancang, Yunnan, SW China: Insights from the in-situ analysis of mica and titanite - Ying-Ying Zhang; Tai-Yi Luo; Yun-Fei Fan; Han-Sheng Long; Yong Yang; Jin-Biao Yang; Fu-Qing Meng (Journal of Asian Earth Sciences, 2024)

Moisture content of tea dhool for the scenting process affects the aroma quality and volatile compounds of osmanthus black tea - Xin Meng; Jie-Qiong Wang; Fang Wang; Ying Gao; Chao-Hong Fu; Qizhen Du; Zhi-Hui Feng; Jian-Xin Chen; Jun-Feng Yin; Yong-Quan Xu (Food Chemistry, 2024)

Non-volatile taste active compounds and umami evaluation of Agrocybe aegerita hydrolysates derived using different enzymes - Fan Yang; Anzhen Fu; Hongyan Meng; Ye Liu; Shuang Bi (Food Bioscience, 2024)

Exosome-functionalized heterogeneous nanofibrous scaffolds repair bone defects accompanied by muscle injury - Shue Jin; Zeyu Luo; Yongrui Cai; Jing Wen; Pengyu Lu; Xiaoxue Fu; Ping Mou; Anjin Chen; Weikun Meng; Jidong Li; Zongke Zhou; Weinan Zeng (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Interleukin-6 is correlated with amygdala volume and depression severity in adolescents and young adults with first-episode major depressive disorder - Yingying Chen; Xiaodi Xia; Zheyi Zhou; Meng Yuan; Yadong Peng; Ying Liu; Jinxiang Tang; Yixiao Fu (Brain Imaging and Behavior, 2024)

Two autophagy-related proteins, ATG5 and ATG7, from Eriocheir sinensis involved into Spiroplasma eriocheiris infection - Yu Yao; Xiang Meng; Hui Fu; Siyu Lu; Jianlong Yang; Chao Geng; Xuguang Li; Wei Gu; Jun Zhou; Qingguo Meng (Aquaculture, 2024)

Inverse effects of aerosol radiative forcing on heavy PM2.5 pollution of local accumulation and regional transport over Central China - Xiaoyun Sun; Tianliang Zhao; Jun Hu; Yongqing Bai; Lu Meng; Qingjian Yang; Yue Zhou; Weikang Fu (Science of The Total Environment, 2024)

Motility behavior and physiological response mechanisms of aerobic denitrifier, Enterobacter cloacae strain HNR under high salt stress: Insights from individual cells to populations - Meng Cheng; Hui-Min Fu; Zheng Mao; Peng Yan; Xun Weng; Teng-Fei Ma; Xiao-Wei Xu; Jin-Song Guo; Fang Fang; You-Peng Chen (Science of The Total Environment, 2024)

Devonian stratiform ironstone deposits in South China formed in a shallow marine environment of a passive continental margin - Mei-Fu Zhou; Yuanjun Jonathan Lyu; Zerui Ray Liu; Ping-Ping Liu; Lei Meng; Wenhong Johnson Qiu; Wen Winston Zhao (Journal of Asian Earth Sciences, 2024)

Tea polyphenols alleviate TBBPA-induced inflammation, ferroptosis and apoptosis via TLR4/NF-κB pathway in carp gills - Ran Xu; Fu-xin Han; Hong-ru Wang; Jing-jing Wang; Zhao-long Cai; Meng-yao Guo (Fish & Shellfish Immunology, 2024)

Exosome-shuttled FTO from BM-MSCs contributes to cancer malignancy and chemoresistance in acute myeloid leukemia by inducing m6A-demethylation: A nano-based investigation - Ruirui Kou; Tian Li; Caizhu Fu; Duanfeng Jiang; Yue Wang; Jie Meng; Ruilan Zhong; Changjiu Liang; Min Dong (Environmental Research, 2024)

Mixing state and influence factors controlling diurnal variation of particulate nitrophenol compounds at a suburban area in northern China - Ziyong Guo; Xiaodong Hu; Wei Sun; Xiaocong Peng; Yuzhen Fu; Kun Liu; Fengxian Liu; He Meng; Yujiao Zhu; Guohua Zhang; Xinfeng Wang; Likun Xue; et al. (Environmental Pollution, 2024)

A comparative study on the degradation of carbamazepine by UV laser/chlorine and UV laser/PS processes: Performance and mechanisms - Qi Fu; Xing-Xing Wang; Huan He; Tian-Yang Zhang; Jian Lu; Meng-Yuan Xu; Renjie Pan; Tong-Cheng Cao; Mohamed Gamal El-Din; Bin Xu (Chemical Engineering Journal, 2024)

Mechanical interlocking induced emission in two-dimensional covalent organic frameworks - Ruo-Meng Zhu; Wang-Kang Han; Yong Liu; Jia-Xing Fu; Jing-Dong Feng; Jinfang Zhang; Huan Pang; Zhi-Guo Gu (Chemical Engineering Journal, 2024)

Influences of conservation tillage on soil macrofaunal biodiversity and trophic structure in the Mollisol region of Northeast China - Xiaoli Liu; Jiancheng Zang; Yun Fu; Xiumei Pan; Di Meng; Yongjie Zhu; Tao Sun (CATENA, 2024)

Investigating the influence of integrated landscape connectivity on water dissolved organic carbon variations in farm pond catchments of subtropical southern China - Huanyao Liu; Cen Meng; Xiaoma Li; Hui Fu; Yi Wang; Yuyuan Li; Jinshui Wu (CATENA, 2024)

High-density bin-based genetic map reveals a 530-kb chromosome segment derived from wild peanut contributing to late leaf spot resistance - Jiaowen Pan; Xiaojie Li; Chun Fu; Jianxin Bian; Zhenyu Wang; Conghui Yu; Xiaoqin Liu; Guanghao Wang; Ruizheng Tian; Xiaofeng Song; Changsheng Li; Han Xia; et al. (Theoretical and Applied Genetics, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Interactive image segmentation based field boundary perception method and software for autonomous agricultural machinery path planning - Hao Wang; Zhifeng Ma; Yaxin Ren; Siqi Du; Hao Lu; Yehua Shang; Shupeng Hu; Guangqiang Zhang; Zhijun Meng; Changkai Wen; Weiqiang Fu (Computers and Electronics in Agriculture, 2024)

Influence of speed measurement method on performance of an electric-drive maize precision planter - Lin Ling; Guangwei Wu; Changkai Wen; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Jianhong Ding; Zhijun Meng; Bingxin Yan (Biosystems Engineering, 2024)

Coagulation/co-catalytic membrane integrated system for fouling-resistant and efficient water purification - Yun-Jie Wang; Chen-Xuan Li; Yan Meng; Zhi-Yan Guo; Shuo Cui; Xian-Zhong Fu; Hou-Qi Liu; Wen-Qi Xia; Wen-Wei Li (Water Research, 2024)

Gut microbiota dysbiosis and intestinal barrier impairment in diarrhea caused by cold drink and high-fat diet - Yajuan Tian; Meng Fu; Jie Su; Meiqiu Yan; Jingjing Yu; Chenxing Wang; Zhuangwei Niu; Yuzhong Du; Xueling Hu; Jiayi Zheng; Bai Tao; Zengguang Gao; et al. (Toxicology, 2024)

An intrusion and environmental effects of man-made silver nanoparticles in cold seeps - Kelei Zhu; Jiawei Liu; Mingyu Zhao; Lulu Fu; Zengfeng Du; Fanqi Meng; Lin Gu; Peiyu Liu; Yan Liu; Chaoqun Zhang; Xin Zhang; Jinhua Li (Science of The Total Environment, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Occurrence, seasonal variation and gas/particle partitioning of current used pesticides (CUPs) across 60 °C temperature and 30° latitudes in China - Liang Wang; Gang Cao; Zi-Feng Zhang; Li-Yan Liu; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

High-efficient nutrient removal in a single-stage electrolysis-integrated sequencing batch biofilm reactor (E-SBBR) for low C/N sanitary sewage treatment - Zhi Yang; Shuohui Shi; Xuejie He; Meng Cao; Hong Lin; Jiahao Fu; Jian Zhou (Journal of Environmental Management, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Adaptation of Glucose Metabolism to Limb Autotomy and Regeneration in the Chinese Mitten Crab - Ju Li; Xiaohong Li; Simiao Fu; Yuxuan Meng; Xiaoyan Lv; Xin Zhang; Guozheng Liu; Jinsheng Sun (Marine Biotechnology, 2024)

Seascapes Shaped the Local Adaptation and Population Structure of South China Coast Yellowfin Seabream (Acanthopagrus latus) - Wenhao Wang; Junrou Huang; Yan Hu; Jianxiang Feng; Dong Gao; Wenyu Fang; Meng Xu; Chunlei Ma; Zhenqiang Fu; Qinglong Chen; Xuanguang Liang; Jianguo Lu (Marine Biotechnology, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

A two-stage Fe(VI) oxidation process enhances the removal of bisphenol A for potential application - Feilong Dong; Chuyun Fu; Zhu Meng; Qiufeng Lin; Jinzhe Li; Tao Zeng; Da Wang; Juntao Tang; Shuang Song (Science of The Total Environment, 2024)

Accident case-driven study on the causal modeling and prevention strategies of coal-mine gas-explosion accidents: A systematic analysis of coal-mine accidents in China - Wang Yuxin; Fu Gui; Lyu Qian; Wu Jingru; Wu Yali; Han Meng; Lu Yuxuan; Xie Xuecai (Resources Policy, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Effects of polyethylene microplastics and heavy metals on soil-plant microbial dynamics - Yi Li; Xinwei Shi; Peiqing Qin; Meng Zeng; Mingyue Fu; Yuyuan Chen; Zhongkai Qin; Yamei Wu; Jialiang Liang; Shuairen Chen; Fangming Yu (Environmental Pollution, 2024)

Orbitally-paced climate change during the Carnian Pluvial Episode - Qian Zhang; Xiugen Fu; Jian Wang; Ahmed Mansour; Hengye Wei; Tan Zhang; Meng Wang (Earth and Planetary Science Letters, 2024)

Challenges and strategies of lithium-ion mass transfer in natural graphite anode - Yin Zhao; Yulong Fu; Yue Meng; Zhi Wang; Junhao Liu; Xuzhong Gong (Chemical Engineering Journal, 2024)

Hybrid nanoassembly indicating a synthetic lethality relationship induces mitotic catastrophe-mediated tumor elimination - Shunzhe Zheng; Guanting Li; Shuwen Fu; Nannan Wang; Han Qiao; Meng Li; Xuanbo Zhang; Kaiyuan Wang; Wei Sun; Chutong Tian; Zhonggui He; Defang Ouyang; et al. (Chemical Engineering Journal, 2024)

A Numerical Study of Moisture and Ionic Transport in Unsaturated Concrete by Considering Multi-ions Coupling Effect - Zhaozheng Meng; Yufei Zhang; Wei-kang Chen; Chuan-qing Fu; Qing Xiang Xiong; Cheng-lin Zhang; Qing-feng Liu (Transport in Porous Media, 2024)

Introduction of blown plate heat exchanger for cabinet cooling system - Saranmanduh Borjigin; Wang Fu; Huijie Wang; Wenlong Liang; Jianlong Ma; Keqilao Meng; Hexi Baoyin (Clean Technologies and Environmental Policy, 2024)

S-scheme MOF-on-MOF heterojunctions for enhanced photo-Fenton Cr(VI) reduction and antibacterial effects - Longyang Wang; Kejie Zhang; Jianying Qian; Mengyi Qiu; Ningyi Li; Hao Du; Xiao Hu; Yangjie Fu; Meng Tan; Derek Hao; Qi Wang (Chemosphere, 2023)

Triplex visual detection of tobacco potyviruses using reverse transcription recombinase polymerase amplification assay combined with lateral flow dipstick - Tengzhi Xu; Xingwei Lin; Xiaolian Zhang; Yong Fu; Hao Luo; Chun Luo; Zhengduo Luo; Lei Lei; Meng-ao Jia (Crop Protection, 2023)

Transcriptiomics analysis reveals immue regulation and cell death regulation of IFNg in Pelodiscus sinensis STA cells - Jianping Fu; Jun Chen; Xinyan Meng; Zhang Luo; Yi Liu; Lili Wei (Aquaculture, 2023)

Cross-regional scale studies of organochlorine pesticides in air in China: Pollution characteristic, seasonal variation, and gas/particle partitioning - Liang Wang; Gang Cao; Li-Yan Liu; Zi-Feng Zhang; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Science of The Total Environment, 2023)

Unraveling the mysteries of (L)WY-domain oomycete effectors - Hongyuan Zheng; Liyuan You; Shuaijie Meng; Daowen Wang; Zhengqing Fu (Science Bulletin, 2023)

Intelligent optimization strategy for electrochemical removal of ammonia nitrogen by neural network embedded in a non-dominated sorting genetic algorithm - Zhengwu Yang; Peng Chen; Guangyuan Meng; Xinwan Zhang; Yaqi Shi; Wenzhao Fu; Huawei Hu; Lehua Zhang (Journal of Water Process Engineering, 2023)

Comparison of the environmental impact of typical packaging systems for food cold chain express based on life cycle assessment - Teng Meng; Yinpu Wang; Lin Fu; Yuelin Wang; Na Zhang; Zhao Wang; Qi Yang (Journal of Cleaner Production, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Influence of ship emissions on PM2.5 in Shanghai: From COVID19 to OMICRON22 lockdown episodes - Yusen Duan; Meng Wang; Yin Shen; Min Yi; Qingyan Fu; Jia Chen; Guangli Xiu (Atmospheric Environment, 2023)

Polyethylene microplastics cause apoptosis via the MiR-132/CAPN axis and inflammation in carp ovarian - Meng-ran Zhu; Hong-ru Wang; Fu-xin Han; Zhao-long Cai; Jing-jing Wang; Meng-yao Guo (Aquatic Toxicology, 2023)

Global trends and focuses of GLP-1RA in renal disease: a bibliometric analysis and visualization from 2005 to 2022 - Yilin Meng; Yaqing Wang; Wenjing Fu; Mingyu Zhang; Jiayi Huang; Haoze Wu; Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Long-term application of controlled-release fertilizer enhances rice production and soil quality under non-flooded plastic film mulching cultivation conditions - Jingjie Zhou; Sheng Tang; Wankun Pan; Meng Xu; Xiu Liu; Liang Ni; Xiali Mao; Tao Sun; Haoran Fu; Kefeng Han; Qingxu Ma; Lianghuan Wu (Agriculture, Ecosystems & Environment, 2023)

A study of ionospheric anomaly detection before the August 14, 2021 Mw7.2 earthquake in Haiti based on sliding interquartile range method - Dongjie Chen; Di Meng; Fu Wang; Yanmei Gou (Acta Geodaetica et Geophysica, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Digital twin perception and modeling method for feeding behavior of dairy cows - Yi Zhang; Yu Zhang; Meng Gao; Baisheng Dai; Shengli Kou; Xinjie Wang; Xiao Fu; Weizheng Shen (Computers and Electronics in Agriculture, 2023)

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Distinct patterns of the soil and phyllosphere antibiotic resistome in natural forest ecosystems under an altitudinal gradient - Shu-Yi-Dan Zhou; Fu-Yi Huang; Wei Su; Zhiyang Lie; Yue Liu; Chenshuo Lin; Kai Yang; Ze Meng; Zhanfeng Liu; Roy Neilson; Jian-Qiang Su; Juxiu Liu (Science of The Total Environment, 2023)

Damage identification for jacket offshore platforms using Transformer neural networks and random decrement technique - Xingxian Bao; Meng Liu; Dianfu Fu; Chen Shi; Hongliang Cui; Zhengyi Sun; Zhihui Liu; Gregorio Iglesias (Ocean Engineering, 2023)

Permeability evolution and production characteristics of inclined coalbed methane reservoirs on the southern margin of the Junggar Basin, Xinjiang, China - Shun Liang; Yaowu Liang; Derek Elsworth; Qiangling Yao; Xuehai Fu; Junqiang Kang; Yisong Hao; Meng Wang (International Journal of Rock Mechanics and Mining Sciences, 2023)

Carbonate lithium isotope systematics indicate cooling triggered mass extinction during the Frasnian-Famennian transition - Yang-Yang Wang; Kun Liang; Yilin Xiao; Bo Chen; Erhao Shan; Tingyu Yang; Meng Zhang; He Sun; Hai-Ou Gu; Fengtai Tong; Lulu Fu; Dong-Yong Li; et al. (Global and Planetary Change, 2023)

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

Centrifugation forced ice-concentrate separation to enhance suspension freezing desalination performance - Jingyu Wei; Peng Chen; Yalin Pan; Zhengnan Fang; Tao Fu; Jingxian Zhang; Guangyuan Meng; Jun Zhu; Lehua Zhang (Desalination, 2023)

Development of 1D bounding surface model for lattice spring model on predicting rock failure under cyclic loading - Meng Fu; Gao-Feng Zhao (Computers and Geotechnics, 2023)

Anion-derived cathode interface engineering enables ether-based electrolytes for sodium-ion batteries - Guangxiang Zhang; Chi Ma; Chuankai Fu; Ziwei Liu; Haoquan Zhao; Meng Chen; Qingmo Shi; Hua Huo; Pengjian Zuo; Geping Yin; Yulin Ma (Chemical Engineering Journal, 2023)

Piezoelectric self-power supply driven by ferroelastic host–guest supramolecule with considerable electromechanical conversion capability - Meng-Meng Lun; Jia-Qi Luo; Zhi-Xu Zhang; Jie Li; Li-Yan Xie; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2023)

Spatial pattern of hydrological and erosion behaviour along a dolomite hillslope in Southwest China - Qingmei Meng; Sheng Wang; Zhiyong Fu; Yusong Deng; Hongsong Chen (CATENA, 2023)

Transcriptome profiling reveals multiple regulatory pathways of Tamarix chinensis in response to salt stress - Ruxia Li; Rao Fu; Meng Li; Yanjing Song; Junlin Li; Chuanjie Chen; Yinyu Gu; Xiaoyan Liang; Wenjing Nie; Lan Ma; Xiangyu Wang; Haiyang Zhang; et al. (Plant Cell Reports, 2023)

Emerging technologies for advancing microalgal photosynthesis and metabolism toward sustainable production - Jingyan Hu; Weizhao Meng; Yixi Su; Cheng Qian; Weiqi Fu (Frontiers in Marine Science, 2023)
Microalgae are unicellular photosynthetic microorganisms that play a vital role in primary production and have diverse applications in various industries. They have high photosynthetic and metabolic capacities and can produce a variety of valuable metabolites, such as lipids, carbohydrates, pigments, and proteins. However, practical applications of microalgae are limited to high-value products due to the high production costs. Algal biotechnology faces challenges such as low energy utilization efficiency and product yield that are currently inadequate to fulfill commercial production. To overcome these challenges, emerging technologies have shown promise to achieve higher production efficiency, including molecular manipulation of photosynthetic efficiency and metabolic activities. Here, we provided an overview of the importance, diversity, and photosynthesis of microalgae, as well as strategies for enhancing their photosynthetic efficiency. We discussed various approaches for improving microalgal photosynthesis, including strain selection and optimization, rational genetic modification, and innovative technologies such as spectral recomposition of light, nanomaterials, advanced cultivation systems, and symbiotic systems. Additionally, we summarized metabolic engineering strategies that focus on optimizing the synthesis of value-added metabolites, such as pigments, long-chain polyunsaturated fatty acids, starch, proteins, and hydrogen in microalgae. By concentrating on improving photosynthetic efficiency and the synthesis of bioactive metabolites, this review provided valuable insights into enhancing microalgae production yields. Overcoming limitations in microalgae production costs can lead to broader applications in various industries. Furthermore, we highlight the potential of these strategies in increasing the efficiency of microalgae as a sustainable source for high-value products.

Development and testing of a ground recognition system for tractor field operations - Chang-kai Wen; Hong-wei Wang; Chang-hai Luo; Wei-qiang Fu; Qing-zhen Zhu; Yan-xin Yin; Zhi-jun Meng (Computers and Electronics in Agriculture, 2023)

Effect of chlorine disinfectant influx on biological sewage treatment process under the COVID-19 pandemic: Performance, mechanisms and implications - Chenyuan Dang; Yibo Zhang; Maosheng Zheng; Qiyue Meng; Jia Wang; Yuening Zhong; Zhenbing Wu; Bingchuan Liu; Jie Fu (Water Research, 2023)

Unlocking the potential of Dongting Lake-grown Miscanthus lutarioriparius biomass: A comprehensive quality analysis and bioproduct application study - Qiang Xu; Shenglan Wu; Tongcheng Fu; Yi Xu; Sai Yang; Meng Li; Zili Yi; Shuai Xue (Science of The Total Environment, 2023)

The development of cataclastic bands in high-porosity sandstones: Insights from ring shear experiments - Mingming Jiang; Yejun Jin; Xiaofei Fu; Haixue Wang; Lingdong Meng (Journal of Structural Geology, 2023)

Role of garbage classification in air pollution improvement of a municipal solid waste disposal base - Song Gao; Lingning Meng; Xiang Ge; Yuewu Li; Yong Yang; Yusen Duan; Qingyan Fu; Shuwei Zhang; Xuechun Yang; Weiliang Fei; Zheng Jiao (Journal of Cleaner Production, 2023)

Construction of facet orientation-supported Z-scheme heterojunction of BiVO4 (110)-Fe2O3 and its photocatalytic degradation of tetracycline - Qiang Fu; Yue Meng; Yiyang Yao; Hui Shen; Bo Xie; Zheming Ni; Shengjie Xia (Journal of Environmental Chemical Engineering, 2023)

Design of Ag@ZnO@Ti3C2 MXene heterojunction photocatalyst for enhanced photocatalytic degradation activity of methylene blue and levofloxacin under visible light irradiation - Wenqiang Liu; Meng Zhou; Heqing Fu (Journal of Environmental Chemical Engineering, 2023)

Impact of wild fish faeces to deep sea dissolved organic carbon as revealed by laboratory incubations - Zhuo-Yi Zhu; Fu-Tao Fang; Shipan Hossen; Yuan Zhao; Zuo-Zhi Chen; Cong Zeng; Meng Zhou (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Degradation of ofloxacin by high-efficiency almond shell-based biochar via peroxymonosulfate activation: A study of the effect of pore structure - Yi-meng Huang; Fu-zhi Huang; Bing-jun Dong; Xiao-qiang Cao; Ya-nan Shang; Xing Xu (Chemical Engineering Journal, 2023)

Phase-modulated built-in electric field to boost photogenerated electron migration for efficient dehalogenation - Meng Ren; Pengjie Zhao; Xinping Fu; Meng Liu; Yuting Ning; Yinjie Zhang; Chunyan Wang; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

The overlooked carbonate radical in micropollutant degradation: An insight into hydration interaction - Ruiyang Xiao; Yunxiang Meng; Yifu Fu; Stanisław Wacławek; Zongsu Wei; Richard Spinney; Dionysios D. Dionysiou; Weizhi Zeng; Wei–Ping Hu (Chemical Engineering Journal, 2023)

Accelerated verification method for the reliability of the motor drive mechanism of the corn precision seed-metering device - Changkai Wen; Jing Zhang; Kan Zheng; Hanqing Li; Lin Ling; Zhijun Meng; Weiqiang Fu; Bingxin Yan (Computers and Electronics in Agriculture, 2023)

Mechanism of microbial inhibition of rainfall erosion in black soil area, as a soil structure builder - Zhaoxing Xiao; Renjie Hou; Tianxiao Li; Fanxiang Meng; Qiang Fu; Mo Li; Dong Liu; Yi Ji; Shuqi Dong (Soil and Tillage Research, 2023)

Variations of PM2.5-bound elements and their associated effects during long-distance transport of dust storms: Insights from multi-sites observations - Qingpeng Meng; Caiqing Yan; Ruiyu Li; Tianle Zhang; Mei Zheng; Yue Liu; Miao Zhang; Guixia Wang; Yuming Du; Chunlin Shang; Peng Fu (Science of The Total Environment, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Do carbon neutrality initiatives affect the shareholder value of firms? Evidence from China - Tingting Li; Xiangrui Meng; Fu Jia; Lujie Chen; Liukai Wang (Journal of Cleaner Production, 2023)

The complexes of soybean protein isolate and procyanidin B2 have synergistic hypolipidemic activity at the cellular level by activating the AMPKα pathway - Lei Ji; Hongling Fu; Yi Wang; Jiaxin Li; Xiaoqing Yang; Hao Gong; Xiangze Meng; Wendan Jing; Weichang Dai; Youbao Li; Bo Lyu; Hansong Yu (Food Chemistry, 2023)

A top-down deep learning model for predicting spatiotemporal dynamics of groundwater recharge - Xin Huang; Lei Gao; Nan Zhang; Russell S. Crosbie; Long Ye; Jian Liu; Zhaoxia Guo; Qinghua Meng; Guobin Fu; Brett A. Bryan (Environmental Modelling & Software, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

Large‐scale exploration of nitrogen utilization efficiency in Asia region for rice crop: Variation patterns and determinants - Yuming Sun; Limin Gao; Xusheng Meng; Jian Huang; Junjie Guo; Xuan Zhou; Guohai Fu; Yang Xu; Leslie G. Firbank; Min Wang; Ning Ling; Xumeng Feng; et al. (Global Change Biology, 2023)
Improving rice nitrogen utilization efficiency (NUtE) is imperative to maximizing future food productivity while minimizing environmental threats, yet knowledge of its variation and the underlying regulatory factors is still lacking. Here, we integrated a dataset with 21,571 data compiled by available data from peer‐reviewed literature and a large‐scale field survey to address this knowledge gap. The overall results revealed great variations in rice NUtE, which were mainly associated with human activities, climate conditions, and rice variety. Specifically, N supply rate, temperature, and precipitation were the foremost determinants of rice NUtE, and NUtE responses to climatic change differed among rice varieties. Further prediction highlighted the improved rice NUtE with the increasing latitude or longitude. The indica and hybrid rice exhibited higher NUtE in low latitude regions compared to japonica and inbred rice, respectively. Collectively, our results evaluated the primary drivers of rice NUtE variations and predicted the geographic responses of NUtE in different varieties. Linking the global variations in rice NUtE with environmental factors and geographic adaptability provides valuable agronomic and ecological insights into the regulation of rice NUtE.

Seismicity characteristics of secondary faults in the Zhangjiakou-Bohai tectonic zone - Jin-Meng Bi; Fu-Yang Cao; Ling-Qin Meng (Applied Geophysics, 2023)

Effect of aeration/micro-aeration on lignocellulosic decomposition, maturity and seedling phytotoxicity during full-scale biogas residues composting - Xingyao Meng; Qingping Wang; Xixi Zhao; Yafan Cai; Jingyi Fu; Mingcheng Zhu; Xuguang Ma; Pan Wang; Rufei Liu; Yongjing Wang; Wei Liu; Lianhai Ren (Waste Management, 2023)

Hydrothermal conversion of hydrocarbons to heterocyclic compounds by geological supercritical CO2 volatiles - Quanyou Liu; Huiyuan Xu; Zhijun Jin; Dongya Zhu; Qingqiang Meng; Xiaoqi Wu; Qi Fu; Simon C. George (Science Bulletin, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Integrative Bioinformatics Analysis of mRNA Expression Profiles of Mice to Explore the Key Genes Involved in Crim1 Mutation-Induced Congenital Cataracts - Ziran Zhang; Fanke Meng; Jing Zhou; Zhihan Zhang; Xiaotian Liang; Meijun Meng; Guoguo Yi; Min Fu (Biochemical Genetics, 2023)
Crim1 has been implicated in cataracts in mice and is of great importance in the development of the eye in both humans and mice. Therefore, we aimed to clarify how Crim1 mutations affect lens development and the molecular mechanism of cataracts in mice through comprehensive bioinformatics analysis. The microarray chip was downloaded from the GEO database to obtain the gene expression profile data set. Differentially expressed genes (DEGs) were screened using the limma package. GO and KEGG analyses of DEGs were performed using the DAVID database. Then, we established the protein–protein interaction (PPI) network in Cytoscape. Next, we used MCODE to analyze the data. We obtained 750 DEGs in total, including 407 upregulated DEGs and 343 downregulated DEGs. GO analysis showed that the DEGs were mainly related to biological processes, such as apoptosis, cell translation and the immune system. KEGG analysis showed that the enriched functions and pathways were related to the processing and presentation of ribosomes, lysosomes, and antigens. We identified 18 HUB genes, among which four core genes, C1qa, C1qb, C1qc, and Cd74, were closely related to congenital cataracts induced by Crim1 mutation. This study reveals the molecular pathogenesis of congenital cataracts induced by Crim1, and this information is expected to facilitate clinical genetic testing, molecular diagnosis, prognosis, and individualized chemotherapy for congenital cataracts (CC).

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Supplementation with Akkermansia muciniphila improved glucose metabolism disorder in common carp (Cyprinus carpio L.) - Guokun Yang; Aixia Jiang; Huimin Cai; Fu You; Shengkui Wu; Yanmin Zhang; Xindang Zhang; Yawei Shen; Xulu Chang; Wenpan Hu; Keke Li; Xiaolin Meng (Aquaculture, 2023)

Effect of non-simultaneous movement of adjacent twin-trapdoor on soil arching effect through discrete-element method simulation - Ren-Peng Chen; Xiang-Shen Fu; Qi-Wei Liu; Han-Lin Wang; Fanyan Meng (Transportation Geotechnics, 2023)

Bifunctional reduced graphene oxide/polyelectrolyte/NiFe layered double hydroxide composites for efficient catalyzed dephosphorylation and 4-nitrophenol reduction - Zijun Xie; Bo Sun; Hongying Lin; Meng Fu; Yi Zhang; Zequn Ma; Xiangming Li (Journal of Water Process Engineering, 2023)

Occurrence, distribution, and risk assessment of quinolone antibiotics in municipal sewage sludges throughout China - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Hazardous Materials, 2023)

Electrochemical catalyst 4-Acetamido-TEMPO oxidation degumming of scutched flax tow (SFT): Promoting of lignin depolymerization and restraining of cellulose degradation - Chaoran Meng; Jingxia Ma; Xianglan Qu; Jiajia Fu (Journal of Cleaner Production, 2023)

Identify nitrogen transport paths and sources contribution in karst valley depression area using isotopic approach - Meng Lu; Fu-Jun Yue; Xiao-Dan Wang; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Journal of Environmental Management, 2023)

Sponge-like, semi-interpenetrating self-sensory hydrogel for smart photothermal-responsive soft actuator with biomimetic self-diagnostic intelligence - Xingchen Cui; Zhezhi Liu; Bing Zhang; Xiaoduo Tang; Fuqiang Fan; Yu Fu; Junhu Zhang; Tieqiang Wang; Fanbao Meng (Chemical Engineering Journal, 2023)

Laser-induced microtextured stators coupling with flexible rotors for low-voltage driving rotational piezoelectric motors - Yanhu Zhang; Xuefei Duan; Ji Zhou; Hao Fu; Xiankai Meng; Bao Liu; Jinghu Ji; Xijun Hua; Yonghong Fu; Dan Luo (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Lactiplantibacillus plantarum: A comprehensive review of its antifungal and anti-mycotoxic effects - Qianqian Li; Xiangquan Zeng; Hailong Fu; Xiaomei Wang; Xiaojun Guo; Meng Wang (Trends in Food Science & Technology, 2023)

Restoring force model of hollow prefabricated square pier with grouted sleeves connection and high-strength steel bars - Tao Fu; Zhixin Zhu; Yan Li; Longwei Xu; Yue Sun; Yuanhui Sun; Lingxiao Meng; Zhonghua Sun (Soil Dynamics and Earthquake Engineering, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Unique ion rectifier intermediate enabled by ultrathin vermiculite sheets for high-performance Zn metal anodes - Jianwen Li; Shuang Zhou; Xinyu Meng; Yining Chen; Chunyan Fu; Alireza Azizi; Xiaoguang Zhao; Weimin Xie; Zhi Chang; Anqiang Pan (Science Bulletin, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

The strong interaction and confinement effect of Ag@NH2-MIL-88B for improving the conversion and durability of photocatalytic Cr(VI) reduction in the presence of a hole scavenger - Qi Wang; Longyang Wang; Shuzhen Zheng; Meng Tan; Lingxuan Yang; Yangjie Fu; Qiang Li; Hao Du; Guoxiang Yang (Journal of Hazardous Materials, 2023)

A coupled electrochemical process for schwertmannite recovery from acid mine drainage: Important roles of anodic reactive oxygen species and cathodic alkaline - Ziyuan Huang; Huanxin Ma; Chengshuai Liu; Fangyuan Meng; Jyh-Fu Lee; Yu-Jung Lin; Xiaoyun Yi; Zhi Dang; Chunhua Feng (Journal of Hazardous Materials, 2023)

Changes in flavors profiles of stewed bone-in lamb loin during cooking by DHS/GC-MS combined with electronic bionic systems - Qianrong Wu; Mingwu Zang; Shouwei Wang; Bing Zhao; Shunliang Zhang; Su Li; Xiaoqian Pan; Meng Liu; Xiaohang Fu (Food Bioscience, 2023)

Gastrointestinal digestion fates of lipids based on pH-stat and Caco-2 cells models: Superior bioavailability of triglyceride monomer derived from silkworm pupae oil - Cheng-Hai Yan; Xiao-Meng Xun; Richard A. Herman; Yu-Fan Zhan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Bioscience, 2023)

An oral nano-antioxidant for targeted treatment of inflammatory bowel disease by regulating macrophage polarization and inhibiting ferroptosis of intestinal cells - Jing Yang; Yunhao Bai; Shuilin Shen; Xinyue Tao; Chengyu Ma; Bowen Fu; Qihao Dai; Jian Wu; Zhengjie Meng; Qingmin Sun; Xueming Li; Hao Ren (Chemical Engineering Journal, 2023)

In Silico Genome-Wide Mining and Analysis of Terpene Synthase Gene Family in Hevea Brasiliensis - Jiahao Liang; De Wang; Xin Li; Weiwen Huang; Chun Xie; Minghui Fu; Hongmei Zhang; Qiong Meng (Biochemical Genetics, 2023)

Relationship between bisphenol A and the cardiovascular disease metabolic risk factors in American adults: A population-based study - Mingcong Chen; Yang Yang; Krishna Baral; Yicheng Fu; Yang Meng; Yang Zhang; Fang Sun; Mingyi Zhao (Chemosphere, 2023)

The positive roles of influent species immigration in mitigating membrane fouling in membrane bioreactors treating municipal wastewater - Ronghua Xu; Wentian Zhang; Yue Fu; Fuqiang Fan; Zanmin Zhou; Jincan Chen; Wanli Liu; Fangang Meng (Water Research, 2023)

Exploring the seasonality of surface urban heat islands using enhanced land surface temperature in a semi-arid city - Liying Han; Linlin Lu; Peng Fu; Chao Ren; Meng Cai; Qingting Li (Urban Climate, 2023)

Discovery of novel HPPD inhibitors: Virtual screening, molecular design, structure modification and biological evaluation - Xin-Yu Leng; Shuang Gao; Yi-Fan Ma; Li-Xia Zhao; Meng Wang; Fei Ye; Ying Fu (Pesticide Biochemistry and Physiology, 2023)

A 209,000-year-old history of methane seepage activity controlled by multiple factors in the South China Sea - Ganglan Zhang; Jun Cao; Yinan Deng; Hongfei Lai; Xuexiao Jiang; Yunxin Fang; Zenggui Kuang; Shengxiong Yang; Qianyong Liang; Piaoer Fu; Tiantian Sun; Meng Jin; et al. (Marine and Petroleum Geology, 2023)

Effects of Torulaspora delbrueckii co-fermented with Saccharomyces cerevisiae on physicochemical and aromatic profiles of blueberry fermented beverage - Yu Wang; Xiao-Yan Qi; Yu Fu; Qi Zhang; Xiao-Han Wang; Meng-Yao Cui; Ying-Ying Ma; Xue-Ling Gao (Food Chemistry, 2023)

The effects of pulsed electric fields treatment on the structure and physicochemical properties of dialdehyde starch - Ying Li; Jin-Hua Wang; Yu Han; Fu-Hao Yue; Xin-An Zeng; Bo-Ru Chen; Man-Qin Zeng; Meng-Wai Woo; Zhong Han (Food Chemistry, 2023)

Taurine reduces apoptosis mediated by endoplasmic reticulum stress in islet β-cells induced by high-fat and -glucose diets - Dongdong Zhao; Xiaozhou Zhang; Yongxin Bian; Lu Meng; Yutong Wu; Yidi Ma; Chen Li; Jingjing Wang; Zizheng Fu; Jingyuan Dai; Deqi Yin; Shumei Lin; et al. (Food and Chemical Toxicology, 2023)

Construction of bubbles enrichment sites and gas-diffusion-microchannel to assist Cr(VI) electrochemical reduction in a flow-through electrochemical system - Chen Peng; Zhang Xinwan; Meng Guangyuan; Fu Tao; Xue Yuanyuan; Wang Zhiwei; Song Pengfei; Zhang Lehua; Liu Haifeng (Chemical Engineering Journal, 2023)

Downscaling algorithms for annual TRMM data based on climatic and orographic variables over the Qinling Mountains, China - Qing Meng; Ranjan Sarukkalige; Guobin Fu; Guan Wang; Wenhao Jia; Zhuang Liu; Hongying Bai; Xiaobang Peng; Shanhong Zhang (Theoretical and Applied Climatology, 2023)

An enhanced tilted-angle acoustic tweezer for mechanical phenotyping of cancer cells - Hanlin Wang; Joe Boardman; Xiaoyan Zhang; Chao Sun; Meng Cai; Jun Wei; Zhiqiang Dong; Mingqian Feng; Dongfang Liang; Sheng Hu; Yu Qian; Shuang Dong; et al. (Analytica Chimica Acta, 2023)

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

Age and composition of Neoproterozoic diabase dykes in North Altyn Tagh, northwest China: implications for Rodinia break-up - Yanguang Li; Shuguang Song; Xiaoyong Yang; Zi-Fu Zhao; Jinlong Dong; Xiaofeng Gao; Michael T.D. Wingate; Chao Wang; Meng Li; Mengqi Jin (International Geology Review, 2023)

Knockdown of Sly-miR160a using short tandem target mimic (STTM) enhanced expression of auxin signaling genes and delayed postharvest ripening of tomato fruit - Francine Ngaffo Mekontso; Shuhui Wu; Ruizuo Fu; Wen Li; Lanhuan Meng; Qing Wang; Jiangkuo Li; Hongmiao Song; Xiangbin Xu (Postharvest Biology and Technology, 2023)

Source identification of PCBs in Antarctic air by compound-specific isotope analysis of chlorine (CSIA-Cl) using HRGC/HRMS - Pu Wang; Wenying Meng; Weiwei Zhang; Min Fu; Yingming Li; Ruiqiang Yang; Qinghua Zhang; Guibin Jiang (Journal of Hazardous Materials, 2023)

PDINH bridged NH2-UiO-66(Zr) Z-scheme heterojunction for promoted photocatalytic Cr(VI) reduction and antibacterial activity - Shuzhen Zheng; Hao Du; Lingxuan Yang; Meng Tan; Ningyi Li; Yangjie Fu; Derek Hao; Qi Wang (Journal of Hazardous Materials, 2023)

Free energy regulation and domain engineering of BaTiO3-NaNbO3 ceramics for superior dielectric energy storage performance - Wenrong Xiao; Zhen Liu; Chao Zhang; Zhanming Dou; Baoyan Fan; Meng Shen; Ying Yang; Wei Luo; Kanghua Li; Qiuyun Fu; Shenglin Jiang; Yaojin Wang; et al. (Chemical Engineering Journal, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Usage behavior characteristics of household air-conditioners during the extremely hot summer – A case study of Chongqing - Longkang Dai; Ziqiao Li; Xiaoyi Chen; Yingxian Zhai; Chenghao Fu; Zhilong Liu; Meng Liu (Building and Environment, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Loss of SUN1 function in spermatocytes disrupts the attachment of telomeres to the nuclear envelope and contributes to non-obstructive azoospermia in humans - Qingxia Meng; Binbin Shao; Dan Zhao; Xu Fu; Jiaxiong Wang; Hong Li; Qiao Zhou; Tingting Gao (Human Genetics, 2023)

Protein engineering of invertase for enhancing yeast dough fermentation under high-sucrose conditions - Yijin Zhao; Kaiwen Meng; Jinyu Fu; Shijie Xu; Guang Cai; Geng Meng; Jens Nielsen; Zihe Liu; Yueping Zhang (Folia Microbiologica, 2023)

Synergistic interactions of fine particles and radiative effects in modulating urban heat islands during winter haze event in a cold megacity of Northeast China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Lixin Ma; Xiaofei Shi; Lu Lu; Xie Shengjin; Fan Meng; Jinpan Jiang; Wei Zhang; Hong Qi (Environmental Science and Pollution Research, 2023)

Assessing accuracy of genomic breeding values of selection candidates under biosecurity restrictions by progeny testing in Chinese shrimp Fenneropenaeus chinensis - Mianyu Liu; Ping Dai; Jie Kong; Xianhong Meng; Juan Sui; Kun Luo; Baolong Chen; Qiang Fu; Baoxiang Cao; Jiawang Cao; Sheng Luan (Aquaculture, 2023)

Photoinduced transformation of ferrihydrite in the presence of aqueous sulfite and its influence on the repartitioning of Cd - Jinwen Qiu; Xiaokang Hou; Yuan Ren; Chengshuai Liu; Fangyuan Meng; Jyh-Fu Lee; Yu-Jung Lin; Ziyuan Huang; Huanxin Ma; Zhenqing Shi; Chunhua Feng (Water Research, 2023)

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Enhancing the effect of biochar ageing on reducing cadmium accumulation in Medicago sativa L - Xin-Yu Zhao; Zhuo-Yun Zhang; Yu-Meng Huang; Fu-Juan Feng (Science of The Total Environment, 2023)

A new phase of treasure hunting in plant genebanks - Guangwei Li; Zhiyong Wang; Yuxuan Meng; Zheng Qing Fu; Daowen Wang; Kunpu Zhang (Molecular Plant, 2023)

Heavy-metal resistant bio-hybrid with biogenic ferrous sulfide nanoparticles: pH-regulated self-assembly and wastewater treatment application - Xian-Zhong Fu; Jie Wu; Jie Li; Jian Ding; Shuo Cui; Xue-Meng Wang; Yun-Jie Wang; Hou-Qi Liu; Xin Deng; Dong-Feng Liu; Wen-Wei Li (Journal of Hazardous Materials, 2023)

Insights into the high performance of Co–Mn oxide supported by carbon fiber frameworks for ciprofloxacin oxidation process - Wen-Xin Fu; Meng-Zhu Qin; Huai-Yuan Niu; Qi-Yao Hu; Duan Guo; Ming-Ming Chen; Cheng-Gang Niu; Da-Wei Huang (Journal of Cleaner Production, 2023)

Sourdough yeast-bacteria interactions results in reduced immunogenicity by increasing depolymerization and hydrolysis of gluten - Wenhui Fu; Xin Jia; Chenglong Liu; Xiao Meng; Ke Zhang; Sha Tao; Wentong Xue (Innovative Food Science & Emerging Technologies, 2023)

Corrigendum to “Limited hydrolysis of glycosylated whey protein isolate ameliorates the oxidative and physical stabilities of conjugated linoleic acid oil-in-water emulsions” [Food Chem. 362 (2021)130212] - Meng Li; Rui Yu; Runxiao Fu; Yanting He; Zhanmei Jiang; Juncai Hou (Food Chemistry, 2023)

Discovery of natural polyphenols from the wild vegetable Suaeda salsa L. with potential cardioprotective functions - Kuo Xu; Xinhai Cui; Xia Ren; Jie Meng; Xianjun Fu; Qing Xia (Food Chemistry, 2023)

Molecular identification and functional analysis of X-linked inhibitor of apoptosis -associated factor-1 (XAF1) in grass carp, Ctenopharyngodon idella - Jianping Fu; Jun Chen; XinYan Meng; Zhang Luo; Yi Liu; Lili Wei (Fish & Shellfish Immunology, 2023)

Assessing the impact of rockfall on a bridge by using hybrid DEM/FEM analysis: A case study in Central Taiwan - Terry Y.P. Yuen; Meng-Chia Weng; Yu-Yao Fu; Guan-Ting Lu; Wen-Jie Shiu; Cheng-An Lu; Chun-Yuan Liu; Chia-Chi Chiu; Tzu-Han Wen (Engineering Geology, 2023)

Carbonized waste polyphenylene sulfide non-woven decorated wood evaporator for clean water production from solar photothermal desalination - Lu Fu; Xiang Zhou; Liumi Deng; Meng Liao; Shaohua Chen; Hua Wang; Luoxin Wang (Desalination, 2023)

Selenium Deficiency Caused Fibrosis as an Oxidative Stress-induced Inflammatory Injury in the Lungs of Mice - Yu-xin Fu; Yi-bo Wang; Qing-wei Bu; Meng-yao Guo (Biological Trace Element Research, 2023)

Activity characteristics of significant earthquake swarms in the Bohai Rim region - Jin-Meng Bi; Cheng Song; Fu-Yang Cao (Applied Geophysics, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Associations between multiple metals exposure and biological aging: Evidence from the Dongfeng-Tongji cohort - Chenming Wang; Shiru Hong; Xin Guan; Yang Xiao; Ming Fu; Hua Meng; Yue Feng; Yuhan Zhou; Qiang Cao; Fangfang Yuan; Chenliang Liu; Guorong Zhong; et al. (Science of The Total Environment, 2023)

Internal flow effect on the coupled CF and IL VIVs of a flexible marine riser subject to a uniform current - Guixin Zhao; Shuai Meng; Chidong Che; Shixiao Fu (Ocean Engineering, 2023)

Intracellularly-photosensitized bio-hybrid with biogenic quantum dots for enhanced wastewater denitrification - Shuo Cui; Yang Si; Xian-Zhong Fu; Hui-Hui Li; Xue-Meng Wang; Wen-Zheng Du; Lang Teng; Ru-Li He; Hou-Qi Liu; Ruquan Ye; Wen-Wei Li (Chemical Engineering Journal, 2023)

Geraniin targeting CaMKK2 inhibits lipid accumulation in 3T3-L1 adipocytes by suppressing lipogenesis - Ji Li; Xuedong Wang; Xiangyu Meng; Xin Zhou; Han Huang; Yi Feng; Yujie Fu; Xinxin Liu; Bo Yu (Chemico-Biological Interactions, 2023)

Exosomes from human urine-derived stem cells carry NRF1 to alleviate bladder fibrosis via regulating miR-301b-3p/TGFβR1 pathway - Junwei Wu; Xinxin Wang; Guoping Fu; Yiyuan Feng; Yan Wang; Guoxian Zhang; Yudong Wu; Lirong Zhang; Hongyu Meng; Jianguo Wen; Bing Zhang; Qingwei Wang (Molecular and Cellular Biochemistry, 2023)

Microbial functional communities and the antibiotic resistome profile in a high-selenium ecosystem - Yanmei Sun; Jia Guo; Fu Wei; Xiaohui Chen; Meng Li; Chao Li; Size Xia; Guangming Zhang; Wencai You; Xin Cong; Tian Yu; Shiwei Wang (Chemosphere, 2023)

The effect of nitrite and nitrate treatment on growth performance, nutritional composition and flavor-associated metabolites of grass carp (Ctenopharyngodon idella) - Jun-Ming Zhang; Bing Fu; Yi-chao Li; Jin-Hui Sun; Jun Xie; Guang-Jun Wang; Jing-Jing Tian; Gen Kaneko; Er-Meng Yu (Aquaculture, 2023)

Clostridium butyricum-fermented Chinese herbal medicine enhances the immunity by modulating the intestinal microflora of largemouth bass (Micropterus salmoides) - Xiaolin Meng; Huimin Cai; Heng Li; Fu You; Aixia Jiang; Wenpan Hu; Keke Li; Xindang Zhang; Yanmin Zhang; Xulu Chang; Guokun Yang; Zhigang Zhou (Aquaculture, 2023)

Uranium capture by a layered 2D/2D niobium phosphate/holey graphene architecture via an electro-adsorption and electrocatalytic reduction coupling process - Yun Liao; Ruilin Lei; Xiaofang Weng; Chuan Yan; Jiaxi Fu; Guoxing Wei; Chen Zhang; Meng Wang; Hongqing Wang (Journal of Hazardous Materials, 2023)

The source distribution and seasonal discrepancies of antibiotic resistance genes among multiple environment media in a cold megacity - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Cleaner Production, 2023)

Metal-organic framework-derived one-dimensional Pd@CeO2 catalysts with enhanced activity for methane oxidation - Mingwei Wu; Meng Miao; Wenzhi Li; Xia Zhang; Lulu Zhang; Taimin Zhen; Yan Fu; Jingting Jin; Liang Yuan (Fuel, 2023)

The heated-induced gelation of soy protein isolate at subunit level: Exploring the impacts of α and α′ subunits on SPI gelation based on natural hybrid breeding varieties - Hongling Fu; Jiaxin Li; Xiaoqing Yang; Mohammed Sharif Swallah; Hao Gong; Lei Ji; Xiangze Meng; Bo Lyu; Hansong Yu (Food Hydrocolloids, 2023)

Effects of haloxyfop-p-methyl on the developmental toxicity, neurotoxicity, and immunotoxicity in zebrafish - Yi Liu; Jing Guo; Wenjin Liu; Fengjie Yang; Yunyun Deng; Yunlong Meng; Bo Cheng; Jianping Fu; June Zhang; Xinjun Liao; Lili Wei; Huiqiang Lu (Fish & Shellfish Immunology, 2023)

Improving tea (Camellia sinensis) quality, economic income, and environmental benefits by optimizing agronomic nitrogen efficiency: A synergistic strategy - Sheng Tang; Haoran Fu; Wankun Pan; Jingjie Zhou; Meng Xu; Kefeng Han; Kaijun Chen; Qingxu Ma; Lianghuan Wu (European Journal of Agronomy, 2023)

Multiple metals exposure and blood mitochondrial DNA copy number: A cross-sectional study from the Dongfeng-Tongji cohort - Ming Fu; Chenming Wang; Shiru Hong; Xin Guan; Hua Meng; Yue Feng; Yang Xiao; Yuhan Zhou; Chenliang Liu; Guorong Zhong; Yingqian You; Tianhao Wu; et al. (Environmental Research, 2023)

Physiological and affective responses to green space virtual reality among pregnant women - Yi Sun; Fu Li; Tao He; Yaohan Meng; Jie Yin; Ilona S. Yim; Liyan Xu; Jun Wu (Environmental Research, 2023)

Fabrication of wide-spectra-responsive NA/NH2-MIL-125(Ti) with boosted activity for Cr(VI) reduction and antibacterial effects - Yangjie Fu; Meng Tan; Zhonglu Guo; Derek Hao; Youran Xu; Hao Du; Chao Zhang; Jiayun Guo; Qiang Li; Qi Wang (Chemical Engineering Journal, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Cymbopogom Citratus Essential Oils: A Promising Source of Antifungals Against Panax Notoginseng-Associated Pathogenic Fungi - Jing Yang; Tian T. Li; Ying Y. Huo; Heng Y. Huang; Qing H. Meng; Fu R. Xu; Xian Dong (Current Microbiology, 2023)

Rapid frequency transfer by BDS-3/GPS PPP with tropospheric augmentation - Dong Zhang; Chuang Shi; Fu Zheng; Meng Wang (GPS Solutions, 2023)

The diversity and structure of diazotrophic communities in the rhizosphere of coastal saline plants is mainly affected by soil physicochemical factors but not host plant species - Yanjing Song; Lan Ma; Haiyang Zhang; Rao Fu; Xiaoyan Liang; Junlin Li; Jiajia Li; Meng Li; Yan Shan; Jieshan Cheng; Xiangyu Wang; Hongxia Zhang (Frontiers in Marine Science, 2022)
The diversity and community structure of rhizospheric microbes are largely affected by soil physicochemical properties and plant species. In this work, high throughput sequencing and quantitative real-time PCR targeting nifH gene were used to assess the abundance and diversity of diazotrophic community in the coastal saline soils of Yellow River Delta (YRD). We demonstrated that the copy number of nifH gene encoding the Fe protein subunit of the nitrogenase in the nitrogen fixation process was significantly affected by soil physiochemical factors, and the abundance of diazotrophs in the rhizospheric soil samples collected from different locations was positively related with soil physicochemical properties. Soil salinity ( P =0.003) and moisture ( P =0.003) were significantly co-varied with the OTU-based community composition of diazotrophs. Taxonomic analysis showed that most diazotrophs belonged to the Alphaproteobacteria , Gammaproteobacteria and Deltaproteobacteria . Linear discriminant analysis (LDA) effect size (LEfSe) and canonical correspondence analysis (CCA) showed that diazotrophic community structure significantly varied with soil salinity, moisture, pH and total nitrogen, carbon, sulphur and nitrite (NO 2 – N) content. Our findings provide direct evidence toward the understanding of different effects of soil physicochemical properties and host plant traits such as halophytes types, life span and cotyledon type, on the community composition of diazotrophic populations in the rhizosphere of plants grown in coastal saline soils.

Insight into biofilm-forming patterns: biofilm-forming conditions and dynamic changes in extracellular polymer substances - Yue Wang; Meng Fu; Bowen Wu; Mingyan Huang; Tian Ma; Hailian Zang; Hanyi Jiang; Yuting Zhang; Chunyan Li (Environmental Science and Pollution Research, 2022)

The effect of reservoir expansion from underground karst cave to surface reservoir on water quality in southwestern China - Meng Lu; Xiao-Dan Wang; Fu-Jun Yue; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Environmental Science and Pollution Research, 2022)

Evaluating the Effect of Anisotropy on Hydraulic Stimulation in a Slate Geothermal Reservoir - Meng-Chia Weng; Po-Lin Wu; Chih-Hung Fang; Yu-Yao Fu; Yen-Che Liao; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2022)

Assessing the impact of rockfall on the retaining structures of a mountain road: a case study in Taiwan - Che-Ming Yang; Chung-Hsun Lee; Chun-Yuan Liu; Wei-Kai Huang; Meng-Chia Weng; Yu-Yao Fu (Landslides, 2022)

Fine mapping of powdery mildew and stripe rust resistance genes Pm5V/Yr5V transferred from Dasypyrum villosum into wheat without yield penalty - Ruiqi Zhang; Chuntian Lu; Xiangru Meng; Yali Fan; Jie Du; Runran Liu; Yigao Feng; Liping Xing; Petr Cápal; Kateřina Holušová; Jaroslav Doležel; Yiwei Wang; et al. (Theoretical and Applied Genetics, 2022)

Effects of CYP24A1 polymorphisms on premature ejaculation: a case–control study - Fei Wang; Defan Luo; Jianxiang Chen; Cuiqing Pan; Zhongyao Wang; Housheng Fu; Jiangbing Xu; Meng Yang; Shaowei Mo; Liying Zhuang; Weifu Wang (Journal of Genetics, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Influencing Factors of Stereotypes on Wastewater Treatment Plants- Case Study of 9 Wastewater Treatment Plants in Xi’an, China - Hanliang Fu; Jiachen Niu; Zhifang Wu; Pengdong Xue; Meng Sun; Hong Zhu; Baoquan Cheng (Environmental Management, 2022)

Impacts of Mercury Exposure Levels and Sources on the Demethylation of Methylmercury Through Human Gut Microbiota - Xian-Feng Yang; Shao-Chen Yang; Fu-Li Wen; Lin Feng; Bo Meng; Hai-Yan Hu; Bao-Lin Wang; Jun Li; Alexandre J. Poulain; Ping Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Development of an Escherichia coli whole cell biocatalyst for the production of hyperoside - Guo-Si Li; Fu-Cheng Zhu; Pei-Pei Wei; Fang-Li Gu; Qi-Ling Xu; Meng-Hua Ma (Biotechnology Letters, 2022)

Zinc Deficiency Aggravates Oxidative Stress Leading to Inflammation and Fibrosis in Lung of Mice - Qirui Zhang; Yao Xue; Yuxin Fu; Bowen Bao; Meng-yao Guo (Biological Trace Element Research, 2022)

Analysis of efficient operation conditions of the Shuang 6 gas storage in Shuangtaizi Oilfield, LiaoHe Basin, China - Jianda Li; Lingdong Meng; Xiaofei Fu; Yejun Jin; Mingming Jiang; Cong Liu (Arabian Journal of Geosciences, 2022)

Outburst debris flow of Yusui Stream caused by a large-scale Silabaku landslide, Southern Taiwan - Che-Ming Yang; Wei-An Chao; Meng-Chia Weng; Yu-Yao Fu; Jui-Ming Chang; Wei-Kai Huang (Landslides, 2022)

Impact of N application rate on tea (Camellia sinensis) growth and soil bacterial and fungi communities - Sheng Tang; Jingjie Zhou; Wankun Pan; Rui Tang; Qingxu Ma; Meng Xu; Tong Qi; Zhengbo Ma; Haoran Fu; Lianghuan Wu (Plant and Soil, 2022)

Soil types determine vegetation communities along a toposequence in a dolomite peak-cluster depression catchment - Qingmei Meng; Sheng Wang; Zhiyong Fu; Yusong Deng; Hongsong Chen (Plant and Soil, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Bioenergy Production Potential of 16 Energy Crops on Marginal Land in China - Tongcheng Fu; Yi Xu; Meng Li; Shuai Xue; Zengqiang Duan; Guang Hui Xie (BioEnergy Research, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Rapid onset hazards, fault-controlled landslides and multi-method emergency decision-making - Fu-yun Guo; Xing-min Meng; Tian-jun Qi; Tom Dijkstra; Jarsve Kristine Thorkildsen; Dong-xia Yue; Guan Chen; Yi Zhang; Xiao-dong Dou; Peng-qing Shi (Journal of Mountain Science, 2022)

Water adsorption characteristic and its impact on pore structure and methane adsorption of various rank coals - Ming-yi Chen; Xiao-yun Chen; Liang Wang; Fu-chao Tian; Yu-meng Yang; Xue-jie Zhang; Ya-pu Yang (Environmental Science and Pollution Research, 2022)

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

The beneficial roles of poisonous skin secretions in survival strategies of the odorous frog Odorrana andersonii - Naixin Liu; Buliang Meng; Wenxin Bian; Meifeng Yang; Longjun Shu; Yixiang Liu; Zhe Fu; Yinglei Wang; Ying Wang; Xinwang Yang (The Science of Nature, 2022)

Two new nor -lignans from Selaginella pulvinata (Hook. & Grev.) Maxim and their antihyperglycemic activities - Hua-Wei Lv; Yu-Xia Li; Meng Luo; Jia-Meng Qi; Ze-Fei Fu; Hong-Jian Zhang; Yuan-Qiang Guo; Chu Chu; Han-Bing Li; Ji-Zhong Yan (Natural Product Research, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

N-acetylcysteine alleviates pulmonary inflammatory response during benzo[a]pyrene-evoked acute lung injury - Hui Zhao; Lin Fu; Hui-Xian Xiang; Ying Xiang; Meng-Die Li; Bian-Bian Lv; Zhu-Xia Tan; Lan Gao; Cheng Zhang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

SAR vehicle recognition via scale-coupled Incep_Dense Network (IDNet) - Bo Wang; Qingji Jiang; Dawei Song; Qiqi Zhang; Meng Sun; Xiaoxuan Fu; Junzhi Wang (International Journal of Remote Sensing, 2021)

Intra-annual radial growth and its climate response for Masson pine and Chinese fir in subtropical China - Shengwang Meng; Xiaoli Fu; Bo Zhao; Xiaoqin Dai; Qingkang Li; Fengting Yang; Liang Kou; Huimin Wang (Trees, 2021)

New phenolic acids from the whole herb of Elephantopus scaber Linn. and their anti-inflammatory activity - Lu Fu; Di Pei; Meng Yu; Hai Shang; Jin-Guang Si; Hong-Wu Zhang; Tao Zhang; Zhong-Mei Zou (Natural Product Research, 2021)

Genome-wide analysis and characterization of R2R3-MYB family in pigeon pea (Cajanus cajan) and their functional identification in phenylpropanoids biosynthesis - Jie Yang; Su Zhang; Hongquan Li; Litao Wang; Ying Liu; Lili Niu; Qing Yang; Dong Meng; Yujie Fu (Planta, 2021)

Home-Use and Real-Time Sleep-Staging System Based on Eye Masks and Mobile Devices with a Deep Learning Model - Tsung-Hao Hsieh; Meng-Hsuan Liu; Chin-En Kuo; Yung-Hung Wang; Sheng-Fu Liang (Journal of Medical and Biological Engineering, 2021)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Landslide mapping and analysis along the China-Pakistan Karakoram Highway based on SBAS-InSAR detection in 2017 - Xiao-jun Su; Yi Zhang; Xing-min Meng; Dong-xia Yue; Jin-hui Ma; Fu-yun Guo; Zi-qiang Zhou; Mohib Ur Rehman; Zainab Khalid; Guan Chen; Run-qiang Zeng; Fu-meng Zhao (Journal of Mountain Science, 2021)

Expression analysis and tissue localization of IgZ in the grouper Epinephelus coioides after Vibrio alginolyticus infection and vaccination - Yao‐Wu Fu; Zhan‐Juan Yao; Meng‐Han He; Zuo‐Pei Wang; Wei‐Feng Chen; Miao Cui; Qi‐Zhong Zhang (Journal of Fish Diseases, 2021)
The orange‐spotted grouper ( Epinephelus coioides ) is an important marine farmed fish in China. It is affected by the bacterial pathogen Vibrio alginolyticus , which causes high mortality and substantial economic losses. We studied the transcriptional changes of the IgZ gene in E. coioides following V. alginolyticus stimulation and investigated the distribution of IgZ in different tissues. The highest expression level of IgZ occurred in the head kidney. When fish were stimulated with live and inactivated V. alginolyticus , the expression levels of IgZ in the head kidney, spleen, intestine, gills and blood cells were significantly upregulated. In an in situ hybridization study, IgZ mRNA‐positive cells were detected in the head kidney, spleen and gill, but positive signals were not detected in the liver and intestine. IgZ‐labelled cells increased in the head kidney, spleen and gills post‐infection with V. alginolyticus for 21 days. The present study provides additional evidence that IgZ is involved in mucosal immune responses and helps explain the role of IgZ in E . coioides defence against V . alginolyticus infection.

A Numerical Meso-Scale Elasto-Plastic Damage Model for Modeling the Deformation and Fracturing of Sandstone Under Cyclic Loading - Tao Xu; Meng Fu; Sheng-qi Yang; Michael J. Heap; Guang-lei Zhou (Rock Mechanics and Rock Engineering, 2021)

Phytolith evidence for early agriculture in the East Liao River Basin, Northeast China - Jiangyong Wang; Linan Sun; Qi Fang; Jiaxin Fu; Baojian Liu; Ying Liu; Xiangmei Kong; Honghao Niu; Guizai Gao; Meng Meng; Dongmei Jie (Archaeological and Anthropological Sciences, 2021)

Resource status and protection strategies of mangroves in China - Xiu-Mei Fu; Hui-Ying Tang; Yang Liu; Meng-Qi Zhang; Shan-Shan Jiang; Fang Yang; Xiao-Yan Li; Chang-Yun Wang (Journal of Coastal Conservation, 2021)
Mangrove is a typical natural landscape with great ecological, social and economic functions and values, and should be highly valued and protected. However, in the past few decades, mangrove resources have suffered serious damage, and there are also many deficiencies in mangrove protection. Chinese mangroves, as an important part of the global mangroves, are of great research value. In the present study, the status and historical dynamic process of Chinese mangrove resources were investigated and discussed to illustrate the problems of resources from three aspects, including mangrove distribution, area and plant species. Based on field research, literature research and data analysis, it was revealed that Chinese mangroves are distributed in eight provinces and regions along the southeast coast with an area of 35,749.25 hm 2 , 38 species and 40 nature reserves. The protection situation and deficiencies were analyzed from the establishment and management of nature reserves. Based on the resource status and problems, reasonable strategies were proposed to protect and manage mangroves mainly from four aspects, including publicity and education, resources restoration and protection technology, legal system establishment, and comprehensive protection and management.

An overview of chitosan and its application in infectious diseases - Qingye Meng; Ying Sun; Hailin Cong; Hao Hu; Fu-Jian Xu (Drug Delivery and Translational Research, 2021)

The first complete genome sequence of an iflavirus from the endoparasitoid wasp Tetrastichus brontispae - E Meng; Baozhen Tang; Jingyi Li; Lang Fu; Youming Hou (Archives of Virology, 2021)

The contrasting relationships of relative humidity with influenza A and B in a humid subtropical region - Qian Wu; Jun He; Wen-Yan Zhang; Ke-Fu Zhao; Jing Jin; Jun-Ling Yu; Qing-Qing Chen; Sai Hou; Meng Zhu; Zhiwei Xu; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Deformation of the Zhangjiazhuang high-speed railway tunnel: an analysis of causal mechanisms using geomorphological surveys and D-InSAR monitoring - Xing-min Meng; Tian-jun Qi; Yan Zhao; Tom Dijkstra; Wei Shi; Yin-fei Luo; Yuan-zhao Wu; Xiao-jun Su; Fu-meng Zhao; Jin-hui Ma; Yi Zhang; Guan Chen; et al. (Journal of Mountain Science, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Bridge Crack Semantic Segmentation Based on Improved Deeplabv3+ - Huixuan Fu; Dan Meng; Wenhui Li; Yuchao Wang (Journal of Marine Science and Engineering, 2021)
Cracks are the main goal of bridge maintenance and accurate detection of cracks will help ensure their safe use. Aiming at the problem that traditional image processing methods are difficult to accurately detect cracks, deep learning technology was introduced and a crack detection method based on an improved DeepLabv3+ semantic segmentation algorithm was proposed. In the network structure, the densely connected atrous spatial pyramid pooling module was introduced into the DeepLabv3+ network, which enabled the network to obtain denser pixel sampling, thus enhancing the ability of the network to extract detail features. While obtaining a larger receptive field, the number of network parameters was consistent with the original algorithm. The images of bridge cracks under different environmental conditions were collected, and then a concrete bridge crack segmentation data set was established, and the segmentation model was obtained through end-to-end training of the network. The experimental results showed that the improved DeepLabv3+ algorithm had higher crack segmentation accuracy than the original DeepLabv3+ algorithm, with an average intersection ratio reaching 82.37%, and the segmentation of crack details was more accurate, which proved the effectiveness of the proposed algorithm.

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Budgets of rotational and divergent kinetic energy in the warm-sector torrential rains over South China: a case study - Shui-Xin Zhong; Wei-Guang Meng; Fu-You Tian (Meteorology and Atmospheric Physics, 2021)
The contributions of divergent and rotational wind components to the kinetic energy budget during a record-breaking rainstorm on 7 May 2017 over South China are examined. This warm-sector extreme precipitation caused historical maximum of 382.6 mm accumulated rainfall in 3 h over the Pearl River Delta (PRD) regions in South China. Results show that there was a high low-level southerly wind-speed tongue stretching into the PRD regions from the northeast of the South China Sea (SCS) during this extreme precipitation. The velocity potential exhibited a low-value center as well as a low-level divergence-center over the SCS. The rotational components of the kinetic energy (KR)-related terms were the main contribution-terms of the kinetic energy budget. The main contribution-terms of KR and the divergent component of kinetic energy (KD) were the barotropical and baroclinic processes-related terms due to cross-contour flow and the vertical flux divergence.

Enhanced rice yields are related to pronounced shifts in soil resident bacterial community structures in response to Rhodopseudomonas palustris and Bacillus subtilis inoculation - Yuan Zhao; Yue Sun; Meng Pei; Jing Fu; Hai Ji; Lihua Zhao; Xian Xiao (Journal of Soils and Sediments, 2021)

Agarose-based spheroid culture enhanced stemness and promoted odontogenic differentiation potential of human dental follicle cells in vitro - Min Li; Tiwei Fu; Sen Yang; Lanlan Pan; Jing Tang; Meng Chen; Panpan Liang; Zhi Gao; Lijuan Guo (In Vitro Cellular & Developmental Biology - Animal, 2021)

QTL mapping and candidate gene identification of lint percentage based on a recombinant inbred line population of upland cotton - Hantao Wang; Xiaoyun Jia; Meng Kang; Wei Li; Xiaokang Fu; Liang Ma; Jianhua Lu; Hengling Wei; Shuxun Yu (Euphytica, 2021)

Photoperiod decelerates the advance of spring phenology of six deciduous tree species under climate warming - Lin Meng; Yuyu Zhou; Lianhong Gu; Andrew D. Richardson; Josep Peñuelas; Yongshuo Fu; Yeqiao Wang; Ghasserm R. Asrar; Hans J. De Boeck; Jiafu Mao; Yongguang Zhang; Zhuosen Wang (Global Change Biology, 2021)
Vegetation phenology in spring has substantially advanced under climate warming, consequently shifting the seasonality of ecosystem process and altering biosphere–atmosphere feedbacks. However, whether and to what extent photoperiod (i.e., daylength) affects the phenological advancement is unclear, leading to large uncertainties in projecting future phenological changes. Here we examined the photoperiod effect on spring phenology at a regional scale using in situ observation of six deciduous tree species from the Pan European Phenological Network during 1980–2016. We disentangled the photoperiod effect from the temperature effect (i.e., forcing and chilling) by utilizing the unique topography of the northern Alps of Europe (i.e., varying daylength but uniform temperature distribution across latitudes) and examining phenological changes across latitudes. We found prominent photoperiod‐induced shifts in spring leaf‐out across latitudes (up to 1.7 days per latitudinal degree). Photoperiod regulates spring phenology by delaying early leaf‐out and advancing late leaf‐out caused by temperature variations. Based on these findings, we proposed two phenological models that consider the photoperiod effect through different mechanisms and compared them with a chilling model. We found that photoperiod regulation would slow down the advance in spring leaf‐out under projected climate warming and thus mitigate the increasing frost risk in spring that deciduous forests will face in the future. Our findings identify photoperiod as a critical but understudied factor influencing spring phenology, suggesting that the responses of terrestrial ecosystem processes to climate warming are likely to be overestimated without adequately considering the photoperiod effect.

Serological evidence of bovine viral diarrhea virus and peste des petits ruminants virus infection in alpacas (Vicugna pacos) in Shanxi Province, northern China - Qing Liu; Lu Liu; Yu-Kai Meng; Chen Wang; Yu Gao; Fu-Guo Zheng; Hai-Li Ma (Tropical Animal Health and Production, 2021)

Gut microbiome alterations and its link to corticosteroid resistance in immune thrombocytopenia - Yanan Wang; Fengqi Liu; Gaochao Zhang; Yan Su; Xueyan Sun; Qi Chen; Chencong Wang; Haixia Fu; Yun He; Xiaolu Zhu; Xiao Liu; Meng Lv; et al. (Science China Life Sciences, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Annual and seasonal precipitation trends and their attributions in the Qinling Mountains, a climate transitional zone in China - Qing Meng; Hongying Bai; Ranjan Sarukkalige; Guobin Fu; Wenhao Jia; Chenhua Zhang (Theoretical and Applied Climatology, 2021)

Transgenic eukaryotic microalgae as green factories: providing new ideas for the production of biologically active substances - Qianwen Shi; Cheng Chen; Wei Zhang; Ping Wu; Meng Sun; Hui Wu; Haizhen Wu; Pengcheng Fu; Jianhua Fan (Journal of Applied Phycology, 2021)

The construction of high precision geostrophic currents based on new gravity models of GOCE and satellite altimetry data - Wenyan Sui; Junru Guo; Jun Song; Zhiliang Liu; Meng Wang; Xibin Li; Yanzhao Fu; Yongquan Li; Yu Cai; Linhui Wang; Lingli Li; Xiaofang Guo; et al. (Acta Oceanologica Sinica, 2021)

Decline of Seriatopora (Scleractinia: Pocilloporidae) fecundity in Taiwan in 2018–2019 - Luca Cirino; Sujune Tsai; Fu-Wen Kuo; Zhi-Hong Wen; Pei-Jie Meng; Chiahsin Lin (Marine Biology Research, 2021)

Differential response of microbial diversity and abundance to hydrological residual time and age in cascade reservoirs - Yihong Yue; Fushun Wang; Zhiwei Fu; Yi Tang; Jing Ma; Yong Qin; Meng Li; Ming Yang; Xue-Ping Chen (Journal of Soils and Sediments, 2021)

Reliability and Validity of a Mobile Device for Assessing Head Control Ability - Mohammad Nikkhoo; Chi-Chien Niu; Chen-Ju Fu; Meng-Ling Lu; Wen-Chien Chen; Yang-Hua Lin; Chih-Hsiu Cheng (Journal of Medical and Biological Engineering, 2021)

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Genetic variants in Hippo signalling pathway-related genes affect the risk of colorectal cancer - Hengyang Shen; Yixuan Meng; Tao Hu; Shuwei Li; Mulong Du; Junyi Xin; Dongying Gu; Meilin Wang; Zan Fu (Archives of Toxicology, 2021)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Differences in evaporite geochemistry of the greater Ordos Ordovician salt basin, China: evidence from the M56 submember of the Majiagou Formation - Fu Fan; Fan-Wei Meng; Yong-Sheng Zhang; Mian-Ping Zheng; Kui Su; En-Yuan Xing (Carbonates and Evaporites, 2020)

Microscopic and Fractal Characterization of Organic Matter within Lacustrine Shale Reservoirs in the First Member of Cretaceous Qingshankou Formation, Songliao Basin, Northeast China - Bo Liu; Meng Yan; Xianda Sun; Yunfeng Bai; Longhui Bai; Xiaofei Fu (Journal of Earth Science, 2020)

3D inversion of audio-magnetotelluric data for mineral exploration: A case study of Layikeleke buried porphyry copper deposit, Xinjiang, China - Fu Guang-Ming; Yan Jia-Yong; Chen Hui; Meng Gui-Xiang; Yu Hui; Luo Fan; Luo Lei; Tao Xin (Applied Geophysics, 2020)

Arsenic trioxide alleviates acute graft-versus-host disease by modulating macrophage polarization - Xiao Liu; Yan Su; Xueyan Sun; Haixia Fu; Qiusha Huang; Qi Chen; Xiaodong Mo; Meng Lv; Yuan Kong; Lanping Xu; Xiaojun Huang; Xiaohui Zhang (Science China Life Sciences, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Whole-Brain Map of Long-Range Monosynaptic Inputs to Different Cell Types in the Amygdala of the Mouse - Jia-Yu Fu; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Meng-Yu Tang; Bin Yu; Xiao-Ming Li (Neuroscience Bulletin, 2020)
The amygdala, which is involved in various behaviors and emotions, is reported to connect with the whole brain. However, the long-range inputs of distinct cell types have not yet been defined. Here, we used a retrograde trans-synaptic rabies virus to generate a whole-brain map of inputs to the main cell types in the mouse amygdala. We identified 37 individual regions that projected to neurons expressing vesicular glutamate transporter 2, 78 regions to parvalbumin-expressing neurons, 104 regions to neurons expressing protein kinase C-δ, and 89 regions to somatostatin-expressing neurons. The amygdala received massive projections from the isocortex and striatum. Several nuclei, such as the caudate-putamen and the CA1 field of the hippocampus, exhibited input preferences to different cell types in the amygdala. Notably, we identified several novel input areas, including the substantia innominata and zona incerta. These findings provide anatomical evidence to help understand the precise connections and diverse functions of the amygdala.

Potential probiotic of Lactobacillus strains isolated from the intestinal tracts of pigs and feces of dogs with antibacterial activity against multidrug-resistant pathogenic bacteria - Chuen-Fu Lin; Meng-Yi Lin; Chao-Nan Lin; Ming-Tang Chiou; Jia-Wen Chen; Kai-Chieh Yang; Ming-Cheng Wu (Archives of Microbiology, 2020)

Functional genetic variants in centrosome-related genes CEP72 and YWHAG confer susceptibility to gastric cancer - Jing Ni; Jinchen Wang; Yao Fu; Caiwang Yan; Meng Zhu; Yue Jiang; Jiaping Chen; Yanbing Ding; Xiangshan Fan; Gang Li; Guangfu Jin (Archives of Toxicology, 2020)

Increased EZH2 Levels in Anterior Cingulate Cortex Microglia Aggravate Neuropathic Pain by Inhibiting Autophagy Following Brachial Plexus Avulsion in Rats - Xiang-Lei Meng; Pengfei Fu; Lin Wang; Xun Yang; Guanghui Hong; Xin Zhao; Jie Lao (Neuroscience Bulletin, 2020)

Trehalose attenuates TGF-β1-induced fibrosis of hSCFs by activating autophagy - Nianxuan Wu; Liangbo Chen; Dan Yan; Meng Zhou; Chunyi Shao; Yang Lu; Qinke Yao; Hao Sun; Yao Fu (Molecular and Cellular Biochemistry, 2020)

Postprandial proximal gastric acid pocket and its association with gastroesophageal acid reflux in patients with short-segment Barrett’s esophagus - Yuan-yuan Nian; Xian-mei Meng; Jing Wu; Fu-chu Jing; Xue-qin Wang; Tong Dang; Jun Zhang (Journal of Zhejiang University-SCIENCE B, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

The Response of Sarcodia suiae to Long-term Exposure of Arsenic (Arsenate): Growth, Morphology, and Arsenic Alterations - Mary Joy Halog Libatique; Meng-Chou Lee; Han-Yang Yeh; Fu-Jie Jhang (Water, Air, & Soil Pollution, 2020)

Bacteriostatic effect of lipopeptides from Bacillus subtilis N-2 on Pseudomonas putida using soybean meal by solid-state fermentation - Meng Li; Haijin Mou; Qing Kong; Tan Zhang; Xiaodan Fu (Marine Life Science & Technology, 2020)

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Physiological functions of urea transporter B - Lanying Yu; Tiantian Liu; Shuang Fu; Li Li; Xiaoping Meng; Xin Su; Zhanfeng Xie; Jiayan Ren; Yan Meng; Xuejiao Lv; Yanwei Du (Pflügers Archiv - European Journal of Physiology, 2019)
Urea transporters (UTs) are membrane proteins in the urea transporter protein A (UT-A) and urea transporter protein B (UT-B) families. UT-B is mainly expressed in endothelial cell membrane of the renal medulla and in other tissues, including the brain, heart, pancreas, colon, bladder, bone marrow, and cochlea. UT-B is responsible for the maintenance of urea concentration, male reproductive function, blood pressure, bone metabolism, and brain astrocyte and cardiac functions. Its deficiency and dysfunction contribute to the pathogenesis of many diseases. Actually, UT-B deficiency increases the sensitivity of bladder epithelial cells to apoptosis triggers in mice and UT-B-null mice develop II-III atrioventricular block and depression. The expression of UT-B in the rumen of cow and sheep may participate in digestive function. However, there is no systemic review to discuss the UT-B functions. Here, we update research approaches to understanding the functions of UT-B.

Characteristics changes in banana peel coagulant during storage process - Y. Fu; X. J. Meng; N. N. Lu; H. L. Jian; Y. Di (International Journal of Environmental Science and Technology, 2019)

Risk Assessment of Crop Production Amid Climate Change Based on the Principle of Maximum Entropy: A Case Study of Winter Wheat Production on the North China Plain - Zhan-biao Wang; Cheng-sheng Meng; Jing Chen; Fu Chen (International Journal of Plant Production, 2019)

Se Regulates the Contractile Ability of Uterine Smooth Musclevia Selenoprotein N, Selenoprotein T, and Selenoprotein Win Mice - Fu-han Wang; Xiao Peng; Yu Chen; Ying Wang; Mei Yang; Meng-yao Guo (Biological Trace Element Research, 2019)

Eco-friendly preparation of chitooligosaccharides with different degrees of deacetylation from shrimp shell waste and their effects on the germination of wheat seeds - Xiaodan Fu; Lin Zhu; Li Li; Tan Zhang; Meng Li; Haijin Mou (Marine Life Science & Technology, 2019)
Production of chitosan and its derivatives by traditional methods involves the excessive use of a reaction solution comprised of sodium hydroxide and hydrochloric acid. Waste water resulting from this process has limited the application of chitosan as a fertilizer as the process causes serious environmental pollution. Specifically, the resulting waste water contains high levels of dissolved nitrogen and minerals from shrimp shells. In this study, an eco-friendly method was established to produce chitooligosaccharides (COS) with different degrees of deacetylation (DDAs) from shrimp shell waste. At a solid-to-solvent ratio of 1:6, the degree of demineralization was above 90% with the treatment of 30 g·L −1 H 3 PO 4 , and the degree of deproteinization was above 80% when treated with 30 g·L −1 KOH at 70 °C. Chitosans with different DDAs were obtained by microwave-assisted KOH metathesis and the COS with Mw approximately 1500 Da were then prepared by oxidative degradation. In summary, 33.73 kg H 3 PO 4 , 12.77 kg, and 241.31 kg KOH were supplied during the processes of demineralization, deproteinization, and deacetylation of 100 kg shrimp shell waste, respectively. The process water was totally recycled, demonstrating that the shrimp shell could be wholly transformed into fertilizer. The entire process created a product with the fractions of N:P 2 O 5 :K 2 O:COS = 7.94:24.44:10.72:18.27. The test on the germination promotion of wheat seeds revealed that the COS with 72.12% DDA significantly promoted germination. This work demonstrated the use of an eco-friendly preparation method of COS with a specific degree of deacetylation that can be applied as a fertilizer.

Progranulin alleviates podocyte injury via regulating CAMKK/AMPK-mediated autophagy under diabetic conditions - Di Zhou; Meng Zhou; Ziying Wang; Yi Fu; Meng Jia; Xiaojie Wang; Min Liu; Yan Zhang; Yu Sun; Yabin Zhou; Yi Lu; Wei Tang; et al. (Journal of Molecular Medicine, 2019)

A data-driven approach to predicting the attachment density of biofouling organisms - Andre E. Vellwock; Jimin Fu; Yuan Meng; V. Thiyagarajan; Haimin Yao (Biofouling, 2019)

An iterative damped least-squares algorithm for simultaneously monitoring the development of hemorrhagic and secondary ischemic lesions in brain injuries - Xuechao Liu; Haoting Li; Hang Ma; Canhua Xu; Bin Yang; Meng Dai; Xiuzhen Dong; Feng Fu (Medical & Biological Engineering & Computing, 2019)

Protective Effects of 1-Methylnicotinamide on Aβ1–42-Induced Cognitive Deficits, Neuroinflammation and Apoptosis in Mice - Lili Fu; Caihong Liu; Liang Chen; Yangge Lv; Guoliang Meng; Mei Hu; Yan Long; Hao Hong; Susu Tang (Journal of Neuroimmune Pharmacology, 2019)

Biologically active oligostilbenes from the stems of Vatica mangachapoi and chemotaxonomic significance - Shou-Yuan Wu; Yan-Hui Fu; Qi Zhou; Meng Bai; Guang-Ying Chen; Chang-Ri Han; Xiao-Ping Song (Natural Product Research, 2019)

Phylogeography and population genetic structure of flowering cherry species Cerasus dielsiana in subtropical China - Hong Zhu; Xian-GUI Yi; Yong-Fu Li; Shu-Xia Zhu; Meng Li; Yi-Fan Duan; Xian-Rong Wang (Systematics and Biodiversity, 2019)

Genome-wide identification and characterization of UGT family in pigeonpea (Cajanus cajan) and expression analysis in abiotic stress - Zhihua Song; Lili Niu; Qing Yang; Biying Dong; Litao Wang; Mingzhu Dong; Xiaohong Fan; Yue Jian; Dong Meng; Yujie Fu (Trees, 2019)

The anther-specific CYP704B is potentially responsible for MSG26 male sterility in barley - Juan Qi; Fei Ni; Xiao Wang; Meng Sun; Yu Cui; Jiajie Wu; Allan Caplan; Daolin Fu (Theoretical and Applied Genetics, 2019)

Complete Genome Sequence of Actinosynnema pretiosum X47, An Industrial Strain that Produces the Antibiotic Ansamitocin AP-3 - Chuanqing Zhong; Gongli Zong; Shulan Qian; Meng Liu; Jiafang Fu; Peipei Zhang; Jun Li; Guangxiang Cao (Current Microbiology, 2019)

Two new echinocystic acid derivatives catalyzed by filamentous fungus Gliocladium roseum CGMCC 3.3657 - Shao-Bin Fu; Xu Feng; Qing-Feng Meng; Qing Cai; Di-An Sun (Natural Product Research, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Deformation Mechanism and Vertical Sealing Capacity of Fault in the Mudstone Caprock - Xiaofei Fu; Lingyu Yan; Lingdong Meng; Xiaobo Liu (Journal of Earth Science, 2019)

The scientific connotation of oil and gas formations under deep fluids and organic-inorganic interaction - Quanyou Liu; Dongya Zhu; Qingqiang Meng; Jiayi Liu; Xiaoqi Wu; Bing Zhou; Qi Fu; Zhijun Jin (Science China Earth Sciences, 2019)

Stromatolites in Middle Ordovician carbonate–evaporite sequences and their carbon and sulfur isotopes stratigraphy, Ordos Basin, northwestern China - Fan-Wei Meng; Zhi-li Zhang; Xian-qin Yan; Pei Ni; Wen-Hang Liu; Fu Fan; Gu-Wei Xie (Carbonates and Evaporites, 2019)

Occurrence and removal of polycyclic aromatic hydrocarbons and their derivatives in an ecological wastewater treatment plant in South China and effluent impact to the receiving river - Meng Qiao; Lujing Fu; Wei Cao; Yaohui Bai; Qiuxin Huang; Xu Zhao (Environmental Science and Pollution Research, 2019)

Ethical considerations of cellular immunotherapy for cancer - Sang-sang Ren; Jing-wen Deng; Meng Hong; Yan-li Ren; Hai-jing Fu; Yan-ning Liu; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Altered gray matter volume in primary insomnia patients: a DARTEL-VBM study - Meng Li; Jianhao Yan; Shumei Li; Tianyue Wang; Hua Wen; Yi Yin; Shishun Fu; Luxian Zeng; Junzhang Tian; Guihua Jiang (Brain Imaging and Behavior, 2018)

Improving the annual yield of a wheat and maize system through irrigation at the maize sowing stage † - Yupeng Feng; Meng Yang; Mengfei Shang; Hao Jia; Qingquan Chu; Fu Chen (Irrigation and Drainage, 2018)
To achieve high‐yielding and eco‐friendly crop production, it is crucial to identify the critical water requirement period of crops, especially in annual crop production systems. A 2‐year experiment was established to study the annual yield, total water consumption and water productivity (WP) of a winter wheat ( Triticum aestivum L.) and summer maize ( Zea mays L.) system in the Huang‐Huai‐Hai Plain. The results showed that the annual yield of this crop system increased with irrigation frequency and was highest when irrigation was applied three times in the wheat season and once in the maize season (W 3 M 1 ), though there was no significant difference in annual yield among W 2 M 1 , W 3 M 1 and W 4 M 1 . And there is no evidence in this paper that irrigation scheduling substantially affects WP. W 2 M 1 had the second highest annual yield (18.7 t ha −1 in 2013–2014 and 19.9 ha −1 in 2014–2015) with a low amount of irrigation compared with W 3 M 1 and W 4 M 1 . The highest total water consumption was measured in W 3 M 1 and reached 812 and 873 mm in the first and second years, respectively. Irrigation during the summer maize sowing stage is essential for improving the annual yield and WP. © 2018 John Wiley & Sons, Ltd.

Shear strength of frozen clay under freezing-thawing cycles using triaxial tests - Miao Wang; Shangjiu Meng; Yiqiang Sun; Haiqing Fu (Earthquake Engineering and Engineering Vibration, 2018)

Design of multi-layer coupling support and span of setup entry roof at depth - Hou-sheng Jia; Lu-yao Wang; Shao-wei Liu; Zhi-yao Feng; Meng-xiong Fu (Arabian Journal of Geosciences, 2018)

Poststack internal multiples attenuation based on virtual events - Meng Chen; Jia-Hui Liu; Yong-Fu Cui; Tian-Yue Hu; Fei-Xu Chen; Wei-Kang Kuang; Zhen Zhang (Applied Geophysics, 2018)

Assessing spatial and temporal variations in regional sustainability in mainland China from 2004 to 2014 - Wei Qiu; Fanlin Meng; Yuntao Wang; Guangtao Fu; Junguo He; Dragan Savic; Hongyu Zhao (Clean Technologies and Environmental Policy, 2018)

Analysis of the Spatial Variation and Identification of Factors Affecting the Water Resources Carrying Capacity Based on the Cloud Model - K. Cheng; Q. Fu; J. Meng; T. X. Li; W. Pei (Water Resources Management, 2018)

Detoxification of aflatoxins on prospective approach: effect on structural, mechanical, and optical properties under pressures - Yong-Kai Wei; Xiao-Miao Zhao; Meng-Meng Li; Jing-Xin Yu; Selvaraj Gurudeeban; Yan-Fei Hu; Guang-Fu Ji; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Review of total suspended particles (TSP) and PM2.5 concentration variations in Asia during the years of 1998–2015 - Guor-Cheng Fang; Yuan-Jie Zhuang; Meng-Hsien Cho; Chao-Yang Huang; You-Fu Xiao; Kai-Hsiang Tsai (Environmental Geochemistry and Health, 2018)

A new dihydrochalcone glycoside from the stems of Homalium stenophyllum - Shou-Yuan Wu; Yan-Hui Fu; Qi Zhou; Meng Bai; Guang-Ying Chen; Chang-Ri Han; Xiao-Ping Song (Natural Product Research, 2018)

In Vivo Biocompatibility and Improved Compression Strength of Reinforced Keratin/Hydroxyapatite Scaffold - Jie Fan; Meng-Yan Yu; Tong-da Lei; Yong-Heng Wang; Fu-Yuan Cao; Xiao Qin; Yong Liu (Tissue Engineering and Regenerative Medicine, 2018)

An Efficient and Reliable Assay for Investigating the Effects of Hypoxia/Anoxia on Drosophila - Yiling Xia; Wangchao Xu; Shiquan Meng; Nastasia K. H. Lim; Wenan Wang; Fu-De Huang (Neuroscience Bulletin, 2018)

Transferability of Conceptual Hydrological Models Across Temporal Resolutions: Approach and Application - Meng-Xuan Jie; Hua Chen; Chong-Yu Xu; Qiang Zeng; Jie Chen; Jong-Suk Kim; Sheng-lian Guo; Fu-Qiang Guo (Water Resources Management, 2018)

Concentrations and analysis of health risks of ambient air metallic elements at Longjing site in central Taiwan - Guor-Cheng Fang; Yu-Cheng Chen; Chaur-Tsuen Lo; Meng-Hsien Cho; Yuan-Jie Zhuang; Kai-Hsiang Tsai; Chao-Yang Huang; You-Fu Xiao (Environmental Geochemistry and Health, 2018)

Physiological and biochemical responses of Camellia sinensis to stress associated with Empoasca vitis feeding - Jian-yu Li; Meng-zhu Shi; Jian-wei Fu; Yue-chao He; David J. Perović; Ting Wang (Arthropod-Plant Interactions, 2018)

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

The Effects of Low Concentrations of Silver Nanoparticles on Wheat Growth, Seed Quality, and Soil Microbial Communities - Guangfu Liu; Meng Zhang; Yujian Jin; Xiaoji Fan; Jiahui Xu; Youchao Zhu; Zhengwei Fu; Xiangliang Pan; Haifeng Qian (Water, Air, & Soil Pollution, 2017)

KIFC1 and myosin Va: two motors for acrosomal biogenesis and nuclear shaping during spermiogenesis of Portunus trituberculatus - Dan-Dan Ma; Meng-Ying Pan; Cong-Cong Hou; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2017)

The Neuron-Specific Protein TMEM59L Mediates Oxidative Stress-Induced Cell Death - Qiuyang Zheng; Xiaoyuan Zheng; Lishan Zhang; Hong Luo; Lingzhi Qian; Xing Fu; Yiqian Liu; Yuehong Gao; Mengxi Niu; Jian Meng; Muxian Zhang; Guojun Bu; et al. (Molecular Neurobiology, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Forest-type shift and subsequent intensive management affected soil organic carbon and microbial community in southeastern China - Xianghua Fang; Jinchi Zhang; Miaojing Meng; Xiaoping Guo; Yanwen Wu; Xin Liu; Keli Zhao; Lizhong Ding; Yangfeng Shao; Weijun Fu (European Journal of Forest Research, 2017)

Annual ambient atmospheric mercury speciation measurement from Longjing, a rural site in Taiwan - Guor-Cheng Fang; Chaur-Tsuen Lo; Meng-Hsien Cho; Yuan-Jie Zhuang; Kai-Hsiang Tsai; Chao-Yang Huang; You-Fu Xiao (Environmental Geochemistry and Health, 2017)

PM2.5 particulates and metallic elements (Ni, Cu, Zn, Cd and Pb) study in a mixed area of summer season in Shalu, Taiwan - Guor-Cheng Fang; You-Fu Xiao; Yuan-Jie Zhuang; Meng-Hsien Cho; Chao-Yang Huang; Kai-Hsiang Tsai (Environmental Geochemistry and Health, 2017)

Glandular trichome-specific expression of alcohol dehydrogenase 1 (ADH1) using a promoter-GUS fusion in Artemisia annua L. - Qian He; Xueqing Fu; Pu Shi; Meng Liu; Qian Shen; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The small auxin-up RNA OsSAUR45 affects auxin synthesis and transport in rice - Yan-Xia Xu; Meng-Zhu Xiao; Yan Liu; Jun-Liang Fu; Yi He; De-An Jiang (Plant Molecular Biology, 2017)

Promotion of artemisinin content in Artemisia annua by overexpression of multiple artemisinin biosynthetic pathway genes - Pu Shi; Xueqing Fu; Meng Liu; Qian Shen; Weimin Jiang; Ling Li; Xiaofen Sun; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Evaluation of the land carrying capacity of major grain-producing areas and the identification of risk factors - Kun Cheng; Qiang Fu; Song Cui; Tian-xiao Li; Wei Pei; Dong Liu; Jun Meng (Natural Hazards, 2017)

Endovascular Treatment Versus Intravenous Thrombolysis for Acute Ischemic Stroke: a Quantitative Review and Meta-Analysis of 21 Randomized Trials - Chen-Chen Tan; Hui-Fu Wang; Jin-Long Ji; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Umbilical cord-derived mesenchymal stem cell transplantation for treating elderly vascular dementia - Yan He; Xingfang Jin; Jun Wang; Mingyao Meng; Zongliu Hou; Weimeng Tian; You Li; Wenju Wang; Yunhong Wei; Yipeng Wang; Hongqiong Meng; Xuyang Lu; et al. (Cell and Tissue Banking, 2017)

Seasonal variations and sources study by way of back trajectories and ANOVA for ambient air pollutants (particulates and metallic elements) within a mixed area at Longjing, central Taiwan: 1-year observation - Guor-Cheng Fang; Chaur-Tsuen Lo; Yuan-Jie Zhuang; Meng-Hsien Cho; Chao-Yang Huang; You-Fu Xiao; Kai-Hsiang Tsai (Environmental Geochemistry and Health, 2017)

Bacterial community composition in the rhizosphere of maize cultivars widely grown in different decades - Xinya Wen; Meng Wang; Jingsong Ti; Yao Wu; Fu Chen (Biology and Fertility of Soils, 2017)

Effect of CR1 Genetic Variants on Cerebrospinal Fluid and Neuroimaging Biomarkers in Healthy, Mild Cognitive Impairment and Alzheimer's Disease Cohorts - Xi-Chen Zhu; Hui-Fu Wang; Teng Jiang; Huan Lu; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of Parkinson’s Disease GWAS-Linked Loci with Alzheimer’s Disease in Han Chinese - Xi-Chen Zhu; Lei Cao; Meng-Shan Tan; Teng Jiang; Hui-Fu Wang; Huan Lu; Chen-Chen Tan; Wei Zhang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The Impact of UNC5C Genetic Variations on Neuroimaging in Alzheimer’s Disease - Jia-Hao Sun; Hui-Fu Wang; Xi-Chen Zhu; Wan-Jiang Yu; Chen-Chen Tan; Teng Jiang; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Dietary Patterns and Risk of Dementia: a Systematic Review and Meta-Analysis of Cohort Studies - Lei Cao; Lan Tan; Hui-Fu Wang; Teng Jiang; Xi-Chen Zhu; Huan Lu; Meng-Shan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

A sensitive immunochromatographic assay using colloidal gold–antibody probe for rapid detection of fumonisin B 1 in corn - Xi-Chun Wang; Hai-Xin Fan; Meng-Xue Fan; Fu-Hui Li; Shi-Bin Feng; Jin-Chun Li; Jin-Jie Wu; Yu Li; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2016)

Characterization of a trichome-specific promoter of the aldehyde dehydrogenase 1 (ALDH1) gene in Artemisia annua - Meng Liu; Pu Shi; Xueqing Fu; Peter E. Brodelius; Qian Shen; Weimin Jiang; Qian He; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Impact of Common Variations in PLD3 on Neuroimaging Phenotypes in Non-demented Elders - Chong Wang; Hui-Fu Wang; Meng-Shan Tan; Ying Liu; Teng Jiang; Dao-Qiang Zhang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Relationship between leaf reddening, ROS and antioxidants in Buxus microphylla during overwintering - Xue-ru Jiang; Jin-gen Peng; Meng-xue Jia; Yan Liu; Ling Guo; Rong-fu Gao (Acta Physiologiae Plantarum, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

The Regulatory Roles of ncRNA Rli60 in Adaptability of Listeria monocytogenes to Environmental Stress and Biofilm Formation - Ye-long Peng; Qing-ling Meng; Jun Qiao; Kun Xie; Cheng Chen; Tian-li Liu; Zheng-xiang Hu; Yu Ma; Xue-peng Cai; Chuang-fu Chen (Current Microbiology, 2016)

Cyanidin-3-O-glucoside Induces Apoptosis and Inhibits Migration of Tumor Necrosis Factor-α-Treated Rat Aortic Smooth Muscle Cells - Xuerui Yan; Lin Wu; Bin Li; Xianjun Meng; Hanping Dai; Yanan Zheng; Junfan Fu (Cardiovascular Toxicology, 2016)

Removal of Color Compounds from Sugarcane Juice by Modified Sugarcane Bagasse: Equilibrium and Kinetic Study - Bo-hua Chai; He-cheng Meng; Zhen-gang Zhao; Qiang Huang; Xiong Fu (Sugar Tech, 2016)

Sorghum and Switchgrass as Biofuel Feedstocks on Marginal Lands in Northern China - Hai Mei Fu; Fan Yu Meng; R. L. Molatudi; Bao Gui Zhang (BioEnergy Research, 2016)

Mechanism of Rock Burst Occurrence in Specially Thick Coal Seam with Rock Parting - Jian-chao Wang; Fu-xing Jiang; Xiang-jun Meng; Xu-you Wang; Si-tao Zhu; Yu Feng (Rock Mechanics and Rock Engineering, 2016)

Rapid and highly efficient callus induction and plant regeneration in the starch-rich duckweed strains of Landoltia punctata - Meng Huang; Lili Fu; Xuepiao Sun; Rong Di; Jiaming Zhang (Acta Physiologiae Plantarum, 2016)

Insular Cortex is Critical for the Perception, Modulation, and Chronification of Pain - Changbo Lu; Tao Yang; Huan Zhao; Ming Zhang; Fancheng Meng; Hao Fu; Yingli Xie; Hui Xu (Neuroscience Bulletin, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Synthesis of some new thiazolo[3,2-a]pyrimidine derivatives and screening of their in vitro antibacterial and antitubercular activities - Dong Cai; Zhi-Hua Zhang; Yu Chen; Xin-Jia Yan; Shi-Ti Zhang; Liang-Jing Zou; Li-Hong Meng; Fang Li; Bing-Jie Fu (Medicinal Chemistry Research, 2016)

Effects of reconstructed magnetic field from sparse noisy boundary measurements on localization of active neural source - Hui-min Shen; Kok-Meng Lee; Liang Hu; Shaohui Foong; Xin Fu (Medical & Biological Engineering & Computing, 2016)

Two jasmonate-responsive factors, TcERF12 and TcERF15, respectively act as repressor and activator of tasy gene of taxol biosynthesis in Taxus chinensis - Meng Zhang; Shutao Li; Lin Nie; Qingpu Chen; Xiangping Xu; Longjiang Yu; Chunhua Fu (Plant Molecular Biology, 2015)

CEF1/OsMYB103L is involved in GA-mediated regulation of secondary wall biosynthesis in rice - Yafeng Ye; Binmei Liu; Meng Zhao; Kun Wu; Weimin Cheng; Xiangbin Chen; Qian Liu; Zan Liu; Xiangdong Fu; Yuejin Wu (Plant Molecular Biology, 2015)

The Effect of Continuous Sedation Therapy on Immunomodulation, Plasma Levels of Antioxidants, and Indicators of Tissue Repair in Post-Burn Sepsis Patients - Li Chen; Ke Meng; Wei Su; Yanjie Fu (Cell Biochemistry and Biophysics, 2015)

Automated rapid iterative negative geotaxis assay and its use in a genetic screen for modifiers of Aβ42-induced locomotor decline in Drosophila - Haiyan Liu; Meng Han; Qingyi Li; Xiao Zhang; Wen-An Wang; Fu-De Huang (Neuroscience Bulletin, 2015)

Upregulation of centromere protein H is associated with progression of renal cell carcinoma - Xun Wu; Youcheng Lin; Liping Shi; Yi Huang; Caiyong Lai; Yongqiang Wang; Meng Zhang; Shupeng Wang; Baoli Heng; Ganshen Yu; Xinghua Du; Lu Fang; et al. (Journal of Molecular Histology, 2015)

Recent changes in precipitation extremes in the Heihe River basin, Northwest China - Aifang Cheng; Qi Feng; Guobin Fu; Jiankai Zhang; Zongxing Li; Meng Hu; Gang Wang (Advances in Atmospheric Sciences, 2015)

miR-26a enhances autophagy to protect against ethanol-induced acute liver injury - Weidong Han; Xianghui Fu; Jiansheng Xie; Zhipeng Meng; Ying Gu; Xichun Wang; Ling Li; Hongming Pan; Wendong Huang (Journal of Molecular Medicine, 2015)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Chronic Metformin Preconditioning Provides Neuroprotection via Suppression of NF-κB-Mediated Inflammatory Pathway in Rats with Permanent Cerebral Ischemia - Xi-Chen Zhu; Teng Jiang; Qiao-Quan Zhang; Lei Cao; Meng-Shan Tan; Hui-Fu Wang; Zheng-Zheng Ding; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2015)

Generation by reverse genetics of an effective attenuated Newcastle disease virus vaccine based on a prevalent highly virulent Chinese strain - Meng-Meng Liu; Jin-Long Cheng; Xiao-Hui Yu; Zhuo-Ming Qin; Fu-Lin Tian; Guo-Zhong Zhang (Biotechnology Letters, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Natural incidence of Fusarium species and fumonisins B 1 and B 2 associated with maize kernels from nine provinces in China in 2012 - Meng Fu; Renjie Li; Congcong Guo; Minhao Pang; Yingchao Liu; Jingao Dong (Food Additives & Contaminants: Part A, 2015)

Challenges and adaptations of farming to climate change in the North China Plain - Hai-Lin Zhang; Xin Zhao; Xiao-Gang Yin; Sheng-Li Liu; Jian-Fu Xue; Meng Wang; Chao Pu; Rattan Lal; Fu Chen (Climatic Change, 2015)

Ischemic Preconditioning Provides Neuroprotection by Induction of AMP-Activated Protein Kinase-Dependent Autophagy in a Rat Model of Ischemic Stroke - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Qiao-Quan Zhang; Meng-Shan Tan; Lei Cao; Hui-Fu Wang; Jian-Quan Shi; Li Gao; Hao Qin; Ying-Dong Zhang; Lan Tan (Molecular Neurobiology, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Effective bioconversion of sophoricoside to genistein from Fructus sophorae using immobilized Aspergillus niger and Yeast - Chen Feng; Shuang Jin; Xin-Xin Xia; Yue Guan; Meng Luo; Yuan-Gang Zu; Yu-Jie Fu (World Journal of Microbiology and Biotechnology, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

Characteristics of Rocky Basin Structure of Yongshu Reef in the Southern South China Sea - Qing-Shan Meng; Ke-Fu Yu; Ren Wang; Yue Qin; Hou-Zhen Wei; Xin-Zhi Wang (Marine Georesources & Geotechnology, 2014)

Ion dynamics associated with substorm dipolarization fronts - Song Fu; Maha Ashour-Abdalla; XiaoHua Deng; Mostafa El-Alaoui; Meng Zhou; Robert L. Richard; Raymond J. Walker; ZhiGang Yuan (Science China Earth Sciences, 2014)

Comparison of elemental and black carbon measurements during normal and heavy haze periods: implications for research - Guorui Zhi; Yingjun Chen; Zhigang Xue; Fan Meng; Jing Cai; Guoying Sheng; Jiamo Fu (Environmental Monitoring and Assessment, 2014)

Phylogenetic assessment of Chaetomium indicum and allied species, with the introduction of three new species and epitypification of C. funicola and C. indicum - Xue-Wei Wang; Xiao-Liang Wang; Fu-Jiang Liu; Xiao-Meng Zhao; Jing Li; Lei Cai (Mycological Progress, 2014)

Constructing a dense genetic linkage map and mapping QTL for the traits of flower development in Brassica carinata - Jun Zou; Harsh Raman; Shaomin Guo; Dandan Hu; Zili Wei; Ziliang Luo; Yan Long; Wenxia Shi; Zhong Fu; Dezhi Du; Jinling Meng (Theoretical and Applied Genetics, 2014)

MJO prediction in the NCEP Climate Forecast System version 2 - Wanqiu Wang; Meng-Pai Hung; Scott J. Weaver; Arun Kumar; Xiouhua Fu (Climate Dynamics, 2014)

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

miR-124 Represses ROCK1 Expression to Promote Neurite Elongation Through Activation of the PI3K/Akt Signal Pathway - Xi Gu; Siying Meng; Shuhu Liu; Chunhong Jia; Yingying Fang; Shuji Li; Congcong Fu; Qiancheng Song; Lifang Lin; Xuemin Wang (Journal of Molecular Neuroscience, 2014)

Breed-linked polymorphisms of porcine toll-like receptor 2 (TLR2) and TLR4 and the primary investigation on their relationship with prevention against Mycoplasma pneumoniae and bacterial LPS challenge - Xiaomin Fang; Xiao Liu; Cui Meng; Yanfeng Fu; Xuemin Wang; Bixia Li; Feng Tu; Fang Zhao; Shouwen Ren (Immunogenetics, 2013)

Occurrence and fate of PPCPs and correlations with water quality parameters in urban riverine waters of the Pearl River Delta, South China - Xin Yang; Feng Chen; Fangang Meng; Yuanyu Xie; Hui Chen; Kyana Young; Wangxing Luo; Tingjin Ye; Wenjie Fu (Environmental Science and Pollution Research, 2013)

Yeast-Incorporated Gallium Attenuates Glucocorticoid-Induced Bone Loss in Rats by Inhibition of Bone Resorption - Zhaozhou Ren; Liqing Yang; Feng Xue; Qingjie Meng; Kejia Wang; Xian Wu; Chao Ji; Teng Jiang; Da Liu; Long Zhou; Jing Zhang; Qin Fu (Biological Trace Element Research, 2013)

Pedobacter hainanensis sp. nov., Isolated from Seaside Soil - Yan-yu Meng; Yun-bin Fu; Meng-yu Wang; Yong Zhao; Qi-shun Liu; Yu-guang Du (Current Microbiology, 2013)

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis - Shu-tao Li; Meng Zhang; Chun-hua Fu; Sha Xie; Yu Zhang; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

T-2 Toxin Contamination in Grains and Selenium Concentration in Drinking Water and Grains in Kaschin–Beck Disease Endemic Areas of Qinghai Province - Li-Yan Sun; Qiang Li; Fan-Gang Meng; Ying Fu; Zhi-Jun Zhao; Li-Hua Wang (Biological Trace Element Research, 2012)

Enhancing Taxol Biosynthesis by Overexpressing a 9-Cis-Epoxycarotenoid Dioxygenase Gene in Transgenic Cell Lines of Taxus chinensis - Shu-tao Li; Chun-hua Fu; Meng Zhang; Yu Zhang; Sha Xie; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Metabolic engineering of Bacillus subtilis for enhanced production of acetoin - Meng Wang; Jing Fu; Xueyu Zhang; Tao Chen (Biotechnology Letters, 2012)

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

A Comparison Study Between Spring and Summer Fogs in the Yellow Sea-Observations and Mechanisms - Suping Zhang; Man Li; Xiangui Meng; Gang Fu; Zhaopeng Ren; Shanhong Gao (Pure and Applied Geophysics, 2012)

Dual Porosity and Dual Permeability Modeling of Horizontal Well in Naturally Fractured Reservoir - Ren-Shi Nie; Ying-Feng Meng; Yong-Lu Jia; Fu-Xiang Zhang; Xiang-Tong Yang; Xin-Nian Niu (Transport in Porous Media, 2012)

An Accurate Method of Computing the Gradient of Seismic Wave Reflection Coefficients (SWRCs) for the Inversion of Stratum Parameters - Xiao-Bo Liu; Fu-Ping Liu; Xian-Jun Meng; Jia-Qi Xiao (Surveys in Geophysics, 2012)

DJ-1 may contribute to metastasis of non-small cell lung cancer - Jing Bai; Changlong Guo; Wenjing Sun; Ming Li; Xiangning Meng; Yang Yu; Yan Jin; Dandan Tong; Jingshu Geng; Qi Huang; Jiping Qi; Songbin Fu (Molecular Biology Reports, 2012)

Genetic dissection of intersubgenomic heterosis in Brassica napus carrying genomic components of B. rapa - Donghui Fu; Wei Qian; Jun Zou; Jinling Meng (Euphytica, 2012)

Methionine synthase reductase A66G polymorphism contributes to tumor susceptibility: evidence from 35 case–control studies - Dong Han; Chao Shen; Xiangning Meng; Jing Bai; Feng Chen; Yang Yu; Yan Jin; Songbin Fu (Molecular Biology Reports, 2012)

Synthesis and antihypertensive activity evaluation in spontaneously hypertensive rats of nitrendipine analogues - Kai Zhou; Xiao-meng Wang; Yi-zhi Zhao; Yong-xiao Cao; Qiang Fu; San-qi Zhang (Medicinal Chemistry Research, 2011)

cDNA cloning and characterization of UDP-glucose: anthocyanidin 3-O-glucosyltransferase in Freesia hybrida - Xin Sui; Xiang Gao; Man Ao; Qinmei Wang; Dan Yang; Meng Wang; Yang Fu; Li Wang (Plant Cell Reports, 2011)

Numerical simulation of fluxes generated by inhomogeneities of the underlying surface over the Jinta Oasis in Northwestern China - Wanli Li; Shihua Lü; Shenming Fu; Xianhong Meng; H. C. Nnamchi (Advances in Atmospheric Sciences, 2011)

Effect of tadalafil in chronic renal failure rabbits: relevance to erectile dysfunction - Meng-yuan Zhang; Qiang Fu; Wei Bian (Journal of Zhejiang University-SCIENCE B, 2011)

A dynamic model for genome-wide association studies - Kiranmoy Das; Jiahan Li; Zhong Wang; Chunfa Tong; Guifang Fu; Yao Li; Meng Xu; Kwangmi Ahn; David Mauger; Runze Li; Rongling Wu (Human Genetics, 2011)

Formation mechanism of high quality marine source rocks—Coupled control mechanism of geological environment and organism evolution - Tenger; Kai Hu; Qingqiang Meng; Juan Huang; Xiaodong Fu; Xiaomin Xie; Yunfeng Yang; Changlin Gao (Journal of Earth Science, 2011)

Cloning and characterization of a novel CoA-ligase gene from Penicillium chrysogenum - Zhou-Liang Yu; Jing Liu; Fu-Qiang Wang; Meng Dai; Bao-Hua Zhao; Jian-Gong He; Hua Zhang (Folia Microbiologica, 2011)

Frequency of double minute chromosomes and combined cytogenetic abnormalities and their characteristics - Yihui Fan; Renfang Mao; Hongpei Lv; Jie Xu; Lei Yan; Yanhong Liu; Meng Shi; Guohua Ji; Yang Yu; Jing Bai; Yan Jin; Songbin Fu (Journal of Applied Genetics, 2011)

The Removal of Ocular Artifacts from EEG Signals Using Adaptive Filters Based on Ocular Source Components - Hsiao-Lung Chan; Yu-Tai Tsai; Ling-Fu Meng; Tony Wu (Annals of Biomedical Engineering, 2010)

Genetic analysis and characterization of a new maize association mapping panel for quantitative trait loci dissection - Xiaohong Yang; Jianbing Yan; Trushar Shah; Marilyn L. Warburton; Qing Li; Lin Li; Yufeng Gao; Yuchao Chai; Zhiyuan Fu; Yi Zhou; Shutu Xu; Guanghong Bai; et al. (Theoretical and Applied Genetics, 2010)

Gene expression profiling in muscle tissues of the commercially important teleost, Siniperca chuatsi L. - Wuying Chu; Guihong Fu; Jia Chen; Dinggen Chen; Tao Meng; Ruixue Zhou; Xinjie Xia; Jianshe Zhang (Aquaculture International, 2010)

Diversity of five novel Y-STR loci and their application in studies of north Chinese populations - Zhaoyang Xu; Haiming Sun; Yang Yu; Yan Jin; Xaingning Meng; Donglin Sun; Jing Bai; Feng Chen; Songbin Fu (Journal of Genetics, 2010)

Broadening the avenue of intersubgenomic heterosis in oilseed Brassica - Jun Zou; Jiali Zhu; Shunmou Huang; Entang Tian; Yong Xiao; Donghui Fu; Jinxing Tu; Tingdong Fu; Jinling Meng (Theoretical and Applied Genetics, 2010)

Risk of digoxin intoxication caused by clarithromycin–digoxin interactions in heart failure patients: a population-based study - Agnes L. F. Chan; Meng-Ting Wang; Chen-Yi Su; Fu-Hsiung Tsai (European Journal of Clinical Pharmacology, 2009)

Undisturbed Strata Succession Sampling Technology and the Engineering Geological Characteristics of an Atoll in the Southern South China Sea - Qing-Shan Meng; Ren Wang; Ke-Fu Yu; Ming-Jian Hu; Xin-Zhi Wang; Chao Yang (Marine Georesources & Geotechnology, 2009)

Genome-wide analysis of gene expression profiles during ear development of maize - Yun Zhu; Junjie Fu; Jinpeng Zhang; Tingsong Liu; Zhiwei Jia; Jiashi Wang; Ying Jin; Yun Lian; Meng Wang; Jun Zheng; Wei Hou; Guoying Wang (Plant Molecular Biology, 2009)

A High Polymorphism Level in Rhinopithecus roxellana - Deng Pan; Hong-Xing Hu; Shi-Jie Meng; Zheng-Ming Men; Yun-Xin Fu; Ya-Ping Zhang (International Journal of Primatology, 2009)

Gene expression profiles associated with intersubgenomic heterosis in Brassica napus - Xin Chen; Maoteng Li; Jiaqin Shi; Donghui Fu; Wei Qian; Jun Zou; Chunyu Zhang; Jinling Meng (Theoretical and Applied Genetics, 2008)

Light distribution, photosynthetic rate and yield in a Paulownia-wheat intercropping system in China - Fangdong Li; Ping Meng; Dali Fu; Baoping Wang (Agroforestry Systems, 2008)

Classification of duck hepatitis virus into three genotypes based on molecular evolutionary analysis - Liyan Wang; Meng Pan; Yu Fu; Dabing Zhang (Virus Genes, 2008)

Effects of land use on phosphorus loss in the hilly area of the Loess Plateau, China - Qinghua Meng; Bojie Fu; Xiaoping Tang; Hongchang Ren (Environmental Monitoring and Assessment, 2008)

Use of geochemical modeling to evaluate the hydraulic connection of aquifers: a case study from Chianan Plain, Taiwan - Hsueh-Yu Lu; Tsung-Kwei Liu; Wen-Fu Chen; Tsung-Ren Peng; Chung-Ho Wang; Meng-Hsun Tsai; Tai-Sheng Liou (Hydrogeology Journal, 2008)

Identification of poly-reactive natural IgM antibody that recognizes late apoptotic cells and promotes phagocytosis of the cells - Meng Fu; Ping-shen Fan; Wei Li; Cheng-xin Li; Ying Xing; Jing-gang An; Gang Wang; Xue-li Fan; Tian-wen Gao; Yu-feng Liu; Shigaku Ikeda (Apoptosis, 2007)

Benzo[a]pyrene-induced cell cycle progression is through ERKs/cyclin D1 pathway and requires the activation of JNKs and p38 mapk in human diploid lung fibroblasts - Hong Ju Du; Ning Tang; Bing Ci Liu; Bao Rong You; Fu Hai Shen; Meng Ye; Ai Gao; Chuan Shu Huang (Molecular and Cellular Biochemistry, 2006)

Intersubgenomic heterosis in seed yield potential observed in a new type of Brassica napus introgressed with partial Brassica rapa genome - W. Qian; X. Chen; D. Fu; J. Zou; J. Meng (Theoretical and Applied Genetics, 2005)

Induced Activity of Superoxide Dismutase and Peroxidase of in vitro Plants by Low Concentrations of Ethanol - Xiu-Qing Li; Shi-Hua Li; De-Fu Chen; Fan-Rui Meng (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Application of MCR: Facile one-pot diastereoselective syntheses of novel chiral α,α'-iminodiacetic acid analogues - Kuangsen Sung; Fu-Lin Chen; Meng-Jung Chung (Molecular Diversity, 2003)